Abl family of tyrosine kinases and microbial pathogenesis - Wessler, Silja; Backert, Steffen (International Review of Cell and Molecular Biology, 2011)
Abl nonreceptor tyrosine kinases are activated by multiple stimuli and regulate cytoskeletal reorganization, cell proliferation, survival, and stress responses. Several downstream pathways have direct impact on physiological processes, including development and maintenance of the nervous and immune systems and epithelial morphogenesis. Recent studies also indicated that numerous viral and bacterial pathogens highjack Abl signaling for different purposes. Abl kinases are activated to reorganize the host actin cytoskeleton and promote the direct tyrosine phosphorylation of viral surface proteins and injected bacterial type-III and type-IV effector molecules. However, Abl kinases also play other roles in infectious processes of bacteria, viruses, and prions. These activities have crucial impact on microbial invasion and release from host cells, actin-based motility, pedestal formation, as well as cell-cell dissociation involved in epithelial barrier disruption and other responses. Thus, Abl kinases exhibit important functions in pathological signaling during microbial infections. Here, we discuss the different signaling pathways activated by pathogens and highlight possible therapeutic intervention strategies. © 2011 Elsevier Inc.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Abl kinase; Actin cytoskeleton; Molecular pathogenesis; Tyrosine phosphorylation

Activation of Abl by Helicobacter pylori: A Novel Kinase for CagA and Crucial Mediator of Host Cell Scattering - Tammer, Ina; Brandt, Sabine; Hartig, Roland; König, Wolfgang; Backert, Steffen (Gastroenterology, 2007)
Background & Aims: The pathogenesis of Helicobacter pylori (Hp)-associated diseases depends on a specialized type IV secretion system. This type IV secretion system injects the cytotoxin-associated gene A (CagA) effector protein into target cells where CagA becomes phosphorylated on tyrosine residues by Src. Src then is inactivated rapidly, suggesting the presence of another host tyrosine kinase to ensure constant CagA phosphorylation in sustained Hp infections. We aimed to identify this kinase. Methods: By using the AGS gastric epithelial cell model, we performed a detailed functional characterization of Abl tyrosine kinase in signaling during Hp infections. Results: We showed that Abl kinase is activated and a novel crucial mediator of Hp infections. First, Abl-specific inhibitors SKI-DV2-43 or STI571 (Gleevec, Novartis) and knockdown of c-Abl/Abl-related gene Arg by small hairpin and interfering RNAs efficiently inhibit CagA phosphorylation and cell scattering. Second, during infection, Abl is activated rapidly by autophosphorylation at Y-412. Third, both Abl and Src phosphorylated Y-899, Y-918, and Y-972 of CagA. Fourth, we found that the Abl substrate CrkII is phosphorylated at Y-221 in vivo. Fifth, overexpression of kinase-dead Abl (K290M) blocked Hp-induced actin cytoskeletal rearrangements. We further showed that sustained activity of Abl is required to maintain CagA in a phosphorylated state. Moreover, phosphorylated CagA forms a physical complex with Abl and activated CrkII in vivo. Conclusions: We propose a model in which Hp has evolved a mechanism to use at least 2 tyrosine kinases, Abl and Src, for CagA phosphorylation and subsequent actin-cytoskeletal rearrangements leading to cell scattering and elongation. © 2007 AGA Institute.
Created from Fastlane, Scopus look-up

A helical RGD motif promoting cell adhesion: Crystal structures of the helicobacter pylori type IV secretion system pilus protein CagL - Barden, Stephan; Lange, Stefanie; Tegtmeyer, Nicole; Conradi, Jens; Sewald, Norbert; Backert, Steffen; Niemann, Hartmut H. (Structure, 2013)
RGD tripeptide motifs frequently mediate ligand binding to integrins. The type IV secretion system (T4SS) protein CagL of the gastric pathogen Helicobacter pylori also contains an RGD motif. CagL decorates the T4SS pilus and may function as an adhesin for host cells. Whether CagL binds integrins via its RGD motif is under debate. Here, we present crystal structures of CagL revealing an elongated four-helix bundle that appears evolutionarily unrelated to the proposed VirB5 orthologs. The RGD motif is surface-exposed but located within a long α helix. This is unprecedented as previously characterized integrin-binding RGD motifs are located within extended or flexible loops. Yet, adhesion of gastric epithelial cells to CagL was strictly RGD-dependent. Comparison of seven crystallographically independent molecules reveals substantial structural flexibility. Intramolecular disulfide bonds engineered to reduce CagL flexibility resulted in more stable protein, but unable to support cell adhesion. CagL may thus partly unfold during receptor binding. © 2013 Elsevier Ltd.
Created from Fastlane, Scopus look-up

Amino-Terminal Processing of Helicobacter pylori Serine Protease HtrA: Role in Oligomerization and Activity Regulation - Albrecht, Nicole; Tegtmeyer, Nicole; Sticht, Heinrich; Skorko-Glonek, Joanna; Backert, Steffen (Frontiers in Microbiology, 2018)
The HtrA family of serine proteases is found in most bacteria, and plays an essential role in the virulence of the gastric pathogen Helicobacter pylori. Secreted H. pylori HtrA (HtrA(Hp)) cleaves various junctional proteins such as E-cadherin disrupting the epithelial barrier, which is crucial for bacterial transmigration across the polarized epithelium. Recent studies indicated the presence of two characteristic HtrAHp forms of 55 and 52 kDa (termed p55 and p52, respectively), in worldwide strains. In addition, p55 and p52 were produced by recombinant HtrA(Hp), indicating auto-cleavage. However, the cleavage sites and their functional importance are yet unclear. Here, we determined the amino-terminal ends of p55 and p52 by Edman sequencing. Two proteolytic cleavage sites were identified (H46/D47 and K50/D51). Remarkably, the cleavage site sequences are conserved in HtrA(Hp) from worldwide isolates, but not in other Gram-negative pathogens, suggesting a highly specific assignment in H. pylori. We analyzed the role of the amino-terminal cleavage sites on activity, secretion and function of HtrA(Hp). Three-dimensional modeling suggested a trimeric structure and a role of amino-terminal processing in oligomerization and regulation of proteolytic activity of HtrA(Hp). Furthermore, point and deletion mutants of these processing sites were generated in the recently reported Campylobacter jejuni 1 htrA/htrA(Hp) genetic complementation system and the minimal sequence requirements for processing were determined. Polarized Caco-2 epithelial cells were infected with these strains and analyzed by immunofluorescence microscopy. The results indicated that HtrA(Hp) processing strongly affected the ability of the protease to disrupt the E-cadherin-based cell-to-cell junctions. Casein zymography confirmed that the amino-terminal region is required for maintaining the proteolytic activity of HtrA(Hp). Furthermore, we demonstrated that this cleavage influences the secretion of HtrA(Hp) in the extracellular space as an important prerequisite for its virulence activity. Taken together, our data demonstrate that amino-terminal cleavage of HtrA(Hp) is conserved in this pathogen and affects oligomerization and thus, secretion and regulatory activities, suggesting an important role in the pathogenesis of H. pylori.
EVALuna2:35494

A novel basolateral type IV secretion model for the CagA oncoprotein of helicobacter pylori - Wessler, Silja; Backert, Steffen (Microbial Cell, 2018)
Intercellular junctions are crucial structural elements for the formation and maintenance of epithelial barrier functions to control homeostasis or protect against intruding pathogens in humans. Alterations in these complexes represent key events in the development and progression of numerous cancers as well as multiple infectious diseases. Many bacterial pathogens harbor type IV secretion systems (T4SSs), which translo-cate virulence factors into host cells to hijack cellular processes. The pathology of the gastric pathogen and type-I carcinogen Helicobacter pylori strongly depends on a T4SS encoded by the cag pathogenicity island (cagPAI). This T4SS forms a needle-like pilus and its activity is accomplished by the pilus-associated factors CagL, CagI and CagY which target the host integrin-β1 receptor followed by injection of the CagA oncoprotein into non-polarized AGS gastric epithelial cells. The finding of a T4SS receptor, however, suggested the presence of a sophisticated control mechanism for the injection of CagA. In fact, integrins constitute a group of basolateral receptors, which are normally absent at apical surfaces of the polarized epithelium in vivo. Our new results demonstrate that T4SS-pilus formation during H. pylori infection of polarized epithelial cells occurs preferentially at basolateral sites, and not at apical membranes (Tegtmeyer et al., 2017). We propose a stepwise process how H. pylori interacts with components of intercellular tight junctions (TJs) and adherens junctions (AJs), followed by contacting integ-rin-based focal adhesions to disrupt and transform the epithelial cell layer in the human stomach. The possible impact of this novel signaling cascade on pathogenesis during infection is reviewed.
Created from Fastlane, Scopus look-up
Keywords: CagA; Claudin; E-cadherin; Focal adhesions; Helicobacter; HtrA; Integrin; Occludin; Protease; T4SS

An RGD helper sequence in CagL of Helicobacter pylori assists in interactions with integrins and injection of CagA. - Conradi, Jens; Tegtmeyer, Nicole; Wozna, Marta; Wissbrock, Marco; Michalek, Carmela; Gagell, Corinna; Cover, Timothy L.; Frank, Ronald; Sewald, Norbert; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2012)
Helicobacter pylori is a specific gastric pathogen that colonizes the stomach in more than 50% of the world's human population. Infection with this bacterium can induce several types of gastric pathology, ranging from chronic gastritis to peptic ulcers and even adenocarcinoma. Virulent H. pylori isolates encode components of a type IV secretion system (T4SS), which form a pilus for the injection of virulence proteins such as CagA into host target cells. This is accomplished by a specialized adhesin on the pilus surface, the protein CagL, a putative VirB5 ortholog, which binds to host cell β(1) integrin, triggering subsequent delivery of CagA across the host cell membrane. Like the human extracellular matrix protein fibronectin, CagL contains an RGD (Arg-Gly-Asp) motif and is able to trigger intracellular signaling pathways by RGD-dependent binding to integrins. While CagL binding to host cells is mediated primarily by the RGD motif, we identified an auxiliary binding motif for CagL-integrin interaction. Here, we report on a surface exposed FEANE (Phe-Glu-Ala-Asn-Glu) interaction motif in spatial proximity to the RGD sequence, which enhances the interactions of CagL with integrins. It will be referred to as RGD helper sequence (RHS). Competitive cell adhesion assays with recombinant wild type CagL and point mutants, competition experiments with synthetic cyclic and linear peptides, and peptide array experiments revealed amino acids essential for the interaction of the RHS motif with integrins. Infection experiments indicate that the RHS motif plays a role in the early interaction of H. pylori T4SS with integrin, to trigger signaling and to inject CagA into host cells. We thus postulate that CagL is a versatile T4SS surface protein equipped with at least two motifs to promote binding to integrins, thereby causing aberrant signaling within host cells and facilitating translocation of CagA into host cells, thus contributing directly to H. pylori pathogenesis.
Created from Fastlane, Scopus look-up

A simplified and cost-effective enrichment protocol for the isolation of Campylobacter spp. from retail broiler meat without microaerobic incubation - Zhou, Ping; Hussain, Syeda K.; Liles, Mark R.; Arias, Covadonga R.; Backert, Steffen; Kieninger, Jessica; Oyarzabal, Omar A. (BMC Microbiology, 2011)
Background: To simplify the methodology for the isolation of Campylobacter spp. from retail broiler meat, we evaluated 108 samples (breasts and thighs) using an unpaired sample design. The enrichment broths were incubated under aerobic conditions (subsamples A) and for comparison under microaerobic conditions (subsamples M) as recommended by current reference protocols. Sensors were used to measure the dissolved oxygen (DO) in the broth and the percentage of oxygen (O2) in the head space of the bags used for enrichment. Campylobacter isolates were identified with multiplex PCR assays and typed using pulsed-field gel electrophoresis (PFGE). Ribosomal intergenic spacer analyses (RISA) and denaturing gradient gel electrophoresis (DGGE) were used to study the bacterial communities of subsamples M and A after 48 h enrichment. Results: The number of Campylobacter positive subsamples were similar for A and M when all samples were combined (P = 0.81) and when samples were analyzed by product (breast: P = 0.75; thigh: P = 1.00). Oxygen sensors showed that DO values in the broth were around 6 ppm and O2values in the head space were 14-16% throughout incubation. PFGE demonstrated high genomic similarity of isolates in the majority of the samples in which isolates were obtained from subsamples A and M. RISA and DGGE results showed a large variability in the bacterial populations that could be attributed to sample-to-sample variations and not enrichment conditions (aerobic or microaerobic). These data also suggested that current sampling protocols are not optimized to determine the true number of Campylobacter positive samples in retail boiler meat. Conclusions: Decreased DO in enrichment broths is naturally achieved. This simplified, cost-effective enrichment protocol with aerobic incubation could be incorporated into reference methods for the isolation of Campylobacter spp. from retail broiler meat. © 2011 Zhou et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

A single-nucleotide polymorphism in Helicobacter pylori promotes gastric cancer development - Sharafutdinov, Irshad; Tegtmeyer-Backert, Nicole; Linz, Bodo; Rohde, Manfred; Vieth, Michael; Tay, Alfred Chin Yen; Lamichhane, Binit; Tuan, Vo Phuoc; Fauzia, Kartika Afrida; Sticht, Heinrich; Yamaoka, Yoshio; Marshall, Barry J.; et al. (Cell Host & Microbe, 2023)
Single-nucleotide polymorphisms (SNPs) in various human genes are key factors in carcinogenesis. However, whether SNPs in bacterial pathogens are similarly crucial in cancer development is unknown. Here, we analyzed 1,043 genomes of the stomach pathogen Helicobacter pylori and pinpointed a SNP in the serine protease HtrA (position serine/leucine 171) that significantly correlates with gastric cancer. Our functional studies reveal that the 171S-to-171L mutation triggers HtrA trimer formation and enhances proteolytic activity and cleavage of epithelial junction proteins occludin and tumor-suppressor E-cadherin. 171L-type HtrA, but not 171S-HtrA-possessing H. pylori, inflicts severe epithelial damage, enhances injection of oncoprotein CagA into epithelial cells, increases NF-κB-mediated inflammation and cell proliferation through nuclear accumulation of β-catenin, and promotes host DNA double-strand breaks, collectively triggering malignant changes. These findings highlight the 171S/L HtrA mutation as a unique bacterial cancer-associated SNP and as a potential biomarker for risk predictions in H. pylori infections.
CRIS-Team Scopus Importer:2023-08-25
Keywords: 53BP1; DNA double-strand breaks; gastric cancer; H. pylori; HtrA; NF-κB; PFGE; signaling; SNP; β-catenin

A small fibronectin-mimicking protein from bacteria induces cell spreading and focal adhesion formation - Tegtmeyer, Nicole; Hartig, Roland; Delahay, Robin M.; Rohde, Manfred; Brandt, Sabine; Conradi, Jens; Takahashi, Seiichiro; Smolka, Adam J.; Sewald, Norbert; Backert, Steffen (Journal of Biological Chemistry, 2010)
Fibronectin, a 250-kDa eukaryotic extracellular matrix protein containing an RGD motif plays crucial roles in cell-cell communication, development, tissue homeostasis, and disease development. The highly complex fibrillar fibronectin meshwork orchestrates the functions of other extracellular matrix proteins, promoting cell adhesion, migration, and intracellular signaling. Here, we demonstrate that CagL, a 26-kDa protein of the gastric pathogen and type I carcinogen Helicobacter pylori, mimics fibronectin in various cellular functions. Like fibronectin, CagL contains a RGD motif and is located on the surface of the bacterial type IV secretion pili as previously shown. CagL binds to the integrin receptor α5β1 and mediates the injection of virulence factors into host target cells. We show that purified CagL alone can directly trigger intracellular signaling pathways upon contact with mammalian cells and can complement the spreading defect of fibronectin -/- knock-out cells in vitro. During interaction with various human and mouse cell lines, CagL mimics fibronectin in triggering cell spreading, focal adhesion formation, and activation of several tyrosine kinases in an RGD-dependent manner. Among the activated factors are the nonreceptor tyrosine kinases focal adhesion kinase and Src but also the epidermal growth factor receptor and epidermal growth factor receptor family member Her3/ErbB3. Interestingly, fibronectin activates a similar range of tyrosine kinases but not Her3/ErbB3. These findings suggest that the bacterial protein CagL not only exhibits functional mimicry with fibronectin but is also capable of activating fibronectin-independent signaling events. We thus postulate that CagL may contribute directly to H. pylori pathogenesis by promoting aberrant signaling crosstalk within host cells. © 2010 by The American Society for Biochemistry and Molecular Biology, Inc.
Created from Fastlane, Scopus look-up

A specific A/T polymorphism in Western tyrosine phosphorylation B-motifs regulates Helicobacter pylori CagA epithelial cell interactions - Zhang, Xue-Song; Tegtmeyer, Nicole; Traube, Leah; Jindal, Shawn; Perez-Perez, Guillermo; Sticht, Heinrich; Backert, Steffen; Blaser, Martin J. (PLoS Pathogens, 2015)
Helicobacter pylori persistently colonizes the human stomach, with mixed roles in human health. The CagA protein, a key host-interaction factor, is translocated by a type IV secretion system into host epithelial cells, where its EPIYA tyrosine phosphorylation motifs (TPMs) are recognized by host cell kinases, leading to multiple host cell signaling cascades. The CagA TPMs have been described as type A, B, C or D, each with a specific conserved amino acid sequence surrounding EPIYA. Database searching revealed strong non-random distribution of the B-motifs (including EPIYA and EPIYT) in Western H. pylori isolates. In silico analysis of Western H. pylori CagA sequences provided evidence that the EPIYT B-TPMs are significantly less associated with gastric cancer than the EPIYA B-TPMs. By generating and using a phosphorylated CagA B-TPM-specific antibody, we demonstrated the phosphorylated state of the CagA B-TPM EPIYT during H. pylori co-culture with host cells. We also showed that within host cells, CagA interaction with phosphoinositol 3-kinase (PI3-kinase) was B-TPM tyrosine-phosphorylation-dependent, and the recombinant CagA with EPIYT B-TPM had higher affinity to PI3-kinase and enhanced induction of AKT than the isogenic CagA with EPIYA B-TPM. Structural modeling of the CagA B-TPM motif bound to PI3-kinase indicated that the threonine residue at the pY+1 position forms a side-chain hydrogen bond to N-417 of PI3-kinase, which cannot be formed by alanine. During co-culture with AGS cells, an H. pylori strain with a CagA EPIYT B-TPM had significantly attenuated induction of interleukin-8 and hummingbird phenotype, compared to the isogenic strain with B-TPM EPIYA. These results suggest that the A/T polymorphisms could regulate CagA activity through interfering with host signaling pathways related to carcinogenesis, thus influencing cancer risk.
EVALuna2:26288

Bacterial serine protease HtrA as a promising new target for antimicrobial therapy? - Wessler, Silja; Schneider, Gisbert; Backert, Steffen (Cell Communication and Signaling, 2017)
Recent studies have demonstrated that the bacterial chaperone and serine protease high temperature requirement A (HtrA) is closely associated with the establishment and progression of several infectious diseases. HtrA activity enhances bacterial survival under stress conditions, but also has direct effects on functions of the cell adhesion protein E-cadherin and extracellular matrix proteins, including fibronectin and proteoglycans. Although HtrA cannot be considered as a pathogenic factor per se, it exhibits favorable characteristics making HtrA a potentially attractive drug target to combat various bacterial infections.
Created from Fastlane, Scopus look-up

Bacterial type III effectors inhibit cell lifting by targeting integrin-linked kinase. - Tegtmeyer, Nicole; Backert, Steffen (Cell Host & Microbe, 2009)
Many pathogenic bacteria are able to surmount exfoliation and colonize the host epithelium efficiently. In a recent article in Nature, Kim et al. (2009) show that Shigella flexneri OspE, a conserved type III effector, reinforces host cell adherence and prevents detachment of the infected cells by interacting with integrin-linked kinase.

Binding of Helicobacter pylori to Human Gastric Mucins Correlates with Binding of TFF1. - Dunne, Ciara; Naughton, Julie; Duggan, Gina; Loughrey, Catherine; Kilcoyne, Michelle; Joshi, Lokesh; Carrington, Stephen; Earley, Helen; Backert, Steffen; Masselot, Catherine Robbe; May, Felicity E. B.; Clyne, Marguerite (Microorganisms, 2018)

Biochemical and functional characterization of Helicobacter pylori vesicles - Olofsson, Annelie; Vallstrom, Anna; Petzold, Katja; Tegtmeyer, Nicole; Schleucher, Jurgen; Carlsson, Sven; Haas, Rainer; Backert, Steffen; Wai, Sun Nyunt; Grobner, Gerhard; Arnqvist, Anna (Molecular Microbiology, 2010)
Summary Helicobacter pylori can cause peptic ulcer disease and/or gastric cancer. Adhesion of bacteria to the stomach mucosa is an important contributor to the vigour of infection and resulting virulence. H. pylori adheres primarily via binding of BabA adhesins to ABO/Lewis b (Leb) blood group antigens and the binding of SabA adhesins to sialyl-Lewis x/a (sLex/a) antigens. Similar to most Gram-negative bacteria, H. pylori continuously buds off vesicles and vesicles derived from pathogenic bacteria often include virulence-associated factors. Here we biochemically characterized highly purified H. pylori vesicles. Major protein and phospholipid components associated with the vesicles were identified with mass spectroscopy and nuclear magnetic resonance. A subset of virulence factors present was confirmed by immunoblots. Additional functional and biochemical analysis focused on the vesicle BabA and SabA adhesins and their respective interactions to human gastric epithelium. Vesicles exhibit heterogeneity in their protein composition, which were specifically studied in respect to the BabA adhesin. We also demonstrate that the oncoprotein, CagA, is associated with the surface of H. pylori vesicles. Thus, we have explored mechanisms for intimate H. pylori vesicle-host interactions and found that the vesicles carry effector-promoting properties that are important to disease development. © 2010 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Biochemical properties of the HtrA homolog from bacterium Stenotrophomonas maltophilia - Zarzecka, Urszula; Zarzecka, Urszula; Modrak-Wojcik, Anna; Bayassi, Martyna; Szewczyk, Maciej; Gieldon, Artur; Lesner, Adam; Koper, Tomasz; Bzowska, Agnieszka; Sanguinetti, Maurizio; Backert, Steffen; Lipinska, Barbara; et al. (International Journal of Biological Macromolecules, 2018)

cag+ Helicobacter pylori induces homotypic aggregation of macrophage-like cells by up-regulation and recruitment of intracellular adhesion molecule 1 to the cell surface. - Moese, S.; Selbach, M.; Meyer, Thomas F.; Backert, Steffen (Infection and Immunity, 2002)
Infection with cag+ but not cag-negative Helicobacter pylori leads to the formation of large homotypic aggregates of macrophage-like cells. Intracellular adhesion molecule 1 is up-regulated and recruited to the cell surface of infected cells and mediates the aggregation via lymphocyte function-associated molecule 1. This signaling may regulate cell-cell interactions and inflammatory responses.

Campylobacteriose — eine zoonotische Infektionskrankheit - Alter, Thomas; Bereswill, Stefan; Backert, Steffen (BioSpektrum, 2021)
Campylobacter jejuni represents an important zoonotic pathogen that is causing foodborne enteric infections. In the human gut, C. jejuni bacteria induce intestinal campylobacteriosis which can develop into systemic post-infectious sequelae such as Guillain-Barré syndrome or rheumatoid arthritis. Here, we review the pathobiology and molecular mechanisms of C. jejuni infections as well as promising strategies to combat campylobacteriosis within the “One World — One Health” approach.
CRIS-Team Scopus Importer:2021-10-22

Campylobacter jejuni enters gut epithelial cells and impairs intestinal barrier function through cleavage of occludin by serine protease HtrA - Harrer, Aileen; Buecker, Roland; Böhm, Manja; Zarzecka, Urszula; Tegtmeyer, Nicole; Sticht, Heinrich; Schulzke, Joerg D.; Backert, Steffen (Gut Pathogens, 2019)
Campylobacter jejuni secretes HtrA (high temperature requirement protein A), a serine protease that is involved in virulence. Here, we investigated the interaction of HtrA with the host protein occludin, a tight junction strand component. Immunofluorescence studies demonstrated that infection of polarized intestinal Caco-2 cells with C. jejuni strain 81-176 resulted in a redistribution of occludin away from the tight junctions into the cytoplasm, an effect that was also observed in human biopsies during acute campylobacteriosis. Occludin knockout Caco-2 cells were generated by CRISPR/Cas9 technology. Inactivation of this gene affected the polarization of the cells in monolayers and transepithelial electrical resistance (TER) was reduced, compared to wild-type Caco-2 cells. Although tight junctions were still being formed, occludin deficiency resulted in a slight decrease of the tight junction plaque protein ZO-1, which was redistributed off the tight junction into the lateral plasma membrane. Adherence of C. jejuni to Caco-2 cell monolayers was similar between the occludin knockout compared to wild-type cells, but invasion was enhanced, indicating that deletion of occludin allowed larger numbers of bacteria to pass the tight junctions and to reach basal membranes to target the fibronectin receptor followed by cell entry. Finally, we discovered that purified C. jejuni HtrA cleaves recombinant occludin in vitro to release a 37 kDa carboxy-terminal fragment. The same cleavage fragment was observed in Western blots upon infection of polarized Caco-2 cells with wild-type C. jejuni, but not with isogenic Delta htrA mutants. HtrA cleavage was mapped to the second extracellular loop of occludin, and a putative cleavage site was identified. In conclusion, HtrA functions as a secreted protease targeting the tight junctions, which enables the bacteria by cleaving occludin and subcellular redistribution of other tight junction proteins to transmigrate using a paracellular mechanism and subsequently invade epithelial cells.
CRIS-Team WoS Importer:2019-03-06

Campylobacter jejuni Serine Protease HtrA Cleaves the Tight Junction Component Claudin-8 - Sharafutdinov, Irshad; Soltan Esmaeili, Delara; Harrer, Aileen; Tegtmeyer, Nicole; Sticht, Heinrich; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2020)
Campylobacter jejuni express the high temperature requirement protein A (HtrA), a secreted serine protease, which is implicated in virulence properties of the pathogen. Previous studies have shown that C. jejuni HtrA can cleave the epithelial transmembrane proteins occludin and E-cadherin in the tight and adherens junctions, respectively. In the present report, we studied the interaction of HtrA with another human tight junction protein, claudin-8. Confocal immunofluorescence experiments have shown that C. jejuni infection of the intestinal polarized epithelial cells in vitro leads to a relocation of claudin-8. Wild-type C. jejuni induced the downregulation of claudin-8 signals in the tight junctions and an accumulation of claudin-8 agglomerates in the cytoplasm, which were not seen during infection with isogenic Delta htrA knockout deletion or protease-inactive S197A point mutants. Western blotting of protein samples from infected vs. uninfected cells revealed that an 18-kDa carboxy-terminal fragment is cleaved-off from the 26-kDa full-length claudin-8 protein, but not during infection with the isogenic Delta htrA mutant. These results were confirmed by in vitro cleavage assays using the purified recombinant C. jejuni HtrA and human claudin-8 proteins. Recombinant HtrA cleaved purified claudin-8 in vitro giving rise to the same 18-kDa sized carboxy-terminal cleavage product. Mapping studies revealed that HtrA cleavage occurs in the first extracellular loop of claudin-8. Three-dimensional modeling of the claudin-8 structure identified an exposed HtrA cleavage site between the amino acids alanine 58 and asparagine 59, which is in well agreement with the mapping studies. Taken together, HtrA operates as a secreted virulence factor targeting multiple proteins both in the tight and adherens junctions. This strategy may help the bacteria to open the cell-to-cell junctions, and to transmigrate across the intestinal epithelium by a paracellular mechanism and establish an acute infection.
CRIS-Team WoS Importer:2021-01-08

Campylobacter jejuni Serine Protease HtrA Induces Paracellular Transmigration of Microbiota across Polarized Intestinal Epithelial Cells - Sharafutdinov, Irshad; Tegtmeyer, Nicole; Müsken, Mathias; Backert, Steffen (Biomolecules, 2022)
Campylobacter jejuni represents an eminent zoonotic germ responsible for foodborne infections causing campylobacteriosis. In addition, infections with C. jejuni constitute a risk factor for the occurrence of inflammatory bowel disease (IBD). In the latter case, patients show inflammatory reactions not only against C. jejuni, but also against the non-infectious microbiota. However, the involved mechanisms and molecular basis are still largely unclear. We recently reported that C. jejuni breaches the intestinal epithelial barrier by secretion of serine protease HtrA (high temperature requirement A), which cleaves several major tight and adherens junction proteins. In the present study, we aimed to study if HtrAexpressing C. jejuni may also trigger the transepithelial migration of non-pathogenic gastrointestinal microbiota. Using confocal immunofluorescence and scanning electron microscopy, we demonstrate that C. jejuni wild-type (wt) as well as the isogenic ∆htrA mutant bind to the surface of polarized intestinal Caco-2 epithelial cells, but do not invade them at the apical side. Instead, C. jejuni wt, but not ∆htrA mutant, disrupt the cellular junctions and transmigrate using the paracellular route between neighboring cells. Using transwell filter systems, we then co-incubated the cells with C. jejuni and non-invasive microbiota strains, either Escherichia coli or Lactococcus lactis. Interestingly, C. jejuni wt, but not ∆htrA mutant, induced the efficient transmigration of these microbiota bacteria into the basal compartment. Thus, infection of the intestinal epithelium with C. jejuni causes local opening of cellular junctions and paracellular translocation in an HtrA-dependent manner, which paves the way for transmigration of microbiota that is otherwise non-invasive. Taken together, these findings may have impacts on various Campylobacter-associated diseases such as IBD, which are discussed here.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Campylobacter; commensal; E-cadherin; Escherichia coli; HtrA; Lactococcus lactis; microbiota; serine protease; tight junction

Campylobacter jejuni serine protease HtrA plays an important role in heat tolerance, oxygen resistance, host cell adhesion, invasion, and transmigration. - Böhm, Manja; Lind, Judith; Backert, Steffen; Tegtmeyer, Nicole (European Journal of Microbiology and Immunology, 2015)
Campylobacter jejuni is an important pathogen of foodborne illness. Transmigration across the intestinal epithelial barrier and invasion are considered as primary reasons for tissue damage triggered by C. jejuni. Using knockout mutants, it was shown that the serine protease HtrA may be important for stress tolerance and physiology of C. jejuni. HtrA is also secreted in the extra-cellular environment, where it can cleave junctional host cell proteins such as E-cadherin. Aim of the present study was to establish a genetic complementation system in two C. jejuni strains in order to introduce the wild-type htrA gene in trans, test known htrA phenotypes, and provide the basis to perform further mutagenesis. We confirm that reexpression of the htrA wild-type gene in ΔhtrA mutants restored the following phenotypes: 1) C. jejuni growth at high temperature (44 °C), 2) growth under high oxygen stress conditions, 3) expression of proteolytically active HtrA oligomers, 4) secretion of HtrA into the supernatant, 5) cell attachment and invasion, and 6) transmigration across polarized epithelial cells. These results establish a genetic complementation system for htrA in C. jejuni, exclude polar effects in the ΔhtrA mutants, confirm important HtrA properties, and permit the discovery and dissection of new functions.

Campylobacter jejuni Surface-Bound Protease HtrA, but Not the Secreted Protease nor Protease in Shed Membrane Vesicles, Disrupts Epithelial Cell-to-Cell Junctions - Sharafutdinov, Irshad; Tegtmeyer, Nicole; Rohde, Manfred; Olofsson, Annelie; Rehman, Zia ur; Arnqvist, Anna; Backert, Steffen (Cells, 2024)
Fundamental functions of the intestinal epithelium include the digestion of food, absorption of nutrients, and its ability to act as the first barrier against intruding microbes. Campylobacter jejuni is a major zoonotic pathogen accounting for a substantial portion of bacterial foodborne illnesses. The germ colonizes the intestines of birds and is mainly transmitted to humans through the consumption of contaminated poultry meat. In the human gastrointestinal tract, the bacterium triggers campylobacteriosis that can progress to serious secondary disorders, including reactive arthritis, inflammatory bowel disease and Guillain–Barré syndrome. We recently discovered that C. jejuni serine protease HtrA disrupts intestinal epithelial barrier functions via cleavage of the tight and adherens junction components occludin, claudin-8 and E-cadherin. However, it is unknown whether epithelial damage is mediated by the secreted soluble enzyme, by HtrA contained in shed outer-membrane vesicles (OMVs) or by another mechanism that has yet to be identified. In the present study, we investigated whether soluble recombinant HtrA and/or purified OMVs induce junctional damage to polarized intestinal epithelial cells compared to live C. jejuni bacteria. By using electron and confocal immunofluorescence microscopy, we show that HtrA-expressing C. jejuni bacteria trigger efficient junctional cell damage, but not soluble purified HtrA or HtrA-containing OMVs, not even at high concentrations far exceeding physiological levels. Instead, we found that only bacteria with active protein biosynthesis effectively cleave junctional proteins, which is followed by paracellular transmigration of C. jejuni through the epithelial cell layer. These findings shed new light on the pathogenic activities of HtrA and virulence strategies of C. jejuni.
CRIS-Team Scopus Importer:2024-04-26
Keywords: Campylobacter; E-cadherin; occludin; serine protease HtrA; tight junctions

Campylobacter Virulence Factors and Molecular Host-Pathogen Interactions - Tegtmeyer, Nicole; Sharafutdinov, Irshad; Harrer, Aileen; Soltan Esmaeili, Delara; Linz, Bodo; Backert, Steffen (Current Topics in Microbiology and Immunology, 2021)
Campylobacter jejuni and Campylobacter coli can be frequently isolated from poultry and poultry-derived products, and in combination these two species cause a large portion of human bacterial gastroenteritis cases. While birds are typically colonized by these Campylobacter species without clinical symptoms, in humans they cause (foodborne) infections at high frequencies, estimated to cost billions of dollars worldwide every year. The clinical outcome of Campylobacter infections comprises malaise, diarrhea, abdominal pain and fever. Symptoms may continue for up to two weeks and are generally self-limiting, though occasionally the disease can be more severe or result in post-infection sequelae. The virulence properties of these pathogens have been best-characterized for C. jejuni, and their actions are reviewed here. Various virulence-associated bacterial determinants include the flagellum, numerous flagellar secreted factors, protein adhesins, cytolethal distending toxin (CDT), lipooligosaccharide (LOS), serine protease HtrA and others. These factors are involved in several pathogenicity-linked properties that can be divided into bacterial chemotaxis, motility, attachment, invasion, survival, cellular transmigration and spread to deeper tissue. All of these steps require intimate interactions between bacteria and host cells (including immune cells), enabled by the collection of bacterial and host factors that have already been identified. The assortment of pathogenicity-associated factors now recognized for C. jejuni, their function and the proposed host cell factors that are involved in crucial steps leading to disease are discussed in detail.
CRIS-Team Scopus Importer:2021-03-19
Keywords: CadF; CheY; CiaB; FlpA; JlpA

Cancer-associated SNPs in bacteria: lessons from Helicobacter pylori - Linz, Bodo; Sticht, Heinrich; Tegtmeyer, Nicole; Backert, Steffen (Trends in Microbiology, 2024)
Several single-nucleotide polymorphisms (SNPs) in human chromosomes are known to predispose to cancer. However, cancer-associated SNPs in bacterial pathogens were unknown until discovered in the stomach pathogen Helicobacter pylori. Those include an alanine-threonine polymorphism in the EPIYA-B phosphorylation motif of the injected effector protein CagA that affects cancer risk by modifying inflammatory responses and loss of host cell polarity. A serine-to-leucine change in serine protease HtrA is associated with boosted proteolytic cleavage of epithelial junction proteins and introduction of DNA double-strand breaks (DSBs) in host chromosomes, which co-operatively elicit malignant alterations. In addition, H. pylori genome-wide association studies (GWAS) identified several other SNPs potentially associated with increased gastric cancer (GC) risk. Here we discuss the clinical importance, evolutionary origin, and functional advantage of the H. pylori SNPs. These exciting new data highlight cancer-associated SNPs in bacteria, which should be explored in more detail in future studies.
CRIS-Team Scopus Importer:2025-02-04
Keywords: CagA; gastric cancer; GWAS; HtrA; SNP; T4SS

Chaperone activity of serine protease HtrA of Helicobacter pylori as a crucial survival factor under stress conditions - Zarzecka, Urszula; Harrer, Aileen; Zawilak-Pawlik, Anna; Skorko-Glonek, Joanna; Backert, Steffen (Cell Communication and Signaling, 2019)
Background: Serine protease HtrA exhibits both proteolytic and chaperone activities, which are involved in cellular protein quality control. Moreover, HtrA is an important virulence factor in many pathogens including Helicobacter pylori, for which the crucial stage of infection is the cleavage of E-cadherin and other cell-to-cell junction proteins. Methods: The in vitro study of H. pylori HtrA (HtrA Hp ) chaperone activity was carried out using light scattering assays and investigation of lysozyme protein aggregates. We produced H. pylori ∆htrA deletion and HtrA Hp point mutants without proteolytic activity in strain N6 and investigated the survival of the bacteria under thermal, osmotic, acidic and general stress conditions as well as the presence of puromycin or metronidazole using serial dilution tests and disk diffusion method. The levels of cellular and secreted proteins were examined using biochemical fraction and Western blotting. We also studied the proteolytic activity of secreted HtrA Hp using zymography and the enzymatic digestion of β-casein. Finally, the consequences of E-cadherin cleavage were determined by immunofluorescence microscopy. Results: We demonstrate that HtrA Hp displays chaperone activity that inhibits the aggregation of lysozyme and is stable under various pH and temperature conditions. Next, we could show that N6 expressing only HtrA chaperone activity grow well under thermal, pH and osmotic stress conditions, and in the presence of puromycin or metronidazole. In contrast, in the absence of the entire htrA gene the bacterium was more sensitive to a number of stresses. Analysing the level of cellular and secreted proteins, we noted that H. pylori lacking the proteolytic activity of HtrA display reduced levels of secreted HtrA. Moreover, we compared the amounts of secreted HtrA from several clinical H. pylori strains and digestion of β-casein. We also demonstrated a significant effect of the HtrA Hp variants during infection of human epithelial cells and for E-cadherin cleavage. Conclusion: Here we identified the chaperone activity of the HtrA Hp protein and have proven that this activity is important and sufficient for the survival of H. pylori under multiple stress conditions. We also pinpointed the importance of HtrA Hp chaperone activity for E- cadherin degradation and therefore for the virulence of this eminent pathogen.
CRIS-Team Scopus Importer:2019-12-13
Keywords: Chaperone; E- cadherin; Helicobacter pylori; HtrA; Protease; Protein quality control system; Secreted proteins; Stress endurance; Virulence factor

Characterisation of worldwide Helicobacter pylori strains reveals genetic conservation and essentiality of serine protease HtrA - Tegtmeyer, Nicole; Moodley, Yoshan; Yamaoka, Yoshio; Pernitzsch, Sandy Ramona; Schmidt, Vanessa; Traverso, Francisco Rivas; Schmidt, Thomas P.; Rad, Roland; Yeoh, Khay Guan; Bow, Ho; Torres, Javier; Gerhard, Markus; et al. (Molecular Microbiology, 2016)
HtrA proteases and chaperones exhibit important roles in periplasmic protein quality control and stress responses. The genetic inactivation of htrA has been described for many bacterial pathogens. However, in some cases such as the gastric pathogen Helicobacter pylori, HtrA is secreted where it cleaves the tumour-suppressor E-cadherin interfering with gastric disease development, but the generation of htrA mutants is still lacking. Here, we show that the htrA gene locus is highly conserved in worldwide strains. HtrA presence was confirmed in 992 H.pylori isolates in gastric biopsy material from infected patients. Differential RNA-sequencing (dRNA-seq) indicated that htrA is encoded in an operon with two subsequent genes, HP1020 and HP1021. Genetic mutagenesis and complementation studies revealed that HP1020 and HP1021, but not htrA, can be mutated. In addition, we demonstrate that suppression of HtrA proteolytic activity with a newly developed inhibitor is sufficient to effectively kill H.pylori, but not other bacteria. We show that HelicobacterhtrA is an essential bifunctional gene with crucial intracellular and extracellular functions. Thus, we describe here the first microbe in which htrA is an indispensable gene, a situation unique in the bacterial kingdom. HtrA can therefore be considered a promising new target for anti-bacterial therapy.
Created from Fastlane, Scopus look-up

Classification of Helicobacter pylori Virulence Factors: Is CagA a Toxin or Not? - Knorr, Jakob; Ricci, Vittorio; Hatakeyama, Masanori; Backert, Steffen (Trends in Microbiology, 2019)
Since its discovery, Helicobacter pylori has been identified as the causative agent of various gastric diseases. H. pylori produces myriads of disease-associated virulence factors. These bacterial determinants can be distinguished as cell-binding factors, immunoregulatory components, survival factors, toxins, and effector proteins. For most of these factors there is consensus about their classification. However, there is a strong dispute in the literature as to whether one of the best-studied factors, CagA, represents a toxin or not. CagA displays unique functions that are clearly different from conventional toxins, and CagA counteracts the activities of an established H. pylori toxin, VacA. Canonical toxins commonly have specific (and narrow) targets, can act even in the absence of the bacterial cell, and elicit acute damage to host cells. However, there is still no agreement on the classification of CagA. Here we discuss whether CagA acts as a toxin, and propose a classification consensus for CagA.
CRIS-Team Scopus Importer:2019-05-28
Keywords: CagA; gastric cancer; Helicobacter pylori; T4SS; toxin; type IV secretion; VacA

Clinical Presentations and Pathogenicity Mechanisms of Bacterial Foodborne Infections - Tegtmeyer, Nicole; Rohde, Manfred; Backert, Steffen (Microbial Food Safety, 2011)
Foodborne infections are estimated to affect one in four Americans each year. Most of these infections are caused by the Norwalk-like viruses, but Campylobacter and nontyphoidal Salmonella species together account for about one fourth of cases of illness in which a pathogen can be detected. Less common bacterial infections, such as with Listeria monocytogenes and the Shiga toxin-producing Escherichia coli, cause fewer infections but are also important because of their severe complications and high mortality rate. This chapter describes the clinical presentations, molecular determinants, and pathogenicity mechanisms of very important bacterial foodborne pathogens as well as the associated diseases in humans.<br
Keywords: Listeria Monocytogenes; Effector Protein; Thrombotic Thrombocytopenic Purpura; Watery Diarrhea; Foodborne Pathogen

Composition, structure and function of the Helicobacter pylori cag pathogenicity island encoded type IV secretion system - Backert, Steffen; Tegtmeyer, Nicole; Fischer, Wolfgang (Future Microbiology, 2015)
Many Gram-negative pathogens harbor type IV secretion systems (T4SS) that translocate bacterial virulence factors into host cells to hijack cellular processes. The pathology of the gastric pathogen Helicobacter pylori strongly depends on a T4SS encoded by the cag pathogenicity island. This T4SS forms a needle-like pilus, and its assembly is accomplished by multiple protein-protein interactions and various pilus-associated factors that bind to integrins followed by delivery of the CagA oncoprotein into gastric epithelial cells. Recent studies revealed the crystal structures of six T4SS proteins and pilus formation is modulated by iron and zinc availability. All these T4SS interactions are crucial for deregulating host signaling events and disease progression. New developments in T4SS functions and their importance for pathogenesis are discussed.
Created from Fastlane, Scopus look-up
Keywords: c-Met; CagA; CagL; cagPAI; CagY; cortactin; EGF receptor; gastric disease; GTPase; Helicobacter pylori; integrin; MARK2/PAR1b kinase; signaling; T4SS; type IV secretion; tyrosine kinases; VirB proteins; β-catenin

Conjugative plasmid DNA transfer in Helicobacter pylori mediated by chromosomally encoded relaxase and TraG-like proteins - Backert, Steffen; Kwok, Terry; König, Wolfgang (Microbiology, 2005)
One of the striking characteristics of Helicobacter pylori is the extensive genetic diversity among clinical isolates. This diversity has been attributed to an elevated mutation rate, impaired DNA repair, DNA transfer and frequent recombination events. Plasmids have also been identified in H. pylori but it remained unknown whether conjugation can contribute to DNA transfer between clinical isolates. To examine whether H. pylori possesses intrinsic capability for conjugative plasmid transfer, shuttle vectors were introduced into H. pylori containing an oriT sequence of the conjugative IncPα plasmid RP4 but no mobilization (mob) genes. It was shown that these vectors could stably replicate and be mobilized among clinical H. pylori strains. It was also demonstrated that traG and relaxase (rlx) homologues carried on the H. pylori chromosome were important for plasmid transfer. Primer extension studies and mutagenesis further confirmed that the relaxase homologue rlx1 in H. pylori encodes a functional enzyme capable of acting on the RP4 oriT. Furthermore, the findings of this study indicate that traG and rlx1 act independently of the previously described type IV secretion systems, including that encoded by the cag pathogenicity island and the comB transformation apparatus, in mediating conjugative plasmid DNA transfer between H. pylori strains. © 2005 SGM.
Created from Fastlane, Scopus look-up

Conjugative transfer of chromosomally encoded antibiotic resistance from Helicobacter pylori to Campylobacter jejuni - Oyarzabal, Omar A.; Rad, Roland; Backert, Steffen (Journal of Clinical Microbiology, 2007)
Many strains of Helicobacter pylori are naturally competent for transformation and able to transfer chromosomal DNA among different isolates using a conjugation-like mechanism. In this study, we sought to determine whether H. pylori can transfer DNA into Campylobacter jejuni, a closely related species of the Campylobacterales group. To monitor the transfer, a chromosomally encoded streptomycin resistance cassette prearranged by a specific mutation in the rpsL gene of H. pylori was used. Mating of the bacteria on plates or in liquid broth medium produced C. jejuni progeny containing the streptomycin marker. DNA transfer was unidirectional, from H. pylori to C. jejuni, and the progeny were genetically identical to C. jejuni recipient strains. DNase I treatment reduced but did not eliminate transfer, and DNase I-treated cell supernatants did not transform, ruling out phage transduction. Recombinants also did not occur when the mating bacteria were separated by a membrane, suggesting that DNA transfer requires cell-to-cell contact. Transfer of the streptomycin marker was independent of the H. pylori comB transformation system, the cag pathogenicity island, and another type IV secretion system called tfs3. These findings indicated that a DNase I-resistant, conjugation-like mechanism may contribute to horizontal DNA transfer between different members of the Campylobacteriales group. The significance of this DNA uptake by C. jejuni in the context of acquiring antibiotic resistance is discussed. Copyright © 2007, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Control of campylobacter spp. in commercial poultry production - Oyarzabal, Omar A.; Backert, Steffen (Campylobacter Spp. and Related Organisms in Poultry: Pathogen-Host Interactions, Diagnosis and Epidemiology, 2016)
Campylobacteriosis continues to be an important disease worldwide. The most important risk factors associated with the transmission of Campylobacter spp. are the consumption of raw milk, undercooked or contaminated chicken, and raw oysters. The number of campylobacteriosis cases associated to raw milk and oysters could be greatly reduced by applying temperature treatments to the product. Although cooking is also the best control measurement for the transmission of Campylobacter spp. from chicken meat, the high contamination found in some chicken samples required a more comprehensive approach to reduce the appearance of the pathogen in the final product. This chapter reviews the intervention strategies that have been practically applied by the food industry to reduce the contamination of poultry products with Campylobacter spp. The discussion focuses on on-farm interventions and the interventions applied in processing plants. In the USA, chemical interventions have been used for approximately 20 years and have found a commercial niche in the poultry industry.
Created from Fastlane, Scopus look-up
Keywords: Biosecurity; Campylobacter; Chemical interventions; Control; Farm interventions; Plant interventions

Correction: Macroevolution of gastric Helicobacter species unveils interspecies admixture and time of divergence (The ISME Journal, (2018), 12, 10, (2518-2531), 10.1038/s41396-018-0199-5) - Smet, Annemieke; Yahara, Koji; Rossi, Mirko; Tay, Alfred; Backert, Steffen; Enßer, Armin; Fox, James G.; Flahou, Bram; Ducatelle, Richard; Haesebrouck, Freddy; Corander, Jukka (Isme Journal, 2019)
The original version of this Article contained an error in the presentation of the author Armin Ensser, which was incorrectly given as Ensser Armin. The correct author list is as follows: Annemieke Smet, Koji Yahara, Mirko Rossi, Alfred Tay, Steffen Backert, Armin Ensser, James G. Fox, Bram Flahou, Richard Ducatelle, Freddy Haesebrouck, Jukka Corander The authors apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2019-05-28

Cortactin: A major cellular target of the gastric carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Backert, Steffen; Tegtmeyer, Nicole (Cancers, 2020)
Cortactin is an actin binding protein and actin nucleation promoting factor regulating cytoskeletal rearrangements in nearly all eukaryotic cell types. From this perspective, cortactin poses an attractive target for pathogens to manipulate a given host cell to their own benefit. One of the pathogens following this strategy is Helicobacter pylori, which can cause a variety of gastric diseases and has been shown to be the major risk factor for the onset of gastric cancer. During infection of gastric epithelial cells, H. pylori hijacks the cellular kinase signaling pathways, leading to the disruption of key cell functions. Specifically, by overruling the phosphorylation status of cortactin, H. pylori alternates the activity of molecular interaction partners of this important protein, thereby manipulating the performance of actin-cytoskeletal rearrangements and cell movement. In addition, H. pylori utilizes a unique mechanism to activate focal adhesion kinase, which subsequently prevents host epithelial cells from extensive lifting from the extracellular matrix in order to achieve chronic infection in the human stomach.
CRIS-Team Scopus Importer:2020-02-07
Keywords: Abl; CagA; CagPAI; FAK; Helicobacter pylori; SHP2; Signaling; Src; T4SS; Type IV secretion; Tyrosine kinases

Cortactin: A major cellular target of viral, protozoal, and fungal pathogens - Sharafutdinov, Irshad; Friedrich, Barbara; Rottner, Klemens; Backert, Steffen; Tegtmeyer, Nicole (Molecular Microbiology, 2024)
Many viral, protozoal, and fungal pathogens represent major human and animal health problems due to their great potential of causing infectious diseases. Research on these pathogens has contributed substantially to our current understanding of both microbial virulence determinants and host key factors during infection. Countless studies have also shed light on the molecular mechanisms of host–pathogen interactions that are employed by these microbes. For example, actin cytoskeletal dynamics play critical roles in effective adhesion, host cell entry, and intracellular movements of intruding pathogens. Cortactin is an eminent host cell protein that stimulates actin polymerization and signal transduction, and recently emerged as fundamental player during host–pathogen crosstalk. Here we review the important role of cortactin as major target for various prominent viral, protozoal and fungal pathogens in humans, and its role in human disease development and cancer progression. Most if not all of these important classes of pathogens have been reported to hijack cortactin during infection through mediating up- or downregulation of cortactin mRNA and protein expression as well as signaling. In particular, pathogen-induced changes in tyrosine and serine phosphorylation status of cortactin at its major phospho-sites (Y-421, Y-470, Y-486, S-113, S-298, S-405, and S-418) are addressed. As has been reported for various Gram-negative and Gram-positive bacteria, many pathogenic viruses, protozoa, and fungi also control these regulatory phospho-sites, for example, by activating kinases such as Src, PAK, ERK1/2, and PKD, which are known to phosphorylate cortactin. In addition, the recruitment of cortactin and its interaction partners, like the Arp2/3 complex and F-actin, to the contact sites between pathogens and host cells is highlighted, as this plays an important role in the infection process and internalization of several pathogens. However, there are also other ways in which the pathogens can exploit the function of cortactin for their needs, as the cortactin-mediated regulation of cellular processes is complex and involves numerous different interaction partners. Here, the current state of knowledge is summarized.
CRIS-Team Scopus Importer:2024-06-21
Keywords: cortactin; cytoskeleton; pathogenesis; signaling; virulence

Cortactin: An Achilles' heel of the actin cytoskeleton targeted by pathogens - Selbach, Matthias; Backert, Steffen (Trends in Microbiology, 2005)
Cortactin is an actin-binding protein and a central regulator of the actin cytoskeleton. Importantly, cortactin is also a common target exploited by microbes during infection. Its involvement in disease development is exemplified by a variety of pathogenic processes, such as pedestal formation [enteropathogenic and enterohaemorrhagic Escherichia coli (EPEC and EHEC)], invasion (Shigella, Neisseria, Rickettsia, Chlamydia, Staphylococcus and Cryptosporidium), actin-based motility (Listeria, Shigella and vaccinia virus) and cell scattering (Helicobacter). Recent progress turns our attention to how cortactin function can be regulated by serine and tyrosine phosphorylation. This has an important impact on how pathogens abuse cortactin to modulate the architecture of the host actin cytoskeleton. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Cortactin: A universal host cytoskeletal target of Gram-negative and Gram-positive bacterial pathogens - Sharafutdinov, Irshad; Knorr, Jakob; Rottner, Klemens; Backert, Steffen; Tegtmeyer, Nicole (Molecular Microbiology, 2022)
Pathogenic bacteria possess a great potential of causing infectious diseases and represent a serious threat to human and animal health. Understanding the molecular basis of infection development can provide new valuable strategies for disease prevention and better control. In host-pathogen interactions, actin-cytoskeletal dynamics play a crucial role in the successful adherence, invasion, and intracellular motility of many intruding microbial pathogens. Cortactin, a major cellular factor that promotes actin polymerization and other functions, appears as a central regulator of host-pathogen interactions and different human diseases including cancer development. Various important microbes have been reported to hijack cortactin signaling during infection. The primary regulation of cortactin appears to proceed via serine and/or tyrosine phosphorylation events by upstream kinases, acetylation, and interaction with various other host proteins, including the Arp2/3 complex, filamentous actin, the actin nucleation promoting factor N-WASP, focal adhesion kinase FAK, the large GTPase dynamin-2, the guanine nucleotide exchange factor Vav2, and the actin-stabilizing protein CD2AP. Given that many signaling factors can affect cortactin activities, several microbes target certain unique pathways, while also sharing some common features. Here we review our current knowledge of the hallmarks of cortactin as a major target for eminent Gram-negative and Gram-positive bacterial pathogens in humans.
CRIS-Team Scopus Importer:2022-12-23
Keywords: Cortactin; Cytoskeleton; Pathogenesis; Signaling; Virulence

Cortactin-dependent control of Par1b-regulated epithelial cell polarity in Helicobacter infection - Sharafutdinov, Irshad; Harrer, Aileen; Müsken, Mathias; Rottner, Klemens; Sticht, Heinrich; Täger, Christian; Naumann, Michael; Tegtmeyer, Nicole; Backert, Steffen (Cell Insight, 2024)
Cell polarity is crucial for gastric mucosal barrier integrity and mainly regulated by polarity-regulating kinase partitioning-defective 1b (Par1b). During infection, the carcinogen Helicobacter pylori hijacks Par1b via the bacterial oncoprotein CagA leading to loss of cell polarity, but the precise molecular mechanism is not fully clear. Here we discovered a novel function of the actin-binding protein cortactin in regulating Par1b, which forms a complex with cortactin and the tight junction protein zona occludens-1 (ZO-1). We found that serine phosphorylation at S405/418 and the SH3 domain of cortactin are important for its interaction with both Par1b and ZO-1. Cortactin knockout cells displayed disturbed Par1b cellular localization and exhibited morphological abnormalities that largely compromised transepithelial electrical resistance, epithelial cell polarity, and apical microvilli. H. pylori infection promoted cortactin/Par1b/ZO-1 abnormal interactions in the tight junctions in a CagA-dependent manner. Infection of human gastric organoid-derived mucosoids supported these observations. We therefore hypothesize that CagA disrupts gastric epithelial cell polarity by hijacking cortactin, and thus Par1b and ZO-1, suggesting a new signaling pathway for the development of gastric cancer by Helicobacter.
CRIS-Team Scopus Importer:2024-05-03
Keywords: ASPP2; CagA; Cell polarity; Cortactin; Par1b; T4SS; Tight junction; ZO-1

Cortactin is required for efficient fak, src and abl tyrosine kinase activation and phosphorylation of helicobacter pylori caga - Knorr, Jakob; Sharafutdinov, Irshad; Fiedler, Florian; Soltan Esmaeili, Delara; Rohde, Manfred; Rottner, Klemens; Backert, Steffen; Tegtmeyer, Nicole (International Journal of Molecular Sciences, 2021)
Cortactin is a well‐known regulatory protein of the host actin cytoskeleton and represents an attractive target of microbial pathogens like Helicobacter pylori. H. pylori manipulates cortactin’s phosphorylation status by type‐IV secretion‐dependent injection of its virulence protein CagA. Multiple host tyrosine kinases, like FAK, Src, and Abl, are activated during infection, but the pathway(s) involved is (are) not yet fully established. Among them, Src and Abl target CagA and stimulate tyrosine phosphorylation of the latter at its EPIYA‐motifs. To investigate the role of cortactin in more detail, we generated a CRISPR/Cas9 knockout of cortactin in AGS gastric epithelial cells. Surprisingly, we found that FAK, Src, and Abl kinase activities were dramatically downregulated associated with widely diminished CagA phosphorylation in cortactin knockout cells compared to the parental control. Together, we report here a yet unrecognized cortactin‐dependent signaling pathway involving FAK, Src, and Abl activation, and controlling efficient phosphorylation of injected CagA during infection. Thus, the cortactin status could serve as a potential new biomarker of gastric cancer development.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Abl; Cancer; Cortactin; FAK; Helicobacter; Pathogenesis; Pathogenicity island; Signaling; Src; Virulence

Cortactin promotes effective ags cell scattering by helicobacter pylori caga, but not cellular vacuolization and apoptosis induced by the vacuolating cytotoxin vaca - Sharafutdinov, Irshad; Knorr, Jakob; Soltan Esmaeili, Delara; Backert, Steffen; Tegtmeyer-Backert, Nicole (Pathogens, 2022)
Cortactin is an actin-binding protein and actin-nucleation promoting factor regulating cytoskeletal rearrangements in eukaryotes. Helicobacter pylori is a gastric pathogen that exploits cortactin to its own benefit. During infection of gastric epithelial cells, H. pylori hijacks multiple cellular signaling pathways, leading to the disruption of key cell functions. Two bacterial virulence factors play important roles in this scenario, the vacuolating cytotoxin VacA and the translocated effector protein CagA of the cag type IV secretion system (T4SS). Specifically, by overruling the phosphorylation status of cortactin, H. pylori alternates the activity of molecular interaction partners of this important protein, thereby manipulating the performance of cytoskeletal rearrangements, endosomal trafficking and cell movement. Based on shRNA knockdown and other studies, it was previously reported that VacA utilizes cortactin for its cellular uptake, intracellular travel and induction of apoptosis by a mitochondria-dependent mechanism, while CagA induces cell scattering, motility and elongation. To investigate the role of cortactin in these phenotypes in more detail, we produced a complete knockout mutant of cortactin in the gastric adenocarcinoma cell line AGS by CRISPR-Cas9. These cells were infected with H. pylori wild-type or various isogenic mutant strains. Unexpectedly, cortactin deficiency did not prevent the uptake and formation of VacA-dependent vacuoles, nor the induction of apoptosis by internalized VacA, while the induction of T4SS-and CagA-dependent AGS cell movement and elongation were strongly reduced. Thus, we provide evidence that cortactin is required for the function of internalized CagA, but not VacA.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Annexin V; Apoptosis; CagA; CagE; Caspase-3; Cell scattering; Cortactin; FlaA; H. pylori; T4SS; VacA

c-Src and c-Abl kinases control hierarchic phosphorylation and function of the CagA effector protein in Western and East Asian Helicobacter pylori strains - Mueller, Doreen; Tegtmeyer, Nicole; Brandt, Sabine; Yamaoka, Yoshio; De Poire, Eimear; Sgouras, Dionyssios; Wessler, Silja; Torres, Javier; Smolka, Adam; Backert, Steffen (Journal of Clinical Investigation, 2012)
Many bacterial pathogens inject into host cells effector proteins that are substrates for host tyrosine kinases such as Src and Abl family kinases. Phosphorylated effectors eventually subvert host cell signaling, aiding disease development. In the case of the gastric pathogen Helicobacter pylori, which is a major risk factor for the development of gastric cancer, the only known effector protein injected into host cells is the oncoprotein CagA. Here, we followed the hierarchic tyrosine phosphorylation of H. pylori CagA as a model system to study early effector phosphorylation processes. Translocated CagA is phosphorylated on Glu-Pro-Ile-Tyr-Ala (EPIYA) motifs EPIYA-A, EPIYA-B, and EPIYA-C in Western strains of H. pylori and EPIYA-A, EPIYA-B, and EPIYA-D in East Asian strains. We found that c-Src only phosphorylated EPIYA-C and EPIYA-D, whereas c-Abl phosphorylated EPIYA-A, EPIYA-B, EPIYA-C, and EPIYA-D. Further analysis revealed that CagA molecules were phosphorylated on 1 or 2 EPIYA motifs, but never simultaneously on 3 motifs. Furthermore, none of the phosphorylated EPIYA motifs alone was sufficient for inducing AGS cell scattering and elongation. The preferred combination of phosphorylated EPIYA motifs in Western strains was EPIYA-A and EPIYA-C, either across 2 CagA molecules or simultaneously on 1. Our study thus identifies a tightly regulated hierarchic phosphorylation model for CagA starting at EPIYA-C/D, followed by phosphorylation of EPIYA-A or EPIYA-B. These results provide insight for clinical H. pylori typing and clarify the role of phosphorylated bacterial effector proteins in pathogenesis.
Created from Fastlane, Scopus look-up

Cultivation and molecular characterization of viable Helicobacter pylori from the root canal of 170 deciduous teeth of children - Elger, Wieland; Tegtmeyer, Nicole; Rohde, Manfred; Linz, Bodo; Hirsch, Christian; Backert, Steffen (Cell Communication and Signaling, 2024)
Background: Helicobacter pylori is a persistent pathogen in the human stomach. However, the proposed transmission route via the oral cavity is not understood and under intense debate. While dozens of studies have shown by PCR that H. pylori DNA is frequently present in the oral cavity, data on the growth and characterization of viable H. pylori from this compartment are very scarce, and it is unclear whether the bacteria can survive in the oral cavity for longer time periods or even colonize it. Methods: Selective growth methods, scanning electron microscopy, urease assay, Western blotting, PCR, and gene sequencing were applied to identify and examine viable H. pylori in decayed milk teeth. Results: Here, we studied viable H. pylori in the plaque and root canals of 170 endodontically infected deciduous teeth that were extracted from 54 children. While H. pylori DNA was detected in several plaque and many root canal samples by PCR, live bacteria could only be cultivated from 28 root canals, but not from plaque. These 28 isolates have been identified as H. pylori by PCR and sequencing of vacA, cagA and htrA genes, phylogenetic analyses, protein expression of major H. pylori virulence factors, and by signal transduction events during infection of human cell lines. Conclusions: Thus, the microaerobic environment in the root canals of endodontically infected teeth may represent a protected and transient reservoir for live H. pylori, especially in individuals with poor dental hygiene, which could serve as a potential source for re-infection of the stomach after antibiotic therapy or for transmission to other individuals.
CRIS-Team Scopus Importer:2025-02-04
Keywords: CagA; Endodontics; Helicobacter pylori; HtrA; Root canal; VacA

Cyclic RGD peptides interfere with binding of the Helicobacter pylori protein CagL to integrins αvβ3 and α5β1 - Conradi, Jens; Huber, Sylwia; Gaus, Katharina; Mertink, Felix; Royo Gracia, Soledad; Strijowski, Ulf; Backert, Steffen; Sewald, Norbert (Amino Acids, 2012)
The human pathogen Helicobacter pylori that may cause different gastric diseases exploits integrins for infection of gastric cells. The H. pylori protein CagL present on the outer region of the type IV secretion pilus contains an RGD sequence (-Arg-Gly-Asp-) that enables binding to cells presenting integrins α5β1 and αVβ 3. This interaction can be inhibited with conformationally designed cyclic RGD peptides derived from the CagL epitope -Ala-Leu-Arg-Gly-Asp-Leu-Ala-. The inhibition of the CagL-αVβ3 interaction by different RGD peptides strongly suggests the importance of the RGD motif for CagL binding. CagL point mutants (RAD, RGA) show decreased affinity to integrin αVβ3. Furthermore, structure-activity relationship studies with cyclic RGD peptides in a spatial screening approach show the distinct influence of the three-dimensional arrangement of RGD motif on the ability to interfere with this interaction. Resulting from these studies, similar structural requirements for the CagL epitope as previously suggested for other ligands of integrin αVβ3 are proposed. © 2011 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: α; CagL; Integrins; RGD peptides; SAR studies

Detection of Fusobacterium nucleatum in Patients with Colitis-Associated Colorectal Cancer - Dregelies, Theresa; Haumaier, Franziska; Sterlacci, William; Backert, Steffen; Vieth, Michael (Current Microbiology, 2023)
Fusobacterium nucleatum is supposed to play a critical role in the development of colorectal cancer. The species has also been associated with ulcerative colitis (UC) that can progress into colorectal cancer, however, the involvement of bacteria in this process remains unclear. We analysed 177 colon biopsies obtained from patients during screening, including 20 healthy controls, 56 UC cases and 69 cases at different stages of progression to colitis-associated cancer (CAC); 32 samples of sporadic colorectal carcinoma (sCRC) were also included. The presence of F. nucleatum was detected by quantitative real-time PCR (qPCR). Our data show an association between the presence of the bacteria and the progression of carcinogenesis in UC patients. In 39.5% of CAC samples F. nucleatum was detected, compared to only 1.8% in UC cases. The bacteria were detected in 6.3% of samples with initial neoplastic transformation, so-called low-grade dysplasia (LGD), whereas high-grade dysplasia (HGD) resulted in 33.3% of samples positive for F. nucleatum. The fraction of F. nucleatum-positive samples from sCRC cases was 56.3%, which was not significantly different to the CAC group. We conclude that F. nucleatum is associated with the occurrence and progression of colon carcinogenesis, rather than with UC itself.
CRIS-Team Scopus Importer:2023-08-11

Differential Expression of Interleukin 1β during Helicobacter pylori Infection of Toll-like Receptor 2 (TLR2)- and TLR10-Expressing HEK293 Cell Lines - Suneesh Kumar, Pachathundikandi; Backert, Steffen (Journal of Infectious Diseases, 2016)
Created from Fastlane, Scopus look-up

Differential gene expression in colon carcinoma cells and tissues detected with a cDNA array - Backert, Steffen; Gelos, Marcos; Kobalz, Ursula; Hanski, Marie Luise; Böhm, Christian; Mann, Benno; Lövin, Nicole; Gratchev, Alexei; Mansmann, Ulrich; Moyer, Mary Pat; Riecken, Ernst-Otto; Hanski, Christoph (International Journal of Cancer, 1999)
Expression of selected genes coding for proteins with defined cellular functions was analysed in human cell lines derived from normal colonic mucosa, non-mucinous colonic carcinomas and mucinous colonic carcinomas. Altered expression of 10 genes in colon carcinoma cells was found by using a cDNA array; 6 of these alterations (60%) were confirmed by Northern blotting or semi-quantitative reverse transcription-polymerase chain reaction (RT- PCR). Among these 6 genes, 3 transcription factors as well as the topoisomerase II α and the mitosis inhibitor WEEIHu gene were significantly suppressed in the tumour cell lines. In addition, the gene coding for the cell cycle inhibitor p21 was overexpressed only in cell lines derived from mucinous carcinomas. The significant suppression of the kinase WEEIHu gene in carcinoma cells of both phenotypes and the tendency of the mucinous phenotype to overexpress p21 protein were confirmed in human colon carcinoma tissues. Our data show that the cDNA array method permits a correct identification of changes in gene expression with a relatively high accuracy. The different expression of the p21 gene in the non-mucinous and mucinous carcinoma cells supports the hypothesis that these phenotypes may develop along different genetic pathways. The detection of WEEIHu gene suppression in colon carcinoma cells and tissues suggests its potential role in tumourigenesis.
Created from Fastlane, Scopus look-up

Differential phosphoproteome profiling reveals a functional role for VASP in Helicobacter pylori-induced cytoskeleton turnover in gastric epithelial cells - Knauer, Olivia; Binai, Nadine A.; Carra, Gert; Beckhaus, Tobias; Hanschmann, Kay-Martin; Renne, Thomas; Backert, Steffen; Karas, Michael; Wessler, Silja (Cellular Microbiology, 2008)
Infection with Helicobacter pylori induces various gastric diseases, including ulceration, gastritis and neoplasia. As H. pylori-induced cellular mechanisms leading to these disease states are widely unclear, we analysed the phosphoproteome of H. pylori-infected gastric epithelial cells. Phosphoproteins from infected cells were enriched using affinity columns and analysed by two-dimensional gel electrophoresis and mass spectrometry. Eleven novel phosphoproteins that showed differentially regulated phosphorylation levels during H. pylori infection were identified. Interestingly, the identified proteins were actin-binding, transport and folding, RNA/DNA-binding or cancer-associated proteins. We analysed functions of one identified H. pylori-regulated candidate, the vasodilator-stimulated phosphoprotein (VASP). H. pylori induced VASP phosphorylation at residues Ser157, Ser239 and Thr278, which was enhanced by the bacterial oncogene cytotoxin-associated gene A. Overexpression of a phosphorylation-resistant VASP mutant efficiently blocked host cell elongation. We identified cGMP-dependent protein kinase G-mediated Ser239 and Thr278 phosphorylation of VASP as a crucial event in H. pylori-dependent host cell elongation. These results suggest that phosphorylated VASP could be a novel target candidate for therapeutic intervention in H. pylori-related gastric diseases. © 2008 The Authors Journal compilation © 2008 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Differentiation of Gastric Helicobacter Species Using MALDI-TOF Mass Spectrometry - Berlamont, Helena; De Witte, Chloe; De Bruyckere, Sofie; Fox, James G.; Backert, Steffen; Smet, Annemieke; Boyen, Filip; Haesebrouck, Freddy (Pathogens, 2021)
Gastric helicobacters (Helicobacter (H.) pylori and non-H. pylori Helicobacter species (NHPHs)) colonize the stomach of humans and/or animals. Helicobacter species identification is essential since many of them are recognized as human and/or animal pathogens. Currently, Helicobacter species can only be differentiated using molecular methods. Differentiation between NHPHs using MALDI-TOF MS has not been described before, probably because these species are poorly represented in current MALDI-TOF MS databases. Therefore, we identified 93 gastric Helicobacter isolates of 10 different Helicobacter species using MALDI-TOF MS in order to establish a more elaborate Helicobacter reference database. While the MALDI Biotyper database was not able to correctly identify any of the isolates, the in-house database correctly identified all individual mass spectra and resulted in 82% correct species identification based on the two highest log score matches (with log scores >= 2). In addition, a dendrogram was constructed using all newly created main spectrum profiles. Nine main clusters were formed, with some phylogenetically closely related Helicobacter species clustering closely together and well-defined subclusters being observed in specific species. Current results suggest that MALDI-TOF MS allows rapid differentiation between gastric Helicobacter species, provided that an extensive database is at hand and variation due to growth conditions and agar-medium-related peaks are taken into account.
CRIS-Team WoS Importer:2021-04-09

Different roles of integrin-β1 and integrin-αv for type IV secretion of CagA versus cell elongation phenotype and cell lifting by Helicobacter pylori - Tegtmeyer, Nicole; Backert, Steffen (PLoS Pathogens, 2020)
CRIS-Team Scopus Importer:2020-08-07

Distinct roles of secreted HtrA proteases from gram-negative pathogens in cleaving the junctional protein and tumor suppressor E-cadherin - Hoy, Benjamin; Geppert, Tim; Boehm, Manja; Reisen, Felix; Plattner, Patrick; Gadermaier, Gabriele; Sewald, Norbert; Ferreira, Fatima; Briza, Peter; Schneider, Gisbert; Backert, Steffen; Wessler, Silja (Journal of Biological Chemistry, 2012)
The periplasmic chaperone and serine protease HtrA is important for bacterial stress responses and protein quality control. Recently, we discovered that HtrA from Helicobacter pylori is secreted and cleaves E-cadherin to disrupt the epithelial barrier, but it remained unknown whether this maybe a general virulence mechanism. Here, we show that important other pathogens including enteropathogenic Escherichia coli, Shigella flexneri, and Campylobacter jejuni, but not Neisseria gonorrhoeae, cleaved E-cadherin on host cells. HtrA deletion in C. jejuni led to severe defects in E-cadherin cleavage, loss of cell adherence, paracellular transmigration, and basolateral invasion. Computational modeling of HtrAs revealed a conserved pocket in the active center exhibiting pronounced proteolytic activity. Differential E-cadherin cleavage was determined by an alanine-to-glutamine exchange in the active center of neisserial HtrA. These data suggest that HtrA-mediated E-cadherin cleavage is a prevalent pathogenic mechanism of multiple Gram-negative bacteria representing an attractive novel target for therapeutic intervention to combat bacterial infections. © 2012 by The American Society for Biochemistry and Molecular Biology, Inc.
Created from Fastlane, Scopus look-up

DNA Binding Specificity of the Replication Initiator Protein, DnaA from Helicobacter pylori - Zawilak, Anna; Durrant, Marcus C.; Jakimowicz, Piotr; Backert, Steffen; Zakrzewska-Czerwińska, Jolanta (Journal of Molecular Biology, 2003)
The key protein in the initiation of Helicobacter pylori chromosome replication, DnaA, has been characterized. The amount of the DnaA protein was estimated to be approximately 3000 molecules per single cell; a large part of the protein was found in the inner membrane. The H.pylori DnaA protein has been analysed using in vitro (gel retardation assay and surface plasmon resonance (SPR)) as well as in silico (comparative computer modeling) studies. DnaA binds a single DnaA box as a monomer, while binding to the fragment containing several DnaA box motifs, the oriC region, leads to the formation of high molecular mass nucleoprotein complexes. In comparison with the Escherichia coli DnaA, the H.pylori DnaA protein exhibits lower DNA-binding specificity; however, it prefers oriC over non-box DNA fragments. As determined by gel retardation techniques, the H.pylori DnaA binds with a moderate level of affinity to its origin of replication (4nM). Comparative computer modelling showed that there are nine residues within the binding domain which are possible determinants of the reduced H.pylori DnaA specificity. Of these, the most interesting is probably the triad PTL; all three residues show significant divergence from the consensus, and Thr398 is the most divergent residue of all. © 2003 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Helicobacter pylori; Initiator protein DnaA

DNA transfer in the gastric pathogen Helicobacter pylori - Fernández González, Esther; Backert, Steffen (Journal of Gastroenterology, 2014)
The gastric pathogen Helicobacter pylori is one of the most genetically diverse bacteria. Recombination and DNA transfer contribute to its genetic variability and enhance host adaptation. Among the strategies described to increase genetic diversity in bacteria, DNA transfer by conjugation is one of the best characterized. Using this mechanism, a fragment of DNA from a donor cell can be transferred to a recipient, always mediated by a conjugative nucleoprotein complex, which is evolutionarily related to type IV secretion systems (T4SSs). Interestingly, the H. pylori chromosomes can encode up to four T4SSs, including the cagPAI, comB, tfs3, and tfs4 genes, some of which are known to promote chronic H. pylori infection. The T4SS encoded by the cagPAI mediates the injection of the effector protein CagA and proinflammatory signaling, and the comB system is involved in DNA uptake from the environment. However, the role of tfs3 and tfs4 is not yet clear. The presence of a functional XerD tyrosine recombinase and 5′AAAGAATG-3′ border sequences as well as two putative conjugative relaxases (Rlx1 and Rlx2), a coupling protein (TraG), and a chromosomal region carrying a putative origin of transfer (oriT) suggest the existence of a DNA transfer apparatus in tfs4. Moreover, a conjugation-like DNA transfer mechanism in H. pylori has already been described in vitro, but whether this occurs in vivo is still unknown. Some extrachromosomal plasmids and phages are also present in various H. pylori strains. Genetic exchange among plasmids and chromosomes, and involved DNA mobilization events, could explain part of H. pylori's genetic diversity. Here, we review our knowledge about the possible DNA transfer mechanisms in H. pylori and its implications in bacterial adaptation to the host environment. © 2014 Springer.
Created from Fastlane, Scopus look-up
Keywords: ADR; Cag; Competence; Conjugation; DNA transfer; Genetic variability; Host adaptation; Origin of transfer; Pathogenicity island; Phage transduction; Pilus; Plasmid mobilization; Recombination; Relaxase; Type IV secretion system; Tyrosine recombinase; VirB/D; Virulence

Dual infection system identifies a crucial role for PKA-mediated serine phosphorylation of the EPEC-Tir-injected effector protein in regulating Rac1 function - Brandt, Sabine; Kenny, Brendan; Rohde, Manfred; Martinez-Quiles, Narcisa; Backert, Steffen (Cellular Microbiology, 2009)
Many Gram-negative pathogenic bacteria possess type-III or type-IV secretion systems to inject 'effector' proteins directly into host cells to modulate cellular processes in their favour. A common target is the actin-cytoskeleton linked to the delivery of a single (CagA) effector by Helicobacter pylori and multiple effectors by enteropathogenic Escherichia coli (EPEC) respectively. Here we report co-infection as a powerful strategy for defining effector protein function and mechanisms by which they modulate cellular responses. This is exemplified by our finding that EPEC inhibits H. pylori-induced AGS cell elongation, a disease-related event linked to Rac1 activation. While this inhibitory process is dependent on the translocated Intimin receptor, Tir, and the outer-membrane protein, Intimin, it unexpectedly revealed evidence for Tir signalling independent of Intimin interaction and tyrosine phosphorylation of Tir. Furthermore, the work defined a long awaited role for protein kinase A (PKA)-mediated phosphorylation of Tir at serine-434 and serine-463. Our data are consistent with a model whereby EPEC activates PKA for Tir phosphorylation. Activated PKA then phosphorylates Rac1 at serine-71 associated with reduced GTP-load and inhibited cell elongation. Thus, the co-infection approach is a powerful strategy for defining novel effector function with important implications for characterizing mechanisms and regulatory signalling pathways in bacterial pathogenesis. © 2009 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Early and late genome-wide gastric epithelial transcriptome response during infection with the human carcinogen Helicobacter pylori - Sharafutdinov, Irshad; Ekici, Arif Bülent; Vieth, Michael; Backert, Steffen; Linz, Bodo (Cell Insight, 2022)
Infection of the stomach by Helicobacter pylori is a major risk factor for the development of gastric cancer. Colonization of the gastric epithelium leads to the activation of multiple disease-related signaling pathways. Serine protease HtrA represents an important secreted virulence factor that mediates cleavage of cellular junctions. However, its potential role in nuclear responses is unknown. Here, we performed a genome-wide RNA-seq analysis of polarized gastric epithelial cells infected by wild-type (wt) and ΔhtrA mutant bacteria. Fluorescence microscopy showed that H. pylori wt, but not ΔhtrA bacteria, preferably localized at cellular junctions. Our results pinpointed early (2 h) and late (6 h) transcriptional responses, with most differentially expressed genes at 6 h post infection. The transcriptomes revealed HtrA-dependent targeting of genes associated with inflammation and apoptosis (e.g. IL8, ZFP36, TNF). Accordingly, infection with the ΔhtrA mutant induced increased apoptosis rates in host cells, which was associated with reduced H. pylori CagA expression. In contrast, transcription of various carcinogenesis-associated genes (e.g. DKK1, DOCK8) was affected by H. pylori independent of HtrA. These findings suggest that H. pylori disturbs previously unknown molecular pathways in an HtrA-dependent and HtrA-independent manner, and provide valuable new insights of this significant pathogen in humans and thus potential targets for better controlling the risk of malignant transformation.<br
Keywords: Helicobacter; Cancer; RNA-seq; HtrA; Apoptosis; Inflammation

Efficacy of supplemented buffered peptone water for the isolation of Campylobacter jejuni and C. coli from broiler retail products - Oyarzabal, Omar A.; Backert, Steffen; Nagaraj, Manonmani; Miller, Robert S.; Hussain, Syeda K.; Oyarzabal, Esteban A. (Journal of Microbiological Methods, 2007)
Broiler retail samples (n = 113) were analyzed to determine (i) the effectiveness of buffered peptone water (BPW) supplemented with blood and antibiotics for the isolation of Campylobacter jejuni and C. coli, (ii) if a 1:4 enrichment ratio performs similarly as a 1:9 ratio, and (iii) if BPW is similar to Bolton broth for enumeration of Campylobacter spp. in retail broiler meat using the most probably number (MPN) procedure. Chi-square comparison showed that BPW performed similarly as Bolton broth (P ≤ 0.05) for Campylobacter isolation in breast tenders, boneless breasts, split breasts and skin samples. However, BPW showed a lower detection rate (P ≥ 0.05) for thighs and boneless thighs. When the results were combined, BPW performed similarly as Bolton broth for the isolation of Campylobacter spp. (P ≤ 0.05). BPW at an enrichment ratio of 1:4 was statistically similar to Bolton broth or BPW at a ratio of 1:9. No differences were observed between the MPN data from Bolton broth and the MPN data from BPW (P ≤ 0.50). A multiplex PCR assay revealed that ca. 48% of the isolates obtained from Bolton broth and 59% of the isolates obtained with BPW were C. coli. Both Bolton broth and BPW allowed for the growth of C. jejuni and C. coli from the same sample. Remarkably, a large genomic variability was observed by PFGE analysis of the isolates collected from the same sample with Bolton broth or BPW, which confirms that more than one genotype can successfully multiply during enrichment and be recoverable on agar plates. These findings suggest that BPW could be used as an enrichment medium for isolation of Campylobacter from retail broiler samples. The implications of the high number of C. coli isolates found in this study is discussed. © 2006 Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Broiler retail meat; Buffered peptone water; Campylobacter coli; Campylobacter jejuni

Electron Microscopic, Genetic and Protein Expression Analyses of Helicobacter acinonychis Strains from a Bengal Tiger - Tegtmeyer, Nicole; Traverso, Francisco Rivas; Rohde, Manfred; Oyarzabal, Omar A.; Lehn, Norbert; Schneider-Brachert, Wulf; Ferrero, Richard L.; Fox, James G.; Berg, Douglas E.; Backert, Steffen (PLoS ONE, 2013)
Colonization by Helicobacter species is commonly noted in many mammals. These infections often remain unrecognized, but can cause severe health complications or more subtle host immune perturbations. The aim of this study was to isolate and characterize putative novel Helicobacter spp. from Bengal tigers in Thailand. Morphological investigation (Gram-staining and electron microscopy) and genetic studies (16SrRNA, 23SrRNA, flagellin, urease and prophage gene analyses, RAPD DNA fingerprinting and restriction fragment polymorphisms) as well as Western blotting were used to characterize the isolated Helicobacters. Electron microscopy revealed spiral-shaped bacteria, which varied in length (2.5-6 μm) and contained up to four monopolar sheathed flagella. The 16SrRNA, 23SrRNA, sequencing and protein expression analyses identified novel H. acinonychis isolates closely related to H. pylori. These Asian isolates are genetically very similar to H. acinonychis strains of other big cats (cheetahs, lions, lion-tiger hybrid and other tigers) from North America and Europe, which is remarkable in the context of the great genetic diversity among worldwide H. pylori strains. We also found by immunoblotting that the Bengal tiger isolates express UreaseA/B, flagellin, BabA adhesin, neutrophil-activating protein NapA, HtrA protease, γ-glutamyl-transpeptidase GGT, Slt lytic transglycosylase and two DNA transfer relaxase orthologs that were known from H. pylori, but not the cag pathogenicity island, nor CagA, VacA, SabA, DupA or OipA proteins. These results give fresh insights into H. acinonychis genetics and the expression of potential pathogenicity-associated factors and their possible pathophysiological relevance in related gastric infections. © 2013 Tegtmeyer et al.
Created from Fastlane, Scopus look-up

Electron microscopic investigation of mitochondrial DNA from Chenopodium album (L.) - Backert, Steffen; Lurz, Rudi; Börner, Thomas (Current Genetics, 1996)
DNA molecules from mitochondria of whole plants and a suspension culture of Chenopodium album were prepared, by a gentle method, for analysis by electron microscopy. Mitochondrial (mt) DNA preparations from both sources contained mostly linear molecules of variable sizes (with the majority of molecules ranging from 40 to 160 kb). Open circular molecules with contour lengths corresponding to 0.3-183 kb represented 23-26% of all mtDNA molecules in the preparations from the suspension culture and 13-15% in the preparations from whole plants. More than 90% of the circular DNA was smaller than 30 kb. Virtually no size classes of the mtDNA molecules could be identified, and circular or linear molecules of the genome size (about 270 kb) were not observed. In contrast, plastid (pt) DNA preparations from the suspension culture contained linear and circular molecules falling into size classes corresponding to monomers, dimers and trimers of the chromosome. About 23% of the ptDNA molecules were circular. DNA preparations from mitochondria contained a higher percentage of more complex molecules (rosette-like structures, catenate-like molecules) than preparations of ptDNA. Sigma-like molecules (putative intermediates of rolling-circle replication) were observed in mtDNA preparations from the suspension culture (18% of the circles), and in much lower amount (1%) in preparations from whole plants. The results are compared with data obtained previously by pulsed-field gel electrophoresis and discussed in relation to the structural organization and replication of the mt genome of higher plants.
Created from Fastlane, Scopus look-up
Keywords: Chenopodium album; Mitochondrial DNA; Mitochondrial plasmid; Plastid DNA; Rolling-circle replication

Emerging roles of Abl family tyrosine kinases in microbial pathogenesis. - Backert, Steffen; Feller, Stephan M.; Wessler, Silja (Trends in Biochemical Sciences, 2008)
Abl family kinases are central regulators of multiple cellular processes controlling actin dynamics, proliferation and differentiation. Recent studies indicate that different pathogens highjack Abl kinase signalling to reorganize the host actin cytoskeleton and promote the tyrosine phosphorylation of four known bacterial and viral effector proteins. Abl signalling is implicated in such diverse processes as microbial invasion, viral release from host cells, actin-based motility, actin-rich pedestal formation and cell scattering. Thus, Abl kinases are emerging as crucial regulators of multiple pathological signalling cascades during infection. Therapeutic intervention against Abl kinase activity might be an effective and novel strategy to combat serious microbial diseases.

Enteropathogenic escherichia coli subverts phosphatidylinositol 4,5-bisphosphate and phosphatidylinositol 3,4,5-trisphosphate upon epithelial cell infection - Sason, Hagit; Milgrom, Michal; Weiss, Aryeh M.; Melamed-Book, Naomi; Balla, Tamas; Grinstein, Sergio; Backert, Steffen; Rosenshine, Ilan; Aroeti, Benjamin (Molecular Biology of the Cell, 2009)
Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] and phosphatidylinositol 3,4,5-trisphosphate [PI(3,4,5)P3] are phosphoi-nositides (PIs) present in small amounts in the inner leaflet of the plasma membrane (PM) lipid bilayer of host target cells. They are thought to modulate the activity of proteins involved in enteropathogenic Escherichia coli (EPEC) infection. However, the role of PI(4,5)P2 and PI(3,4,5)P 3 in EPEC pathogenesis remains obscure. Here we show that EPEC induces a transient PI(4,5)P2 accumulation at bacterial infection sites. Simultaneous actin accumulation, likely involved in the construction of the actin-rich pedestal, is also observed at these sites. Acute PI(4,5)P2 depletion partially diminishes EPEC adherence to the cell surface and actin pedestal formation. These findings are consistent with a bimodal role, whereby PI(4,5)P2 contributes to EPEC association with the cell surface and to the maximal induction of actin pedestals. Finally, we show that EPEC induces PI(3,4,5)P3 clustering at bacterial infection sites, in a translocated intimin receptor (Tir)-dependent manner. Tir phosphorylated on tyrosine 454, but not on tyrosine 474, forms complexes with an active phosphatidylinositol 3-kinase (PI3K), suggesting that PI3K recruited by Tir prompts the production of PI(3,4,5)P3 beneath EPEC attachment sites. The functional significance of this event may be related to the ability of EPEC to modulate cell death and innate immunity.© 2008 by The American Society for Cell Biology.
Created from Fastlane, Scopus look-up

Erratum: Helicobacter pylori adhesin HopQ engages in a virulence-enhancing interaction with human CEACAMs (Nature Microbiology (2016) 2 (16189)) - Javaheri, Anahita; Kruse, Tobias; Moonens, Kristof; Mejias-Luque, Raquel; Debraekeleer, Ayla; Asche, Isabell; Tegtmeyer-Backert, Nicole; Kalali, Behnam; Bach, Nina C.; Sieber, Stephan A.; Hill, Darryl J.; Koeniger, Verena; et al. (Nature Microbiology, 2016)
The original version of this Article contained incorrect labels in Figs 3b and 4e. In Fig. 3b, the second western blot panel should have been labelled 'CEACAM1'. In Fig. 4e, the final two values on the y axis should have read 'I91A' and 'I91T'. All versions of the Article have been updated. We apologize for any confusion this may have caused.
Created from Fastlane, Scopus look-up

Erratum: Induction of TLR-2 and TLR-5 expression by helicobacter pylori switches cagPAI-dependent signalling leading to the secretion of IL-8 and TNF-α (PLoS ONE (2015) 10:10 (e0141721)) - Pachathundikandi, Suneesh Kumar; Brandt, Sabine; Madassery, Joseph; Backert, Steffen (PLoS ONE, 2015)
Created from Fastlane, Scopus look-up

Erratum to: Type IV Secretion in Gram-Negative and Gram-Positive Bacteria - Backert, Steffen; Grohmann, Elisabeth (Current Topics in Microbiology and Immunology, 2017)
CRIS-Team Scopus Importer:2020-09-18

Establishment of serine protease htrA mutants in Helicobacter pylori is associated with secA mutations - Zawilak-Pawlik, Anna; Zarzecka, Urszula; Żyła-Uklejewicz, Dorota; Lach, Jakub; Strapagiel, Dominik; Tegtmeyer-Backert, Nicole; Böhm, Manja; Backert, Steffen; Skorko-Glonek, Joanna (Scientific Reports, 2019)
Helicobacter pylori plays an essential role in the pathogenesis of gastritis, peptic ulcer disease, and gastric cancer. The serine protease HtrA, an important secreted virulence factor, disrupts the gastric epithelium, which enables H. pylori to transmigrate across the epithelium and inject the oncogenic CagA protein into host cells. The function of periplasmic HtrA for the H. pylori cell is unknown, mainly due to unavailability of the htrA mutants. In fact, htrA has been described as an essential gene in this bacterium. We have screened 100 worldwide H. pylori isolates and show that only in the N6 strain it was possible to delete htrA or mutate the htrA gene to produce proteolytically inactive HtrA. We have sequenced the wild-type and mutant chromosomes and we found that inactivation of htrA is associated with mutations in SecA – a component of the Sec translocon apparatus used to translocate proteins from the cytoplasm into the periplasm. The cooperation of SecA and HtrA has been already suggested in Streptococcus pneumonia, in which these two proteins co-localize. Hence, our results pinpointing a potential functional relationship between HtrA and the Sec translocon in H. pylori possibly indicate for the more general mechanism responsible to maintain bacterial periplasmic homeostasis.
CRIS-Team Scopus Importer:2019-08-27

Evaluation of different plate media for direct cultivation of Campylobacter species from live broilers - Potturi-Venkata, Lakshmi Prasanna; Backert, Steffen; Lastovica, A. J.; Vieira, Sergio; Norton, Robert A.; Miller, Robert S.; Pierce, S. J.; Oyarzabal, Omar A. (Poultry Science, 2007)
Accurate identification and optimal culturing procedures for Campylobacter spp. from live broilers are needed for epidemiological studies. Because there is no standardized protocol, we designed and conducted studies to evaluate different selective media for the culturing and isolation of Campylobacter spp. from cecal and fecal samples obtained from battery-reared and commercial broilers. Five media selective for Campylobacter were evaluated: Campylobacter agar base, Campylobacter, Campy-Line, modified Campy-Cefex, and modified charcoal cefoperazone deoxycholate agar. With contaminated broilers reared in battery cages, Campylobacter agar base, Campylobacter, modified Campy-Cefex, and modified charcoal cefoperazone deoxycholate agar revealed similar isolation rates (P > 0.05), whereas Campy-Line showed a lower efficacy (P < 0.05). With commercial live broilers, modified Campy-Cefex agar was more consistent for the isolation of Campylobacter from feces, whereas modified Campy-Cefex and modified charcoal cefoperazone deoxycholate agar showed similar isolation rates from cecal samples. Campy-Line agar showed a lower identification rate (P < 0.05) for both fecal and cecal samples. A multiplex PCR assay used for identification showed that Campylobacter jejuni and Campylobacter coli DNA was present in the samples. Pulsed field gel electrophoresis restriction profiles differed among samples collected from different commercial farms but were similar for isolates from the same farm, suggesting clonal differences. No variation was seen in pulsed field gel electrophoresis patterns among isolates cultured on different media. Our data suggest that the choice of plate medium may influence the efficiency of isolating Campylobacter spp. from broiler chickens by direct plating from fecal or cecal samples. ©2007 Poultry Science Association Inc.
Created from Fastlane, Scopus look-up
Keywords: Broiler; Campylobacter; Plate media

Evaluation of logistic processing to reduce cross-contamination of commercial broiler carcasses with Campylobacter spp. - Potturi-Venkata, Lakshmi Prasanna; Backert, Steffen; Vieira, Sergio; Oyarzabal, Omar A. (Journal of Food Protection, 2007)
Cross-contamination of broiler carcasses with Campylobacter is a large problem in food production. Here, we investigated whether the contamination of broilers carcasses from Campylobacter-negative flocks can be avoided by logistic scheduling during processing. For this purpose, fecal samples were collected from several commercial broiler flocks and enumerated for Campylobacter spp. Based on enumeration results, flocks were categorized as Campylobacter negative or Campylobacter positive. The schedule of processing included the testing of Campylobacter-positive flocks before or after the testing of Campylobacter-negative flocks. During processing, flocks were also sampled for Campylobacter spp. before and after chilling. Campylobacter strains were identified with multiplex PCR and analyzed for relatedness with pulsed-field gel electrophoresis. Our results show that Campylobacter-negative flocks were indeed contaminated with Campylobacter strains originating from previously processed Campylobacter-positive flocks. Campylobacter isolates collected from carcasses originating from different farms processed on the same day showed similar pulsed-field gel electrophoresis patterns, confirming cross-contamination. These findings suggest that a simple logistic processing schedule can preserve the Campylobacter-negative status of broiler carcasses and result in products with enhanced food safety. Copyright ©, International Association for Food Protection.
Created from Fastlane, Scopus look-up

Evolution and Role of Proteases in Campylobacter jejuni Lifestyle and Pathogenesis - Linz, Bodo; Sharafutdinov, Irshad; Tegtmeyer, Nicole; Backert, Steffen (Biomolecules, 2023)
Infection with the main human food-borne pathogen Campylobacter jejuni causes campylobacteriosis that accounts for a substantial percentage of gastrointestinal infections. The disease usually manifests as diarrhea that lasts for up to two weeks. C. jejuni possesses an array of peptidases and proteases that are critical for its lifestyle and pathogenesis. These include serine proteases Cj1365c, Cj0511 and HtrA; AAA+ group proteases ClpP, Lon and FtsH; and zinc-dependent protease PqqE, proline aminopeptidase PepP, oligopeptidase PepF and peptidase C26. Here, we review the numerous critical roles of these peptide bond-dissolving enzymes in cellular processes of C. jejuni that include protein quality control; protein transport across the inner and outer membranes into the periplasm, cell surface or extracellular space; acquisition of amino acids and biofilm formation and dispersal. In addition, we highlight their role as virulence factors that inflict intestinal tissue damage by promoting cell invasion and mediating cleavage of crucial host cell factors such as epithelial cell junction proteins. Furthermore, we reconstruct the evolution of these proteases in 34 species of the Campylobacter genus. Finally, we discuss to what extent C. jejuni proteases have initiated the search for inhibitor compounds as prospective novel anti-bacterial therapies.
CRIS-Team Scopus Importer:2023-03-10
Keywords: anti-bacterial therapy; Campylobacter jejuni; lifestyle; pathogenesis; peptidase; protease; virulence factor

Exploiting the gastric epithelial barrier: Helicobacter pylori’s attack on tight and adherens junctions - Backert, Steffen; Schmidt, Thomas P.; Harrer, Aileen; Wessler, Silja (Molecular Pathogenesis and Signal Transduction by Helicobacter pylori, 2017)
Highly organized intercellular tight and adherens junctions are crucial structural components for establishing and maintenance of epithelial barrier functions, which control the microbiota and protect against intruding pathogens in humans. Alterations in these complexes represent key events in the development and progression of multiple infectious diseases as well as various cancers. The gastric pathogen Helicobacter pylori exerts an amazing set of strategies to manipulate these epithelial cell-to-cell junctions, which are implicated in changing cell polarity, migration and invasive growth as well as pro-inflammatory and proliferative responses. This chapter focuses on the H. pylori pathogenicity factors VacA, CagA, HtrA and urease, and how they can induce host cell signaling involved in altering cell-to-cell permeability. We propose a stepwise model for how H. pylori targets components of tight and adherens junctions in order to disrupt the gastric epithelial cell layer, giving fresh insights into the pathogenesis of this important bacterium.
Created from Fastlane, Scopus look-up

Expression of CEACAM1 or CEACAM5 in AZ-521 cells restores the type IV secretion deficiency for translocation of CagA by Helicobacter pylori - Tegtmeyer, Nicole; Harrer, Aileen; Schmitt, Verena; Singer, Bernhard B.; Backert, Steffen (Cellular Microbiology, 2019)
Helicobacter pylori represents an important pathogen involved in diseases ranging from gastritis, peptic ulceration, to gastric malignancies. Prominent virulence factors comprise the vacuolating cytotoxin VacA and the cytotoxin-associated genes pathogenicity island (cagPAI)-encoded type IV secretion system (T4SS). The T4SS effector protein CagA can be translocated into AGS and other gastric epithelial cells followed by phosphorylation through c-Src and c-Abl tyrosin kinases to hijack signalling networks. The duodenal cell line AZ-521 has been recently introduced as novel model system to investigate CagA delivery and phosphorylation in a VacA-dependent fashion. In contrast, we discovered that AZ-521 cells display a T4SS incompetence phenotype for CagA injection, which represents the first reported gastrointestinal cell line with a remarkable T4SS defect. We proposed that this deficiency may be due to an imbalanced coexpression of T4SS receptor integrin-β1 or carcinoembryonic antigen-related cell adhesion molecules (CEACAMs), which were described recently as novel H. pylori receptors. We demonstrate that AZ-521 cells readily express integrin-β1, but overexpression of integrin-β1 constructs did not restore the T4SS defect. We further show that AZ-521 cells lack the expression of CEACAMs. We demonstrate that genetic introduction of either CEACAM1 or CEACAM5, but not CEACAM6, in AZ-521 cells is sufficient to permit injection and phosphorylation of CagA by H. pylori to degrees observed in the AGS cell model. Expression of CEACAM1 or CEACAM5 in infected AZ-521 cells was also accompanied by tyrosine dephosphorylation of the cytoskeletal proteins vinculin and cortactin, a hallmark of H. pylori-infected AGS cells. Our results suggest the existence of an integrin-β1- and CEACAM1- or CEACAM5-dependent T4SS delivery pathway for CagA, which is clearly independent of VacA. The presence of two essential host protein receptors during infection with H. pylori represents a unique feature in the bacterial T4SS world. Further detailed investigation of these T4SS functions will help to better understand infection strategies by bacterial pathogens.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Abl; AGS; AZ-521; Caco2; CagA; CEACAM; cortactin; Helicobacter pylori; MKN45; signalling; Src; T4SS; type IV secretion; tyrosine kinases; VacA; vinculin

Expression of Helicobacter pylori serine protease HtrA in Campylobacter jejuni reveals a crucial function in oxygen stress resistance, heat tolerance and epithelial barrier disruption - Böhm, Manja; Tegtmeyer, Nicole; Harrer, Aileen; Skorko-Glonek, Joanna; Backert, Steffen (Journal of Cellular Immunology and Serum Biology, 2017)

Expression patterns and role of the CadF protein in Campylobacter jejuni and Campylobacter coli - Krause-Gruszczynska, Malgorzata; Van Alphen, Lieke B.; Oyarzabal, O. A.; Alter, Thomas; Hänel, Ingrid; Schliephake, Annette; König, Wolfgang; Van Putten, Jos P.M.; Konkel, Michael E.; Backert, Steffen (FEMS Microbiology Letters, 2007)
Binding of Campylobacter jejuni and Campylobacter coli to host fibronectin is mediated by the 37 kDa outer membrane protein CadF. Immunoblot analysis of 58 C. jejuni and C. coli isolates of human and animal origin showed that CadF is expressed in every strain. In most C. jejuni isolates, a 37 kDa band (p37) and a less-prominent 32 kDa band (p32) reacted with the antibodies. In C. coli isolates, CadF was consistently larger with sizes of 39 kDa (p39) and 34 kDa (p34), respectively. PCR analysis and sequencing revealed the presence of a 39-bp insertion sequence in the cadF gene of C. coli strains, explaining the increased molecular size. Infection assays revealed that C. jejuni bound and invaded INT-407 epithelial cells much more efficiently than C. coli and that this difference was considerably reduced in isogenic cadF mutants. These results demonstrate that CadF is an important pathogenicity factor. The difference between CadF of C. jejuni and C. coli may potentially be exploited to discriminate these species in food and clinical specimens. © 2007 Federation of European Microbiological Societies.
Created from Fastlane, Scopus look-up
Keywords: Adhesion; CadF; Campylobacter; Fibronectin; Invasion; Pathogenesis

Extracellular HtrA serine proteases: An emerging new strategy in bacterial pathogenesis. - Backert, Steffen; Bernegger, Sabine; Skorko-Glonek, Joanna; Wessler, Silja (Cellular Microbiology, 2018)

Fluorophore-conjugated Helicobacter pylori recombinant membrane protein (HopQ) labels primary colon cancer and metastases in orthotopic mouse models by binding CEA-related cell adhesion molecules - Hollandsworth, Hannah M.; Schmitt, Verena; Amirfakhri, Siamak; Filemoni, Filemoni; Schmidt, Alexej; Landström, Maréne; Lyndin, Mykola; Backert, Steffen; Gerhard, Markus; Wennemuth, Gunther; Hoffman, Robert M.; Singer, Bernhard B.; et al. (Translational Oncology, 2020)
HopQ is an outer-membrane protein of Helicobacter pylori that binds to human carcinoembryonic antigen-related cell-adhesion molecules (CEACAMs) with high specificity. We aimed to investigate fluorescence targeting of CEACAM-expressing colorectal tumors in patient-derived orthotopic xenograft (PDOX) models with fluorescently labeled recombinant HopQ (rHopQ). Western blotting, flow cytometry and ELISA were performed to determine the efficiency of rHopQ binding to CEACAMs. rHopQ was conjugated to IR800DyeCW (rHopQ-IR800). Nude mice received orthotopic implantation of colon cancer tumors. Three weeks later, mice were administered 25 μg or 50 μg HopQ-IR800 and imaged 24 or 48 h later. Intravital images were analyzed for tumor-to-background ratio (TBR). Flow cytometry and ELISA demonstrated binding of HopQ to CEACAM1, 3 and 5. Dose-response intravital imaging in PDOX models demonstrated optimal results 48 h after administration of 50 μg rHopQ-IR800 (TBR = 3.576) in our protocol. Orthotopic models demonstrated clear tumor margins of primary tumors and small regional metastases with a mean TBR = 3.678 (SD ± 1.027). rHopQ showed specific binding to various CEACAMs in PDOX models. rHopQ may be useful for CEACAM-positive tumor and metastasis detection for pre-surgical diagnosis, intra-operative imaging and fluorescence-guided surgery.
CRIS-Team Scopus Importer:2020-09-04

Food Safety Resources - Oyarzabal, Omar A.; Backert, Steffen (Microbial Food Safety, 2011)
There are several food safety resources available in the form of books, journals, trade magazines, and, more recently, through the Internet. This chapter briefly summarizes, in table format, most of the available resources that can provide complementary reading to the chapters described in this book. The summary starts with the books that deal mainly with food safety (Table 1), continues with other microbiology books with sections that deal with food safety (Table 2), moves on to list refereed-journal magazines related to food safety (Table 3), and finally provides some Internet resources related to food safety (Table 4).<br
Keywords: Food Safety; Trade Magazines; Table Format; Microbiology; Important Repository

Four Chromosomal Type IV Secretion Systems in Helicobacter pylori: Composition, Structure and Function - Fischer, Wolfgang; Tegtmeyer, Nicole; Stingl, Kerstin; Backert, Steffen (Frontiers in Microbiology, 2020)
The pathogenic bacterium Helicobacter pylori is genetically highly diverse and a major risk factor for the development of peptic ulcer disease and gastric adenocarcinoma in humans. During evolution, H. pylori has acquired multiple type IV secretion systems (T4SSs), and then adapted for various purposes. These T4SSs represent remarkable molecular transporter machines, often associated with an extracellular pilus structure present in many bacteria, which are commonly composed of multiple structural proteins spanning the inner and outer membranes. By definition, these T4SSs exhibit central functions mediated through the contact-dependent conjugative transfer of mobile DNA elements, the contact-independent release and uptake of DNA into and from the extracellular environment as well as the secretion of effector proteins in mammalian host target cells. In recent years, numerous features on the molecular functionality of these T4SSs were disclosed. H. pylori encodes up to four T4SSs on its chromosome, namely the Cag T4SS present in the cag pathogenicity island (cagPAI), the ComB system, as well as the Tfs3 and Tfs4 T4SSs, some of which exhibit unique T4SS functions. The Cag T4SS facilitates the delivery of the CagA effector protein and pro-inflammatory signal transduction through translocated ADP-heptose and chromosomal DNA, while various structural pilus proteins can target host cell receptors such as integrins or TLR5. The ComB apparatus mediates the import of free DNA from the extracellular milieu, whereas Tfs3 may accomplish the secretion or translocation of effector protein CtkA. Both Tfs3 and Tfs4 are furthermore presumed to act as conjugative DNA transfer machineries due to the presence of tyrosine recombinases with cognate recognition sequences, conjugational relaxases, and potential origins of transfer (oriT) found within the tfs3 and tfs4 genome islands. In addition, some extrachromosomal plasmids, transposons and phages have been discovered in multiple H. pylori isolates. The genetic exchange mediated by DNA mobilization events of chromosomal genes and plasmids combined with recombination events could account for much of the genetic diversity found in H. pylori. In this review, we highlight our current knowledge on the four T4SSs and the involved mechanisms with consequences for H. pylori adaptation to the hostile environment in the human stomach.
CRIS-Team Scopus Importer:2020-08-07
Keywords: cag; competence; conjugation; DNA transfer; pathogenicity island; recombination; type IV secretion system; virulence

Fragment-Based de Novo Design Reveals a Small-Molecule Inhibitor of Helicobacter Pylori HtrA - Perna, Anna M.; Rodrigues, Tiago; Schmidt, Thomas P.; Böhm, Manja; Stutz, Katharina; Reker, Daniel; Pfeiffer, Bernhard; Altmann, Karl-Heinz; Backert, Steffen; Wessler, Silja; Schneider, Gisbert (Angewandte Chemie International Edition, 2015)
Sustained identification of innovative chemical entities is key for the success of chemical biology and drug discovery. We report the fragment-based, computer-assisted de novo design of a small molecule inhibiting Helicobacter pylori HtrA protease. Molecular binding of the designed compound to HtrA was confirmed through biophysical methods, supporting its functional activity in vitro. Hit expansion led to the identification of the currently best-in-class HtrA inhibitor. The results obtained reinforce the validity of ligand-based de novo design and binding-kinetics-guided optimization for the efficient discovery of pioneering lead structures and prototyping drug-like chemical probes with tailored bioactivity.
Created from Fastlane, Scopus look-up
Keywords: biophysical methods; chemical biology; computer-assisted drug design; drug design; receptor-ligand interactions

Functional analysis and cryo-electron microscopy of Campylobacter jejuni serine protease HtrA - Zarzecka, Urszula; Grinzato, Alessandro; Kandiah, Eaazhisai; Cysewski, Dominik; Berto, Paola; Skorko-Glonek, Joanna; Zanotti, Giuseppe; Backert, Steffen (Gut Microbes, 2020)
Campylobacter jejuni is a predominant zoonotic pathogen causing gastroenteritis and other diseases in humans. An important bacterial virulence factor is the secreted serine protease HtrA (HtrA Cj), which targets tight and adherens junctional proteins in the gut epithelium. Here we have investigated the function and structure of HtrA Cj using biochemical assays and cryo-electron microscopy. Mass spectrometry analysis identified differences and similarities in the cleavage site specificity for HtrA Cj by comparison to the HtrA counterparts from Helicobacter pylori and Escherichia coli. We defined the architecture of HtrA Cj at 5.8 Å resolution as a dodecamer, built of four trimers. The contacts between the trimers are quite loose, a fact that explains the flexibility and mobility of the dodecameric assembly. This flexibility has also been studied through molecular dynamics simulation, which revealed opening of the dodecamer to expose the proteolytically active site of the protease. Moreover, we examined the rearrangements at the level of oligomerization in the presence or absence of substrate using size exclusion chromatography, which revealed hexamers, dodecamers and larger oligomeric forms, as well as remarkable stability of higher oligomeric forms (> 12-mers) compared to previously tested homologs from other bacteria. Extremely dynamic decay of the higher oligomeric forms into lower forms was observed after full cleavage of the substrate by the proteolytically active variant of HtrA Cj. Together, this is the first report on the in-depth functional and structural analysis of HtrA Cj, which may allow the construction of therapeutically relevant HtrA Cj inhibitors in the near future.
CRIS-Team Scopus Importer:2020-10-02
Keywords: Campylobacter jejuni; cleavage site specificity; cryo-EM; HtrA; oligomerization; protease; thermal stability

Functional Analysis of the cag Pathogenicity Island in Helicobacter pylori Isolates from Patients with Gastritis, Peptic Ulcer, and Gastric Cancer - Backert, Steffen; Schwarz, Tobias; Miehlke, Stephan; Kirsch, Christian; Sommer, Christian; Kwok, Terry; Gerhard, Markus; Goebel, Ulf B.; Lehn, Norbert; König, Wolfgang; Meyer, Thomas F. (Infection and Immunity, 2004)
Helicobacter pylori is the causative agent of a variety of gastric diseases, but the clinical relevance of bacterial virulence factors is still controversial. Virulent strains carrying the cag pathogenicity island (cagPAI) are thought to be key players in disease development. Here, we have compared cagPAI-dependent in vitro responses in H. pylori isolates obtained from 75 patients with gastritis, peptic ulcer, and gastric cancer (n = 25 in each group). AGS gastric epithelial cells were infected with each strain and assayed for (i) CagA expression, (ii) translocation and tyrosine phosphorylation of CagA, (iii) c-Src inactivation, (iv) cortactin dephosphorylation, (v) induction of actin cytoskeletal rearrangements associated with cell elongation, (vi) induction of cellular motility, and (vii) secretion of interleukin-8. Interestingly, we found high but similar prevalences of all of these cagPAI-dependent host cell responses (ranging from 56 to 80%) among the various groups of patients. This study revealed CagA proteins with unique features, CagA subspecies of various sizes, and new functional properties for the phenotypic outcomes. We further showed that induction of AGS cell motility and elongation are two independent processes. Our data corroborate epidemiological studies, which indicate a significant association of cagPAI presence and functionality with histopathological findings in gastritis, peptic ulcer, and gastric cancer patients, thus emphasizing the importance of the cagPAI for the pathogenicity of H. pylori. Nevertheless, we found no significant association of the specific H. pylori-induced responses with any particular patient group. This may indicate that the determination of disease development is highly complex and involves multiple bacterial and/or host factors.
Created from Fastlane, Scopus look-up

Functional analysis of the Helicobacter pylori cag pathogenicity island reveals both VirD4-CagA-dependent and VirD4-CagA-independent mechanisms. - Selbach, M.; Moese, S.; Meyer, Thomas F.; Backert, Steffen (Infection and Immunity, 2002)
The type IV secretion machinery encoded by the cag pathogenicity island (PAI) of Helicobacter pylori has been implicated in a series of host responses during infection. Here, we analyzed the function of 12 cag PAI genes from both cag I and cag II loci, including the complete virB/D complex (virB4, virB7, virB8, virB9, virB10, virB11, and virD4). We monitored interleukin-8 (IL-8) secretion, CagA translocation and tyrosine phosphorylation, and induction of a scattering ("hummingbird") phenotype upon H. pylori infection of AGS gastric epithelial cells. For the first time, we have complemented individual cag PAI gene knockout mutants with their intact genes expressed from a shuttle vector and showed that complemented CagA and VirD4 restored wild-type function. Our results demonstrate that phenotypic changes and phosphorylation of CagA depended on all virB/D genes and several other genes of the cag PAI. Induction of IL-8 secretion depended largely on the same set of genes but was independent of CagA and VirD4. Thus, CagA translocation and induction of IL-8 secretion are regulated by VirD4-CagA-dependent and VirD4-CagA-independent mechanisms, respectively. The function of VirD4 as a possible adapter protein which guides CagA into the type IV secretion channel is presented in a model.

Function of Serine Protease HtrA in the Lifecycle of the Foodborne Pathogen Campylobacter jejuni - Böhm, Manja; Simson, Daniel; Escher, Ulrike; Schmidt, Anna-Maria; Bereswill, Stefan; Tegtmeyer, Nicole; Backert, Steffen; Heimesaat, Markus M. (European Journal of Microbiology and Immunology, 2018)
Campylobacter jejuni is a major food-borne zoonotic pathogen, responsible for a large proportion of bacterial gastroenteritis cases, as well as Guillian-Barre and Miller-Fisher syndromes. During infection, tissue damage is mainly caused by bacteria invading epithelial cells and traversing the intestinal barrier. C. jejuni is able to enter the lamina propria and the bloodstream and may move into other organs, such as spleen, liver, or mesenteric lymph nodes. However, the involved molecular mechanisms are not fully understood. C. jejuni can transmigrate effectively across polarized intestinal epithelial cells mainly by the paracellular route using the serine protease high-temperature requirement A (HtrA). However, it appears that HtrA has a dual function, as it also acts as a chaperone, interacting with denatured or misfolded periplasmic proteins under stress conditions. Here, we review recent progress on the role of HtrA in C. jejuni pathogenesis. HtrA can be transported into the extracellular space and cleaves cell-to-cell junction factors, such as E-cadherin and probably others, disrupting the epithelial barrier and enabling paracellular transmigration of the bacteria. The secretion of HtrA is a newly discovered strategy also utilized by other pathogens. Thus, secreted HtrA proteases represent highly attractive targets for anti-bacterial treatment and may provide a suitable candidate for vaccine development.
Created from Fastlane, WoS look-up

Gastric Epithelial Barrier Disruption, Inflammation and Oncogenic Signal Transduction by Helicobacter pylori - Naumann, Michael; Ferino, Lorena; Sharafutdinov, Irshad; Backert, Steffen (Springer Science and Business Media Deutschland GmbH, 2023)
Helicobacter pylori exemplifies one of the most favourable bacterial pathogens worldwide. The bacterium colonizes the gastric mucosa in about half of the human population and constitutes a major risk factor for triggering gastric diseases such as stomach cancer. H. pylori infection represents a prime example of chronic inflammation and cancer-inducing bacterial pathogens. The microbe utilizes a remarkable set of virulence factors and strategies to control cellular checkpoints of inflammation and oncogenic signal transduction. This chapter emphasizes on the pathogenicity determinants of H. pylori such as the cytotoxin-associated genes pathogenicity island (cagPAI)-encoded type-IV secretion system (T4SS), effector protein CagA, lipopolysaccharide (LPS) metabolite ADP-glycero-β-D-manno-heptose (ADP-heptose), cytotoxin VacA, serine protease HtrA, and urease, and how they manipulate various key host cell signaling networks in the gastric epithelium. In particular, we highlight the H. pylori-induced disruption of cell-to-cell junctions, pro-inflammatory activities, as well as proliferative, pro-apoptotic and anti-apoptotic responses. Here we review these hijacked signal transduction events and their impact on gastric disease development.
CRIS-Team Scopus Importer:2024-12-16
Keywords: ALPK1; Cortactin; NF-κB; TIFA; Wnt

Gene content, phage cycle regulation model and prophage inactivation disclosed by prophage genomics in the Helicobacter pylori Genome Project - Vale, Filipa F.; Roberts, Richard J.; Kobayashi, Ichizo; Camargo, M. Constanza; Rabkin, Charles S.; Wang, Difei; Hicks, Belynda; Zhu, Bin; Yeager, Meredith; Hutchinson, Amy; Teshome, Kedest; Jones, Kristie; et al. (Gut Microbes, 2024)
Prophages can have major clinical implications through their ability to change pathogenic bacterial traits. There is limited understanding of the prophage role in ecological, evolutionary, adaptive processes and pathogenicity of Helicobacter pylori, a widespread bacterium causally associated with gastric cancer. Inferring the exact prophage genomic location and completeness requires complete genomes. The international Helicobacter pylori Genome Project (HpGP) dataset comprises 1011 H. pylori complete clinical genomes enriched with epigenetic data. We thoroughly evaluated the H. pylori prophage genomic content in the HpGP dataset. We investigated population evolutionary dynamics through phylogenetic and pangenome analyses. Additionally, we identified genome rearrangements and assessed the impact of prophage presence on bacterial gene disruption and methylome. We found that 29.5% (298) of the HpGP genomes contain prophages, of which only 32.2% (96) were complete, minimizing the burden of prophage carriage. The prevalence of H. pylori prophage sequences was variable by geography and ancestry, but not by disease status of the human host. Prophage insertion occasionally results in gene disruption that can change the global bacterial epigenome. Gene function prediction allowed the development of the first model for lysogenic-lytic cycle regulation in H. pylori. We have disclosed new prophage inactivation mechanisms that appear to occur by genome rearrangement, merger with other mobile elements, and pseudogene accumulation. Our analysis provides a comprehensive framework for H. pylori prophage biological and genomics, offering insights into lysogeny regulation and bacterial adaptation to prophages.
CRIS-Team Scopus Importer:2024-09-13
Keywords: genome rearrangement; H. pylori; HpGP; mobile elements; phage cycle; prophage

Gene expression and protein profiling of AGS gastric epithelial cells upon infection with Helicobacterpylori - Backert, Steffen; Gressmann, Helga; Kwok, Terry; Zimny-Arndt, Ursula; König, Wolfgang; Jungblut, Peter R.; Meyer, Thomas F. (Proteomics, 2005)
Helicobacter pylon, one of the most common bacterial pathogens, colonizes the human stomach and causes a variety of gastric diseases. This pathogen elicits a range of phenotypic responses in infected cultured AGS gastric epithelial cells, including expression of proinflammatory genes and changes in the actin cytoskeleton. Some of these responses are mediated by the type IV secretion system (T4SS) encoded by the cag pathogenicity island. We have used two global approaches, namely 2-DE combined with PMF and cDNA expression array analyses, to study in both a comprehensive and quantitative manner the protein profile and the temporal patterns of mRNA accumulation in AGS cells upon infection with H. pylori and isogenic T4SS mutants. We identified 140 transcripts and detected 190 protein species that were differentially regulated upon infection. Infection with wild-type H. pylori induced expression of a variety of host genes and changes in protein pattern involved in transcriptional responses, cell shape regulation and signal transduction. Among them, some were differentially regulated in a cag PAI-dependent manner, as shown by both the proteomic and cDNA expression array approaches. While 2-DE and PMF allowed us to examine the protein profiles in the infected host, array analysis enabled us to demonstrate dynamic temporal changes in host gene expression profile. In conclusion, our combined application of the two global approaches provides further molecular details on how the host cell responds to infection by H. pylon and its isogenic T4SS mutants on both transcriptional and protein levels. The findings pinpoint host proteins such as serine/threonine and tyrosine kinases, transcription factors, cell cycle related components and actin cytoskeletal signaling molecules as potential targets of individual H. pylori virulence determinants. This study serves as a basis for future work on transcription and proteome analyses of the H. pylori infection model. © 2005 Wiley-VCH Verlag GmbH & Co. KGaA.
Created from Fastlane, Scopus look-up
Keywords: cDNA expression array; Mass spectrometry; Molecular pathogenesis; Pathogenicity island; Type IV secretion

Genetic polymorphisms in inflammatory and other regulators in gastric cancer: Risks and clinical consequences - Rudnicka, Karolina; Backert, Steffen; Chmiela, Magdalena (Molecular Mechanisms of Inflammation: Induction, Resolution and Escape by Helicobacter pylori, 2019)
Helicobacter pylori infection is associated with the development of a chronic inflammatory response, which may induce peptic ulcers, gastric cancer (GC), and mucosa-associated lymphoid tissue (MALT) lymphoma. Chronic H. pylori infection promotes the genetic instability of gastric epithelial cells and interferes with the DNA repair systems in host cells. Colonization of the stomach with H. pylori is an important cause of non-cardia GC and gastric MALT lymphoma. The reduction of GC development in patients who underwent anti-H. pylori eradication schemes has also been well described. Individual susceptibility to GC development depends on the host’s genetic predisposition, H. pylori virulence factors, environmental conditions, and geographical determinants. Biological determinants are urgently sought to predict the clinical course of infection in individuals with confirmed H. pylori infection. Possible candidates for such biomarkers include genetic aberrations such as single-nucleotide polymorphisms (SNPs) found in various cytokines/growth factors (e.g., IL-1β, IL-2, IL-6, IL-8, IL-10, IL-13, IL-17A/B, IFN-γ, TNF, TGF-β) and their receptors (IL-RN, TGFR), innate immunity receptors (TLR2, TLR4, CD14, NOD1, NOD2), enzymes involved in signal transduction cascades (PLCE1, PKLR, PRKAA1) as well as glycoproteins (MUC1, PSCA), and DNA repair enzymes (ERCC2, XRCC1, XRCC3). Bacterial determinants related to GC development include infection with CagA-positive (particularly with a high number of EPIYA-C phosphorylation motifs) and VacA-positive isolates (in particular s1/m1 allele strains). The combined genotyping of bacterial and host determinants suggests that the accumulation of polymorphisms favoring host and bacterial features increases the risk for precancerous and cancerous lesions in patients.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Gastric cancer; Gene polymorphism; Helicobacter pylori; Inflammation; SNP

Helicobacter exploits integrin for type IV secretion and kinase activation - Kwok, Terry; Zabler, Dana; Urman, Sylwia; Rohde, Manfred; Hartig, Roland; Wessler, Silja; Misselwitz, Rolf; Berger, Jürgen; Sewald, Norbert; König, Wolfgang; Backert, Steffen (Nature, 2007)
Integrins are important mammalian receptors involved in normal cellular functions as well as pathogenesis of chronic inflammation and cancer. We propose that integrins are exploited by the gastric pathogen and type-1 carcinogen Helicobacter pylori for injection of the bacterial oncoprotein cytotoxin-associated gene A (CagA) into gastric epithelial cells. Virulent H. pylori express a type-IV secretion pilus that injects CagA into the host cell; CagA then becomes tyrosine-phosphorylated by Src family kinases. However, the identity of the host cell receptor involved in this process has remained unknown. Here we show that the H. pylori CagL protein is a specialized adhesin that is targeted to the pilus surface, where it binds to and activates integrin α5β1 receptor on gastric epithelial cells through an arginine-glycine-aspartate motif. This interaction triggers CagA delivery into target cells as well as activation of focal adhesion kinase and Src. Our findings provide insights into the role of integrins in H.-pylori-induced pathogenesis. CagL may be exploited as a new molecular tool for our further understanding of integrin signalling. ©2007 Nature Publishing Group.
Created from Fastlane, Scopus look-up

Helicobacter pylori activates protein kinase C delta to control Raf in MAP kinase signalling: Role in AGS epithelial cell scattering and elongation - Brandt, Sabine; Wessler, Silja; Hartig, Roland; Backert, Steffen (Cell Motility and the Cytoskeleton, 2009)
Helicobacter pylori is a major etiological agent in the development of chronic gastritis, duodenal ulcer and gastric carcinoma in humans. Virulent H. pylori strains harbor a type IV secretion system (T4SS) encoded by the cag pathogenicity island. This T4SS injects the CagA protein into gastric epithelial cells leading to actin-cytoskeletal rearrangements followed by cell elongation and scattering. Here we report that PMA (4β-phorbol-12-myristate-13- acetate), a well-known cell-permeable activator of protein kinase C (PKC), induces a remarkably similar cellular phenotype as compared to infection with H. pylori. PKCs comprise a large family of serine/threonine kinases which are important for multiple physiological processes of host cells. We therefore investigated the role of individual PKC members and the signalling pathways involved in phenotypical outcome. Using isoform-specific silencing RNAs and pharmacological inhibitors we found that two isoforms, PKC-α and PKC-δ, were essential for both PMA- and H. pylori-induced elongation phenotype. Furthermore, we provide evidence that PKC-δ activity is profoundly stimulated during the course of infection using activation-specific antibodies against PKC phosphorylated at threonine residue 505 or serine residue 660. Infection with H. pylori wild-type and mutants showed that at least two bacterial factors activate PKC-δ in a time-dependent manner, one of which is CagA. Immunofluorescence microscopy studies further demonstrated that phosphorylated PKC-δ is accumulated and recruited to dynamic actin-structures at the cell membrane. Finally, we show that PKC-δ specifically targets Raf kinase to stimulate the Erk1/2 kinase pathway, which is also crucial for phenotypical outcome. Thus, PKC-δ is another important mediator of H. pylori-induced pathogenesis. © 2009 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; Protein kinase C; Silencing RNA; Type IV secretion; Tyrosine phosphorylation; Virulence

Helicobacter pylori adhesin HopQ disrupts trans dimerization in human CEACAMs. - Moonens, Kristof; Hamway, Youssef; Neddermann, Matthias; Reschke, Marc; Tegtmeyer, Nicole; Kruse, Tobias; Kammerer, Robert; Mejias-Luque, Raquel; Singer, Bernhard B.; Backert, Steffen; Gerhard, Markus; Remaut, Han (EMBO Journal, 2018)

Helicobacter pylori adhesin HopQ engages in a virulence-enhancing interaction with human CEACAMs - Javaheri, Anahita; Kruse, Tobias; Moonens, Kristof; Mejias-Luque, Raquel; Debraekeleer, Ayla; Asche, Carmen I.; Tegtmeyer-Backert, Nicole; Kalali, Behnam; Bach, Nina C.; Sieber, Stephan A.; Hill, Darryl J.; Koeniger, Verena; et al. (Nature Microbiology, 2016)
Helicobacter pylori specifically colonizes the human gastric epithelium and is the major causative agent for ulcer disease and gastric cancer development. Here, we identify members of the carcinoembryonic antigen-related cell adhesion molecule (CEACAM) family as receptors of H. pylori and show that HopQ is the surface-exposed adhesin that specifically binds human CEACAM1, CEACAM3, CEACAM5 and CEACAM6. HopQ-CEACAM binding is glycan-independent and targeted to the N-domain. H. pylori binding induces CEACAM1-mediated signalling, and the HopQ-CEACAM1 interaction enables translocation of the virulence factor CagA into host cells and enhances the release of pro-inflammatory mediators such as interleukin-8. Based on the crystal structure of HopQ, we found that a β-hairpin insertion (HopQ-ID) in HopQ's extracellular 3+4 helix bundle domain is important for CEACAM binding. A peptide derived from this domain competitively inhibits HopQ-mediated activation of the Cag virulence pathway, as genetic or antibody-mediated abrogation of the HopQ function shows. Together, our data suggest the HopQ-CEACAM1 interaction to be a potentially promising novel therapeutic target to combat H. pylori-associated diseases.
Created from Fastlane, Scopus look-up

Helicobacter pylori and the gut microbiota - Linz, Bodo; Backert, Steffen (Microbiota in Health and Disease, 2021)
The gut microbiota inherits fundamental functions in the preservation of human health properties as they are crucial for nutrient acquisition and digestive properties, energy metabolism, and training of host immunity functions. Colonization of the human stomach by the gastric pathogen Helicobacter pylori and corresponding antibiotic treatment regimens have a great impact on the number and composition of the gut microbiota. Recently, treatment with probiotic bacteria come into focus as nutritional supplements for H. pylori suppression and to boost the success rate of antibiotic treatment against the pathogen, to mitigate the gut dysbiosis and to accelerate the restoration of the gut microbiota. The present article reviews the most recent literature between April 2020 and March 2021 about the impact of H. pylori infection and its antimicrobial treatment on the gut microbiota.<br

Helicobacter pylori: A Paradigm Pathogen for Subverting Host Cell Signal Transmission - Naumann, Michael; Sokolova, Olga; Tegtmeyer, Nicole; Backert, Steffen (Trends in Microbiology, 2017)
Helicobacter pylori colonizes the gastric mucosa in the human stomach and represents a major risk factor for peptic ulcer disease and gastric cancer. Here, we summarize our current knowledge of the complex impact of H. pylori on manipulating host signalling networks, that is, by the cag pathogenicity island (cagPAI)-encoded type IV secretion system (T4SS). We show that H. pylori infections reflect a paradigm for interspecies contact-dependent molecular communication, which includes the disruption of cell–cell junctions and cytoskeletal rearrangements, as well as proinflammatory, cell cycle-related, proliferative, antiapoptotic, and DNA damage responses. The contribution of these altered signalling cascades to disease outcome is discussed.
Created from Fastlane, Scopus look-up
Keywords: gastric cancer; inflammation; pathogen; signalling pathways; T4SS

Helicobacter pylori avoids the critical activation of NLRP3 inflammasome-mediated production of oncogenic mature il-1β in human immune cells - Suneesh Kumar, Pachathundikandi; Blaser, Nicole; Bruns, Heiko; Backert, Steffen (Cancers, 2020)
Helicobacter pylori persistently colonizes the human stomach, and is associated with inflammation-induced gastric cancer. Bacterial crosstalk with the host immune system produces various inflammatory mediators and subsequent reactions in the host, but not bacterial clearance. Interleukin-1β (IL-1β) is implicated in gastric cancer development and certain gene polymorphisms play a role in this scenario. Mature IL-1β production depends on inflammasome activation, and the NLRP3 inflammasome is a major driver in H. pylori-infected mice, while recent studies demonstrated the down-regulation of NLRP3 expression in human immune cells, indicating a differential NLRP3 regulation in human vs. mice. In addition to the formation of mature IL-1β or IL-18, inflammasome activation induces pyroptotic death in cells. We demonstrate that H. pylori infection indeed upregulated the expression of pro-IL-1β in human immune cells, but secreted only very low amounts of mature IL-1β. However, application of exogenous control activators such as Nigericin or ATP to infected cells readily induced NLRP3 inflammasome formation and secretion of high amounts of mature IL-1β. This suggests that chronic H. pylori infection in humans manipulates inflammasome activation and pyroptosis for bacterial persistence. This inflammasome deregulation during H. pylori infection, however, is prone to external stimulation by microbial, environmental or host molecules of inflammasome activators for the production of high amounts of mature IL-1β and signaling-mediated gastric tumorigenesis in humans.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Helicobacter pylori; Inflammasome; Interleukin-1β; NLRP3

Helicobacter pylori caga induces cortactin y-470 phosphorylation-dependent gastric epithelial cell scattering via abl, vav2 and rac1 activation - Tegtmeyer, Nicole; Harrer, Aileen; Rottner, Klemens; Backert, Steffen (Cancers, 2021)
The pathogen Helicobacter pylori is the first reported bacterial type-1 carcinogen playing a role in the development of human malignancies, including gastric adenocarcinoma. Cancer cell motility is an important process in this scenario, however, the molecular mechanisms are still not fully understood. Here, we demonstrate that H. pylori subverts the actin-binding protein cortactin through its type-IV secretion system and injected oncoprotein CagA, e.g., by inducing tyrosine phosphorylation of cortactin at Y-470, which triggers gastric epithelial cell scattering and motility. During infection of AGS cells, cortactin was discovered to undergo tyrosine dephosphorylation at residues Y-421 and Y-486, which is mediated through inactivation of Src kinase. However, H. pylori also profoundly activates tyrosine kinase Abl, which simultaneously phosphorylates cortactin at Y-470. Phosphorylated cortactin interacts with the SH2-domain of Vav2, a guanine nucleotide exchange factor for the Rho-family of GTPases. The cortactin/Vav2 complex then stimulates a previously unrecognized activation cascade including the small GTPase Rac1, to effect actin rearrangements and cell scattering. We hypothesize that injected CagA targets cortactin to locally open the gastric epithelium in order to get access to certain nutrients. This may disturb the cellular barrier functions, likely contributing to the induction of cell motility, which is important in gastric cancer development.
CRIS-Team Scopus Importer:2021-09-10
Keywords: Cancer; Cortactin; Helicobacter; Pathogenesis; Pathogenicity island; Signaling; Virulence

Helicobacter pylori CagA Tertiary Structure Reveals Functional Insights - Backert, Steffen; Tegtmeyer, Nicole (Cell Host & Microbe, 2012)
CagA is a major disease-associated factor injected by the gastric pathogen Helicobacter pylori. In this issue, Hayashi et al. (2012) report the crystallographic structure of the CagA N terminus (residues 24–876) at 3.19 Å resolution. This study revealed three distinct domains, giving novel insights into intramolecular and intermolecular protein and phosphatidylserine interactions.
Created from Fastlane, Scopus look-up

Helicobacter pylori CagL Activates ADAM17 to Induce Repression of the Gastric H, K-ATPase α Subunit - Saha, Arindam; Backert, Steffen; Hammond, Charles E.; Gooz, Monika; Smolka, Adam J. (Gastroenterology, 2010)
Background & Aims: Infection with Helicobacter pylori represses expression of the gastric H, K-adenosine triphosphatase α-subunit (HKα), which could contribute to transient hypochlorhydria. CagL, a pilus protein component of the H pylori type IV secretion system, binds to the integrin α5β1 to mediate translocation of virulence factors into the host cell and initiate signaling. α5β1 binds a disintegrin and metalloprotease (ADAM) 17, a metalloenzyme that catalyzes ectodomain shedding of receptor tyrosine kinase ligands. We investigated whether H pylori-induced repression of HKα is mediated by CagL activation of ADAM17 and release of heparin-binding epidermal growth factor (HB-EGF). Methods: HKα promoter and ADAM17 activity were measured in AGS gastric epithelial cells transfected with HKα promoter-reporter constructs or ADAM17-specific small interfering RNAs and infected with H pylori. HB-EGF secretion was measured by enzyme-linked immunosorbent assay analysis, and ADAM17 interaction with integrins was investigated by coimmunoprecipitation analyses. Results: Infection of AGS cells with wild-type H pylori or an H pylori cagL-deficient isogenic mutant that also contained a wild-type version of cagL (P12ΔcagL/cagL) repressed HKα promoter-Luc reporter activity and stimulated ADAM17 activity. Both responses were inhibited by point mutations in the nuclear factor-κB binding site of HKα or by infection with P12ΔcagL. Small interfering RNA-mediated silencing of ADAM17 in AGS cells inhibited the repression of wild-type HKα promoter and reduced ADAM17 activity and HB-EGF production, compared to controls. Coimmunoprecipitation studies of AGS lysates showed that wild-type H pylori disrupted ADAM17-α5β1 complexes. Conclusions: During acute H pylori infection, CagL dissociates ADAM17 from the integrin α5β1 and activates ADAM17-dependent, nuclear factor-κB-mediated repression of HKα. This might contribute to transient hypochlorhydria in patients with H pylori infection. © 2010 AGA Institute.
Created from Fastlane, Scopus look-up
Keywords: ADAM17; CagL; H; K-ATPase; Helicobacter pylori

Helicobacter pylori CagL dependent induction of gastrin expression via a novel αvβ 5-integrineintegrin linked kinase signalling complex - Wiedemann, Tobias; Hofbaur, Stefan; Tegtmeyer, Nicole; Huber, Sylwia; Sewald, Norbert; Wessler, Silja; Backert, Steffen; Rieder, Gabriele (Gut, 2012)
Objective: One of the most important hormones in the human stomach is the peptide gastrin. It is mainly required for the regulation of gastric pH but is also involved in growth and differentiation of gastric epithelial cells. In Helicobacter pylori infected patients, gastrin secretion can be upregulated by the pathogen, resulting in hypergastrinaemia. H pylori induced hypergastrinaemia is described as being a major risk factor for the development of gastric adenocarcinoma. Design: In this study, the upstream receptor complex and bacterial factors involved in H pylori induced gastrin gene expression were investigated, utilising gastric epithelial cells which were stably transfected with a human gastrin promoter luciferase reporter construct. Results: Integrin linked kinase (ILK) and integrin b5, but not integrin β1, played an important role in gastrin promoter activation. Interestingly, a novel CagL/integrin β5/ILK signalling complex was characterised as being important for H pylori induced gastrin expression. On interaction of H pylori with αvβ 5-integrin and ILK, the epidermal growth factor receptor (EGFR) →Raf→mitogen activated protein kinase kinase (MEK)→extracellular signal regulated kinase (Erk) downstream signalling cascade was identified which plays a central role in H pylori gastrin induction. Conclusion: The newly discovered recognition receptor complex could be a useful target in treating precancerous conditions triggered by H pylori induced hypergastrinaemia.
Created from Fastlane, Scopus look-up

Helicobacter pylori CagL Y58/E59 mutation turns-off type IV secretion-dependent delivery of CagA into host cells - Tegtmeyer, Nicole; Lind, Judith; Schmid, Benedikt; Backert, Steffen (PLoS ONE, 2014)
The type IV secretion system (T4SS) is a major virulence determinant of the gastric pathogen Helicobacter pylori. The CagL protein is a specialized adhesin of the corresponding T4SS pilus, which establishes initial contact with the integrin β1 receptor on host target cells. Recent studies proposed that Y58 and E59 amino acid polymorphisms in CagL increase the virulence of H. pylori strains by enhanced translocation and phosphorylation of the CagA effector protein. These polymorphisms were therefore correlated with an increased risk of gastric cancer development. Here we show that the Y58/E59 motif, which is located in a loop connecting two α-helices, and corresponding polymorphisms could influence the function of CagL. However, expression of isogenic CagL Y58/E59 variants in H. pylori strain 26695 significantly blocked the translocation and phosphorylation of CagA as compared to complemented wild-type CagL. These results suggest that the function of the T4SS for delivery of CagA is turned-off by the Y58/E59 mutation in CagL. This activity appears to be similar to the one recently described for another T4SS pilus protein, CagY, which is also sufficient to cause gain or loss of T4SS function. These data support the hypothesis that certain mutations in CagL or recombination events in CagY may serve as a sort of molecular switch or perhaps rheostat in the T4SS, which could alter the function of the pilus and "tunes" injection of CagA and host pro-inflammatory responses, respectively. © 2014 Tegtmeyer et al.

Helicobacter pylori cell translocating kinase (CtkA/JHP0940) is pro-apoptotic in mouse macrophages and acts as auto-phosphorylating tyrosine kinase - Tenguria, Shivendra; Ansari, Suhail A.; Khan, Nooruddin; Ranjan, Amit; Devi, Savita; Tegtmeyer, Nicole; Lind, Judith; Backert, Steffen; Ahmed, Niyaz (International Journal of Medical Microbiology, 2014)
The Helicobacter pylori gene JHP0940 has been shown to encode a serine/threonine kinase which can induce cytokines in gastric epithelial cells relevant to chronic gastric inflammation. Here we demonstrate that JHP0940 can be secreted by the bacteria, triggers apoptosis in cultured mouse macrophages and acts as an auto-phosphorylating tyrosine kinase. Recombinant JHP0940 protein was found to decrease the viability of RAW264.7 cells (a mouse macrophage cell line) up to 55% within 24. h of co-incubation. The decreased cellular viability was due to apoptosis, which was confirmed by TUNEL assay and Fas expression analysis by flow-cytometry. Further, we found that caspase-1 and IL-1beta were activated upon treatment with JHP0940. These results point towards possible action through the host inflammasome. Our in vitro studies using tyrosine kinase assays further demonstrated that JHP0940 acts as auto-phosphorylating tyrosine kinase and induces pro-inflammatory cytokines in RAW264.7 cells. Upon exposure with JHP0940, these cells secreted IL-1beta, TNF-alpha and IL-6, in a dose- and time-dependent manner, as detected by ELISA and transcript profiling by q-RT-PCR. The pro-inflammatory, pro-apoptotic and other regulatory responses triggered by JHP0940 lead to the assumption of its possible role in inducing chronic inflammation for enhanced bacterial persistence and escape from host innate immune responses by apoptosis of macrophages.
Created from Fastlane, Scopus look-up
Keywords: Apoptosis; H. pylori; Inflammation; JHP0940; Kinases; Plasticity region

Helicobacter pylori controls NLRP3 expression by regulating hsa-miR-223-3p and IL-10 in cultured and primary human immune cells - Suneesh Kumar, Pachathundikandi; Backert, Steffen (Innate Immunity, 2018)

Helicobacter pylori downregulates expression of human β-defensin 1 in the gastric mucosa in a type IV secretion-dependent fashion - Patel, S. R.; Smith, K.; Letley, D. P.; Cook, K. W.; Memon, A. A.; Ingram, R. J. M.; Staples, E.; Backert, Steffen; Zaitoun, A. M.; Atherton, J. C.; Robinson, Karen (Cellular Microbiology, 2013)
Helicobacter pylori establishes a chronic lifelong infection in the human gastric mucosa, which may lead to peptic ulcer disease or gastric adenocarcinoma. The human beta-defensins (hβDs) are antimicrobial peptides, hβD1 being constitutively expressed in the human stomach. We hypothesized that H.pylori may persist, in part, by downregulating gastric hβD1 expression. We measured hβD1 and hβD2 expression in vivo in relation to the presence, density and severity of H.pylori infection, investigated differential effects of H.pylori virulence factors, and studied underlying signalling mechanisms in vitro. Significantly lower hβD1 and higher hβD2 mRNA and protein concentrations were present in gastric biopsies from infected patients. Those patients with higher-level bacterial colonization and inflammation had significantly lower hβD1 expression, but there were no differences in hβD2. H.pylori infection of human gastric epithelial cell lines also downregulated hβD1. Using wild-type strains and isogenic mutants, we showed that a functionalcag pathogenicity island-encoded type IV secretion system induced this downregulation. Treatment with chemical inhibitors or siRNA revealed that H.pylori usurped NF-κB signalling to modulate hβD1 expression. These data indicate that H.pylori downregulates hβD1 expression via NF-κB signalling, and suggest that this may promote bacterial survival and persistence in the gastric niche. © 2013 The Authors.
Created from Fastlane, Scopus look-up

Helicobacter pylori Employs a Unique Basolateral Type IV Secretion Mechanism for CagA Delivery - Tegtmeyer, Nicole; Wessler, Silja; Necchi, Vittorio; Rohde, Manfred; Harrer, Aileen; Rau, Tilman; Asche, Isabell; Böhm, Manja; Loessner, Holger; Figueiredo, Ceu; Naumann, Michael; Palmisano, Ralf; et al. (Cell Host & Microbe, 2017)
The Helicobacter pylori (Hp) type IV secretion system (T4SS) forms needle-like pili, whose binding to the integrin-?1 receptor results in injection of the CagA oncoprotein. However, the apical surface of epithelial cells is exposed to Hp, whereas integrins are basolateral receptors. Hence, the mechanism of CagA delivery into polarized gastric epithelial cells remains enigmatic. Here, we demonstrate that T4SS pilus formation during infection of polarized cells occurs predominantly at basolateral membranes, and not at apical sites. Hp accomplishes this by secreting another bacterial protein, the serine protease HtrA, which opens cell-to-cell junctions through cleaving epithelial junctional proteins including occludin, claudin-8, and E-cadherin. Using a genetic system expressing a peptide inhibitor, we demonstrate that HtrA activity is necessary for paracellular transmigration of Hp across polarized cell monolayers to reach basolateral membranes and inject CagA. The contribution of this unique signaling cascade to Hp pathogenesis is discussed.
EVALuna2:6906

Helicobacter pylori HopH (OipA) and bacterial pathogenicity: Genetic and functional genomic analysis of hopH gene polymorphisms - Dossumbekova, Anar; Prinz, Christian; Mages, Joerg; Lang, Roland; Kusters, Johannes G.; Van Vliet, Arnoud H.M.; Reindl, Wolfgang; Backert, Steffen; Saur, Dieter; Schmid, Roland M.; Rad, Roland (Journal of Infectious Diseases, 2006)
Background. Expression of the Helicobacter pylori outer membrane protein HopH is regulated by phase variation within a CT dinucleotide repeat motif of the hopH gene. Methods. To investigate the importance of HopH for bacterial pathogenicity, we performed a detailed functional genomic and population-based genetic characterization of this contingency locus. Results. Sequencing of hopH in H. pylori strains from 58 patients revealed that the hopH "on" genotype is linked to bacterial virulence determinants, such as the vacAs1, vacAm1, babA2, and, most strongly, cagA genotypes. hopH mutagenesis resulted in reduced bacterial adherence to gastric epithelia in vitro. Complementation of hopH in trans restored the adherence properties of hopH mutants. Although HopH has been previously linked to proinflammatory epithelial signaling, hopH mutagenesis did not alter epithelial interleukin-8 secretion in vitro. Comparative epithelial gene-expression profiling by cDNA microarrays revealed no significant differences between the wild-type-specific and hopH mutant-specific transcriptomes. By contrast, a large set of genes was differentially regulated in a cag pathogenicity island-dependent manner. Conclusion. An in-frame hopH gene may be linked to gastroduodenal diseases because of its association with other virulence factors or increased bacterial adherence and colonization. The strong linkage with cagA indicates that HopH may contribute to the fitness of cagA-positive strains in vivo. © 2006 by the Infectious Diseases Society of America. All rights reserved.
Created from Fastlane, Scopus look-up

Helicobacter pylori HtrA is a new secreted virulence factor that cleaves E-cadherin to disrupt intercellular adhesion - Hoy, Benjamin; Loewer, Martin; Weydig, Christiane; Carra, Gert; Tegtmeyer, Nicole; Geppert, Tim; Schroeder, Peter; Sewald, Norbert; Backert, Steffen; Schneider, Gisbert; Wessler, Silja (EMBO Reports, 2010)
Mammalian and prokaryotic high-temperature requirement A (HtrA) proteins are chaperones and serine proteases with important roles in protein quality control. Here, we describe an entirely new function of HtrA and identify it as a new secreted virulence factor from Helicobacter pylori, which cleaves the ectodomain of the cell-adhesion protein E-cadherin. E-cadherin shedding disrupts epithelial barrier functions allowing H. pylori designed to access the intercellular space. We then designed a small-molecule inhibitor that efficiently blocks HtrA activity, E-cadherin cleavage and intercellular entry of H. pylori. © 2010 European Molecular Biology Organization.
Created from Fastlane, Scopus look-up
Keywords: E-cadherin; H. pylori; HtrA

Helicobacter pylori-Induced Host Cell DNA Damage and Genetics of Gastric Cancer Development - Backert, Steffen; Linz, Bodo; Tegtmeyer, Nicole (Springer Science and Business Media Deutschland GmbH, 2023)
Gastric cancer is a very serious and deadly disease worldwide with about one million new cases every year. Most gastric cancer subtypes are associated with genetic and epigenetic aberrations caused by chromosome instability, microsatellite instability or Epstein-Barr virus infection. Another risk factor is an infection with Helicobacter pylori, which also triggers severe alterations in the host genome. This pathogen expresses an extraordinary repertoire of virulence determinants that take over control of important host cell signaling functions. In fact, H. pylori is a paradigm of persistent infection, chronic inflammation and cellular destruction. In particular, H. pylori profoundly induces chromosomal DNA damage by introducing double-strand breaks (DSBs) followed by genomic instability. DSBs appear in response to oxidative stress and pro-inflammatory transcription during the S-phase of the epithelial cell cycle, which mainly depends on the presence of the bacterial cag pathogenicity island (cagPAI)-encoded type IV secretion system (T4SS). This scenario is closely connected with the T4SS-mediated injection of ADP-glycero-β-D-manno-heptose (ADP-heptose) and oncoprotein CagA. While ADP-heptose links transcription factor NF-κB-induced innate immune signaling with RNA-loop-mediated DNA replication stress and introduction of DSBs, intracellular CagA targets the tumor suppressor BRCA1. The latter scenario promotes BRCAness, a disease characterized by the deficiency of effective DSB repair. In addition, genetic studies of patients demonstrated the presence of gastric cancer-associated single nucleotide polymorphisms (SNPs) in immune-regulatory and other genes as well as specific pathogenic germline variants in several crucial genes involved in homologous recombination and DNA repair, all of which are connected to H. pylori infection. Here we review the molecular mechanisms leading to chromosomal DNA damage and specific genetic aberrations in the presence or absence of H. pylori infection, and discuss their importance in gastric carcinogenesis.
CRIS-Team Scopus Importer:2024-12-16
Keywords: EBV; HtrA; LPS; Oncogenes; Tumor suppressors

Helicobacter pylori-induced posttranscriptional regulation of H-K-ATPase α-subunit gene expression by miRNA - Zhang, Yong-Mei; Noto, Jennifer M.; Hammond, Charles E.; Barth, Jeremy L.; Argraves, W. Scott; Backert, Steffen; Peek, Richard M.; Smolka, Adam J. (American Journal of Physiology-Gastrointestinal and Liver Physiology, 2014)
Acute Helicobacter pylori infection of gastric epithelial cells induces CagA oncoprotein- and peptidoglycan (SLT)-dependent mobilization of NF-κB p50 homodimers that bind to H-K-ATPase α-subunit (HKα) promoter and repress HKα gene transcription. This process may facilitate gastric H. pylori colonization by induction of transient hypochlorhydria. We hypothesized that H. pylori also regulates HKα expression posttranscriptionally by miRNA interaction with HKα mRNA. In silico analysis of the HKα 3′ untranslated region (UTR) identified miR-1289 as a highly conserved putative HKα-regulatory miRNA. H. pylori infection of AGS cells transfected with HKα 3′ UTR-Luc reporter construct repressed luciferase activity by 70%, whereas ΔcagA or Δslt H. pylori infections partially abrogated repression. Transfection of AGS cells expressing HKα 3′ UTR-Luc construct with an oligoribonucleotide mimetic of miR-1289 induced maximal repression (54%) of UTR activity within 30 min; UTR activity was unchanged by nontargeting siRNA transfection. Gastric biopsies from patients infected with cagA+ H. pylori showed a significant increase in miR-1289 expression compared with uninfected patients or those infected with cagA- H. pylori. Finally, miR-1289 expression was necessary and sufficient to attenuate biopsy HKα protein expression in the absence of infection. Taken together, these data indicate that miR-1289 is upregulated by H. pylori in a CagA- and SLT-dependent manner and targets HKα 3′ UTR, affecting HKα mRNA translation. The sensitivity of HKα mRNA 3′ UTR to binding of miR-1289 identifies a novel regulatory mechanism of gastric acid secretion and offers new insights into mechanisms underlying transient H. pylori-induced hypochlorhydria. © 2014 the American Physiological Society.
Created from Fastlane, Scopus look-up
Keywords: H; H-K-ATPase; MicroRNA; Proton pump; Pylori; Regulation acid secretion

Helicobacter pylori induce neutrophil transendothelial migration: Role of the bacterial HP-NAP - Brisslert, Mikael; Enarsson, Karin; Lundin, Samuel; Karlsson, Anna; Kusters, Johannes G.; Svennerholm, Ann-Mari; Backert, Steffen; Quiding-Järbrink, Marianne (FEMS Microbiology Letters, 2005)
Continuous recruitment of neutrophils into the inflamed gastric mucosal tissue is a hallmark of Helicobacter pylori infection in humans. In this study, we examined the ability of H. pylori to induce transendothelial migration of neutrophils using a transwell system consisting of a cultured monolayer of human endothelial cells as barrier between two chambers. We showed for the first time that live H. pylori, but not formalin-killed bacteria, induced a significantly increased transendothelial migration of neutrophils. H. pylori conditioned culture medium also induced significantly increased transendothelial migration, whereas heat-inactivated culture filtrates had no effect, suggesting that the chemotactic factor was proteinaceous. Depletion of H. pylori-neutrophil activating protein (HP-NAP) from the culture filtrates resulted in significant reduction of the transmigration. Culture filtrates from isogenic HP-NAP deficient mutant bacteria also induced significantly less neutrophil migration than culture filtrates obtained from wild-type bacteria. HP-NAP did not induce endothelial cell activation, suggesting that HP-NAP acts directly on the neutrophils. In conclusion, our results demonstrate that secreted HP-NAP is one of the factors resulting in H. pylori induced neutrophil transendothelial migration. We propose that HP-NAP contributes to the continuous recruitment of neutrophils to the gastric mucosa of H. pylori infected individuals. © 2005 Federation of European Microbiological Societies. Published by Elsevier B.V. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Endothelial cells; Helicobacter pylori; HP-NAP; Inflammation; Transmigration

Helicobacter pylori induces AGS cell motility and elongation via independent signaling pathways - Moese, Stefan; Selbach, Matthias; Kwok, Terry; Brinkmann, Volker; König, Wolfgang; Meyer, Thomas F.; Backert, Steffen (Infection and Immunity, 2004)
Helicobacter pylori induces motogenic and cytoskeletal responses in gastric epithelial cells. We demonstrate that these responses can be induced via independent signaling pathways that often occur in parallel. The cag pathogenicity island appears to be nonessential for induction of motility, whereas the elongation phenotype depends on translocation and phosphorylation of CagA.
Created from Fastlane, Scopus look-up

Helicobacter pylori induces transendothelial migration of activated memory T cells - Enarsson, Karin; Brisslert, Mikael; Backert, Steffen; Quiding-Järbrink, Marianne (Infection and Immunity, 2005)
Helicobacter pylori infection is associated with pronounced infiltration of granulocytes and lymphocytes into the gastric mucosa, resulting in active chronic gastritis that may develop into duodenal ulcer disease or gastric adenocarcinoma. Infiltrating T cells play a major role in the pathology of these diseases, but the signals involved in recruitment of T cells from blood to H. pylori-infected tissues are not well understood. We therefore examined H. pylori-induced T-cell transendothelial migration (TEM). The Transwell system, employing a monolayer of human umbilical vein endothelial cells, was used as a model to study TEM. H. pylori induced a significant T-cell migration, compared to spontaneous migration. CD4+ and CD8+ T cells migrated to the same extent in response to H. pylori, whereas there was significantly larger transmigration of memory T cells compared to naive T cells. Both H. pylori culture filtrate and urease induced migration, and the presence of the H. pylori cag pathogenicity island increased TEM. T-cell TEM was mediated by LFA-1-ICAM-1 interactions in accordance with an increased ICAM-1 expression on the endothelial cells after contact with H. pylori. Migrating T cells had increased expression of activation marker CD69 and chemokine receptors CXCR3, CCR4, and CCR9. Furthermore, T cells migrating in response to H. pylori secreted Th1 but not Th2 cytokines upon stimulation. In conclusion, our data indicate that live H. pylori and its secreted products contribute to T-cell recruitment to the gastric mucosa and that the responding T cells have an activated memory Th1 phenotype.
Created from Fastlane, Scopus look-up

Helicobacter pylori infection of AZ-521 cells reveals a type IV secretion defect and VacA-independent CagA phosphorylation - Tegtmeyer, Nicole; Backert, Steffen (Disease Models & Mechanisms, 2017)

Helicobacter pylori inhibits phagocytosis by professional phagocytes involving type IV secretion components. - Backert, Steffen; Ramarao, N.; Gray-Owen, S.D.; Meyer, Thomas F. (Molecular Microbiology, 2000)
Gastric infections by Helicobacter pylori are characteristically associated with an intense inflammation and infiltration of mainly polymorphonuclear lymphocytes (PMNs) and monocytes. The inflammatory response by infiltrated immune cells appears to be a primary cause of the damage to surface epithelial layers and may eventually result in gastritis, peptic ulcer, gastric cancer and/or MALT-associated gastric lymphoma. Our analysis of the interaction between H. pylori and PMNs and monocytes revealed that H. pylori inhibits its own uptake by these professional phagocytes. To some degree, this effect resembles antiphagocytosis by Yersinia enterocolitica. Increasing numbers of bacteria associated per cell are more efficient at blocking their own engulfment. In H. pylori, bacterial protein synthesis is necessary to block phagocytic uptake, as shown by the time and concentration dependence of the bacteriostatic protein synthesis inhibitor chloramphenicol. Furthermore, H. pylori appears broadly to inhibit the phagocytic function of monocytes and PMNs, as infection with H. pylori abrogates the phagocytes' ability to engulf latex beads or adherent Neisseria gonorrhoeae cells. This antiphagocytic phenotype depends on distinct virulence (vir) genes, such as virB7 and virB11, encoding core components of a putative type IV secretion apparatus. Our data indicate that H. pylori exhibits an antiphagocytic activity that may play an essential role in the immune escape of this persistent pathogen.

Helicobacter pylori in Human Diseases Advances in Microbiology, Infectious Diseases and Public Health Volume 11 Preface - Kamiya, Shigeru; Backert, Steffen (Advances in Experimental Medicine and Biology, 2019)
CRIS-Team WoS Importer:2020-06-16

Helicobacter pylori in human diseases - Kamiyama, Satoshi; Backert, Steffen (Springer, 2019)

Helicobacter pylori outer membrane proteins and gastric inflammation - Dossumbekova, Anar; Prinz, Christian; Gerhard, Markus; Brenner, L; Backert, Steffen; Kusters, Johannes G.; Schmid, Roland M.; Rad, Roland (Gut, 2006)

Helicobacter pylori research: From bench to bedside - Backert, Steffen; Yamaoka, Yoshio (Springer, 2016)

Helicobacter pylori type IV secretion, host cell signalling and vaccine development. - Backert, Steffen; Churin, Y.; Meyer, Thomas F. (Keio Journal of Medicine, 2002)
Helicobacter pylori is a bacterial pathogen specialised to colonise and persist the gastric mucosa and to cause severe gastroduodenal disease. A major disease-associated bacterial component is a type IV secretion system (TFSS) encoded by the cytotoxin-associated genes pathogenicity island (cagPAI). Among the multiple responses in H. pylori-infected epithelial cells, the induction of proinflammatory cytokines and chemokines, cell spreading and motility associated with the "hum mingbird" phenotype appear strictly dependent on the functional transporter complex in the cagPAI. H. pylori is also capable of occasionally entering epithelial cells and manipulates the host immune system for immune evasion. Attached bacteria actively translocate the CagA protein into epithelial cells by a TFSS-dependent process and translocated CagA undergoes tyrosine phosphorylation in the carboxy terminal EPIYA sequence repeat motif (Y-972) by kinases of the Src family. Furthermore, we have identified a novel TFSS in H. pylori involved in horizontal DNA-transfer. Host cell signalling events and cellular phenotypes provoked by the cagPAI, the investigation of mechanisms related to gastric cancer as well as the development of a Salmonella based live recombinant vaccine are in the focus of additional departmental activities.

Helicobacter pylori virulence factors affecting gastric proton pump expression and acid secretion - Hammond, Charles E.; Beeson, Craig; Suarez, Giovanni; Peek, Richard M.; Backert, Steffen; Smolka, Adam J. (American Journal of Physiology-Gastrointestinal and Liver Physiology, 2015)
Acute Helicobacter pylori infection of gastric epithelial cells and human gastric biopsies represses H, KATPase α subunit (HKα) gene expression and inhibits acid secretion, causing transient hypochlorhydria and supporting gastric H. pylori colonization. Infection by H. pylori strains deficient in the cag pathogenicity island (cag PAI) genes cagL, cagE, or cagM, which do not transfer CagA into host cells or induce interleukin-8 secretion, does not inhibit HKα expression, nor does a cagA-deficient strain that induces IL-8. To test the hypothesis that virulence factors other than those mediating CagA translocation or IL-8 induction participate in HKα repression by activating NF-κB, AGS cells transfected with HKα promoter-Luc reporter constructs containing an intact or mutated NF-κB binding site were infected with wild-type H. pylori strain 7.13, isogenic mutants lacking cag PAI genes responsible for CagA translocation and/or IL-8 induction (cagA, cagκζ, cagε, cagZ, and cagβ), or deficient in genes encoding two peptidoglycan hydrolases (slt and cagγ). H. pylori-induced AGS cell HKα promoter activities, translocated CagA, and IL-8 secretion were measured by luminometry, immunoblotting, and ELISA, respectively. Human gastric biopsy acid secretion was measured by microphysiometry. Taken together, the data showed that HKα repression is independent of IL-8 expression, and that CagA translocation together with H. pylori transglycosylases encoded by slt and cagγ participate in NF-κB-dependent HKα repression and acid inhibition. The findings are significant because H. pylori factors other than CagA and IL-8 secretion are now implicated in transient hypochlorhydria which facilitates gastric colonization and potential triggering of epithelial progression to neoplasia.
Created from Fastlane, Scopus look-up
Keywords: Acid secretion; Helicobacter pylori; Proton pump; Type 4 secretory system; Virulence factors

Helicobacter urease-induced activation of the TLR2/NLRP3/IL-18 axis protects against asthma - Koch, Katrin N.; Hartung, Mara L.; Urban, Sabine; Kyburz, Andreas; Bahlmann, Anna S.; Lind, Judith; Backert, Steffen; Taube, Christian; Mueller, Anne (Journal of Clinical Investigation, 2015)
Inflammasome activation and caspase-1-dependent (CASP1-dependent) processing and secretion of IL-1β and IL-18 are critical events at the interface of the bacterial pathogen Helicobacter pylori with its host. Whereas IL-1β promotes Th1 and Th17 responses and gastric immunopathology, IL-18 is required for Treg differentiation, H. pylori persistence, and protection against allergic asthma, which is a hallmark of H. pylori-infected mice and humans. Here, we show that inflammasome activation in DCs requires the cytoplasmic sensor NLRP3 as well as induction of TLR2 signaling by H. pylori. Screening of an H. pylori transposon mutant library revealed that pro-IL-1β expression is induced by LPS from H. pylori, while the urease B subunit (UreB) is required for NLRP3 inflammasome licensing. UreB activates the TLR2-dependent expression of NLRP3, which represents a rate-limiting step in NLRP3 inflammasome assembly. ureB-deficient H. pylori mutants were defective for CASP1 activation in murine bone marrow-derived DCs, splenic DCs, and human blood-derived DCs. Despite colonizing the murine stomach, ureB mutants failed to induce IL-1β and IL-18 secretion and to promote Treg responses. Unlike WT H. pylori, ureB mutants were incapable of conferring protection against allergen-induced asthma in murine models. Together, these results indicate that the TLR2/NLRP3/CASP1/IL-18 axis is critical to H. pylori-specific immune regulation.
Created from Fastlane, Scopus look-up

Heptose 1,7-Bisphosphate Directed TIFA Oligomerization: A Novel PAMP-Recognizing Signaling Platform in the Control of Bacterial Infections. - Suneesh Kumar, Pachathundikandi; Backert, Steffen (Gastroenterology International, 2018)

High content, size and distribution of single-stranded DNA in the mitochondria of Chenopodium album (L.) - Backert, Steffen; Lurz, Rudi; Oyarzabal, Omar A.; Börner, Thomas (Plant Molecular Biology, 1997)

Host cell interactome of tyrosine-phosphorylated bacterial proteins. - Selbach, Matthias; Paul, Florian Ernst; Brandt, Sabine; Guye, Patrick; Daumke, Oliver; Backert, Steffen; Dehio, Christoph; Mann, Matthias (Cell Host & Microbe, 2009)
Selective interactions between tyrosine-phosphorylated proteins and their cognate, SH2-domain containing ligands play key roles in mammalian signal transduction. Several bacterial pathogens use secretion systems to inject tyrosine kinase substrates into host cells. Upon phosphorylation, these effector proteins recruit cellular binding partners to manipulate host cell functions. So far, only a few interaction partners have been identified. Here we report the results of a proteomic screen to systematically identify binding partners of all known tyrosine-phosphorylated bacterial effectors by high-resolution mass spectrometry. We identified 39 host interactions, all mediated by SH2 domains, including four of the five already known interaction partners. Individual phosphorylation sites recruited a surprisingly high number of cellular interaction partners suggesting that individual phosphorylation sites can interfere with multiple cellular signaling pathways. Collectively, our results indicate that tyrosine-phosphorylation sites of bacterial effector proteins have evolved as versatile interaction modules that can recruit a rich repertoire of cellular SH2 domains.

Host epithelial cell invasion by Campylobacter jejuni: trigger or zipper mechanism? - Croinin, Tadhg O.; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2012)
Campylobacter jejuni, a spiral-shaped Gram-negative pathogen, is a highly frequent cause of gastrointestinal foodborne illness in humans worldwide. Clinical outcome of C. jejuni infections ranges from mild to severe diarrheal disease, and some other complications including reactive arthritis and Guillain-Barré syndrome. This review article highlights various C. jejuni pathogenicity factors, host cell determinants, and proposed signaling mechanisms involved in human host cell invasion and their potential role in the development of C. jejuni-mediated disease. A model is presented which outlines the various important interactions of C. jejuni with the intestinal epithelium, and we discuss the pro's and con's for the "zipper" over the "trigger" mechanism of invasion. Future work should clarify the contradictory role of some previously identified factors, and should identify and characterize novel virulence determinants, which are crucial to provide fresh insights into the diversity of strategies employed by this pathogen to cause disease.
Created from Fastlane, Scopus look-up

Host-pathogen interaction: How EHEC influence the actin cytoskeleton of the host cell Wirt-Pathogen-Interaktion wie EHEC das Aktinzytoskelett der Wirtszelle beeinflussen - Stradal, Theresia E.B.; Backert, Steffen (BioSpektrum, 2010)
Two types of pathogenic Escherichia coli (EPEC and EHEC) firmly attach to gut epithelial cells and induce pedestals, which are actin-rich structures protruding beneath attached bacteria. The different strategies of EPEC and EHEC to induce pedestals are discussed.
CRIS-Team Scopus Importer:2020-09-18

How Helicobacter pylori infection controls gastric acid secretion - Smolka, Adam J.; Backert, Steffen (Journal of Gastroenterology, 2012)
Infection of the human stomach mucosa by Helicobacter pylori induces strong inflammatory responses and a transitory hypochlorhydria which can progress in ∼2 % of patients to atrophic gastritis, dysplasia, or gastric adenocarcinoma. H. pylori infection of gastric biopsies or cultured gastric epithelial cells in vitro represses the activity of endogenous or transfected promoter of the alpha-subunit (HKα) of gastric H,K-adenosine triphosphatase (H,K-ATPase), the parietal cell enzyme mediating acid secretion. Some mechanistic details of H. pylori-mediated repression of HKα and ensuing hypochlorhydria have been recently elucidated. H. pylori strains expressing a type IV secretion system (T4SS) encoded by the cag pathogenicity island are known to upregulate the transcription factor nuclear factor (NF)-κB. The NF-κB-binding regions in the HKα promoter were identified and shown to repress its transcriptional activity. Interaction studies have indicated that although active phosphorylated NF-κB p65 is present in infected cells, an NF-κB p50/p65 heterodimeric complex fails to bind to the HKα promoter. Point mutations at-159 and-161 bp in the HKα promoter NF-κB binding sequence prevent the binding of NF-κB p50 and prevent H. pylori repression of point-mutated HKα promoter activity. The T4SS factors CagL, CagE, CagM, and possibly CagA and the lytic transglycosylase Slt, are mechanistically involved in NF-κB activation and repression of HKα transcription. CagL, a T4SS pilus component, binds to the integrin α 5β 1 to mediate translocation of virulence factors into the host cell and initiate signaling. During acute H. pylori infection, CagL dissociates ADAM 17 (a disintegrin and a metalloprotease 17) from the integrin α 5β 1 complex and stimulates ADAM17-dependent release of heparin-binding epidermal growth factor (HB-EGF), EGF receptor (EGFR) stimulation, ERK1/2 kinase activation, and NF-κB-mediated repression of HKα. These studies suggest that H. pylori inhibits HKα gene expression by an integrin α 5β 1 → ADAM17 → HBEGF → EGFR → ERK1/2 → NF-κB pathway mediating NF-κB p50 homodimer binding to the HKα promoter. Here we review the molecular basis and recent progress of this novel pathogen-dependent mechanism of H,K-ATPase inhibition, which contributes significantly to our current understanding of H. pylori pathophysiology. © 2012 Springer.
Created from Fastlane, Scopus look-up
Keywords: ADAM17; Cag pathogenicity island; EGFR; ERK1/2; Gastric adenocarcinoma; HB-EGF; Helicobacter pylori; HKα-ATPase; Hypochlorhydria; Integrin α; Parietal cells; Transcription factor NF-jB; Type IV secretion system

How many protein molecules are secreted by single Helicobacter pylori cells: Quantification of serine protease HtrA - Neddermann, Matthias; Backert, Steffen (Cellular Microbiology, 2019)
Infection with Helicobacter pylori represents a major risk for developing peptic ulcer disease, gastric adenocarcinoma, and various other gastric and nongastric sicknesses. A series of H. pylori virulence factors can be secreted into the cell culture supernatant, and the secretome contains more than 100 different proteins. However, the quantities of proteins secreted by the bacteria over time are unknown. One of these factors is the serine protease high-temperature requirement A (HtrA), encoded by an essential bifunctional gene with crucial intracellular and extracellular activities. We have demonstrated recently that secreted HtrA can cleave off the ectodomains of the tight junction proteins occludin and claudin-8, as well as of the tumour suppressor and adherens junction protein E-cadherin on polarised gastric epithelial cells. The exact mechanism of secretion and the quantity of secreted HtrA, however, have not been studied in detail. Here, we applied protein purification and quantitative Western blotting to determine the number of HtrA molecules secreted by H. pylori cells in liquid culture during a time course. Over a period of 8 hr, actively dividing bacteria secreted HtrA at a similar rate, on average about 9,600 HtrA molecules per cell. We determined minor variation over time corresponding to 9,931 ± 1,768 at an OD600 of 0.4 after 2 hr, 9,403 ± 2,356 2 hr later, and 9,644 ± 2,067 molecules per cell after 8 hr of culturing, when the culture had reached an OD600 of 0.8. This is the first report on the quantification of a secreted virulence protein from the important gastric pathogen H. pylori. Because HtrA has been considered as a promising new target for antibacterial therapy, knowledge about secreted protein quantities is crucial for optimising corresponding treatment regimes.
CRIS-Team Scopus Importer:2019-06-18
Keywords: Helicobacter pylori; secretion; serine protease HtrA; signalling; VacA

H. pylori-Induced DNA Strand Breaks Are Introduced by Nucleotide Excision Repair Endonucleases and Promote NF-κB Target Gene Expression - Hartung, Mara L.; Gruber, Dorothea C.; Koch, Katrin N.; Grueter, Livia; Rehrauer, Hubert; Tegtmeyer, Nicole; Backert, Steffen; Mueller, Anne (Cell Reports, 2015)
The human bacterial pathogen Helicobacter pylori exhibits genotoxic properties that promote gastric carcinogenesis. H. pylori introduces DNA double strand breaks (DSBs) in epithelial cells that trigger host cell DNA repair efforts. Here, we show that H. pylori-induced DSBs are repaired via error-prone, potentially mutagenic non-homologous end-joining. A genome-wide screen for factors contributing to DSB induction revealed a critical role for the H. pylori type IV secretion system (T4SS). Inhibition of transcription, as well as NF-κB/RelA-specific RNAi, abrogates DSB formation. DSB induction further requires β1-integrin signaling. DSBs are introduced by the nucleotide excision repair endonucleases XPF and XPG, which, together with RelA, are recruited to chromatin in a highly coordinated, T4SS-dependent manner. Interestingly, XPF/XPG-mediated DNA DSBs promote NF-κB target gene transactivation and host cell survival. In summary, H. pylori induces XPF/XPG-mediated DNA damage through activation of the T4SS/β1-integrin signaling axis, which promotes NF-κB target gene expression and host cell survival.
Created from Fastlane, Scopus look-up

HtrA-dependent adherence and invasion of Campylobacter jejuni in human vs. avian cells - Simson, Daniel; Böhm, Manja; Backert, Steffen (Letters in Applied Microbiology, 2020)

Human Campylobacteriosis-A Serious Infectious Threat in a One Health Perspective - Heimesaat, Markus M.; Backert, Steffen; Alter, Thomas; Bereswill, Stefan (Current Topics in Microbiology and Immunology, 2021)
Zoonotic Campylobacter species-mainly C. jejuni and C. coli-are major causes of food-borne bacterial infectious gastroenteritis worldwide. Symptoms of intestinal campylobacteriosis include abdominal pain, diarrhea and fever. The clinical course of enteritis is generally self-limiting, but some infected individuals develop severe post-infectious sequelae including autoimmune disorders affecting the nervous system, the joints and the intestinal tract. Moreover, in immunocompromised individuals, systemic spread of the pathogens may trigger diseases of the circulatory system and septicemia. The socioeconomic costs associated with Campylobacter infections have been calculated to several billion dollars annually. Poultry meat products represent major sources of human infections. Thus, a "One World-One Health" approach with collective efforts of public health authorities, veterinarians, clinicians, researchers and politicians is required to reduce the burden of campylobacteriosis. Innovative intervention regimes for the prevention of Campylobacter contaminations along the food chain include improvements of information distribution to strengthen hygiene measures for agricultural remediation. Given that elimination of Campylobacter from the food production chains is not feasible, novel intervention strategies fortify both the reduction of pathogen contamination in food production and the treatment of the associated diseases in humans. This review summarizes some current trends in the combat of Campylobacter infections including the combination of public health and veterinary preventive approaches with consumer education. The "One World-One Health" perspective is completed by clinical aspects and molecular concepts of human campylobacteriosis offering innovative treatment options supported by novel murine infection models that are based on the essential role of innate immune activation by bacterial endotoxins.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Campylobacter jejuni; Campylobacteriosis; Infection models; Infection prevention; One health

Human campylobacteriosis - Backert, Steffen; Tegtmeyer, Nicole; Croinin, Tadhg O.; Böhm, Manja; Heimesaat, Markus M. (Campylobacter: Features, Detection, and Prevention of Foodborne Disease, 2017)
Campylobacter subspecies represent a highly frequent cause of foodborne gastrointestinal (GI) illnesses in humans worldwide. The incidence and prevalence of campylobacteriosis due to infection with Campylobacter jejuni has increased over the past decades, both in developed and developing countries. The clinical outcome of C. jejuni infection ranges from mild to severe diarrheal disease, and some postinfection sequelae, including Guillain-Barré syndrome, reactive arthritis, and others. Poultry and poultry farms represent a major reservoir and source of transmission of C. jejuni strains to humans. Other risk factors of outbreaks include the consumption of contaminated meat, milk, vegetables, and water as well as direct contact with live animals or surface water. This Chapter highlights the various known routes of C. jejuni transmission and infection, bacterial, and host virulence determinants as well as their proposed role in the development of C. jejuni-mediated disease.
CRIS-Team Scopus Importer:2020-09-18
Keywords: Campylobacteriosis; Guillain-Barré syndrome; Inflammatory bowel disease; Irritable bowel syndrome; Outbreak; Reactive arthritis; Reiter's syndrome

Identification of a tyrosine-phosphorylated 35 kDa carboxy-terminal fragment (p35CagA) of the Helicobacter pylori CagA protein in phagocytic cells: processing or breakage? - Moese, Stefan; Selbach, Matthias; Zimny-Arndt, Ursula; Jungblut, Peter R.; Meyer, Thomas F.; Backert, Steffen (Proteomics, 2001)
Helicobacter pylori is a very common bacterial pathogen that causes gastric disease by inducing the infiltration of immune cells as an initial event. Virulent H. pylori strains express a type IV secretion system composed of several virulence (Vir) proteins encoded by the cag pathogenicity island (cag PAI). During infection of phagocytic cells (U937, Josk-M and J774A.1) we have detected a de novo tyrosine-phosphorylated protein (p35p-Tyr) with sizes of 30 kDa, 38 kDa or 40 kDa, depending on the H. pylori strain. p35p-Tyr occurrence required functional virB4, virB7, virB10, virB11, virD4 and cagA (cytotoxin-associated gene A) genes encoded by the cag PAI suggesting that p35p-Tyr is a bacterial protein of variable size. We have biochemically purified p35p-Tyr from infected U937 cells. Tryptic peptides of p35p-Tyr determined by matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS) identified the carboxy (C)-terminal part of the H. pylori CagA protein. Subsequent analysis by two-dimensional electrophoresis (2-DE) and immunoblotting using anti-CagA antibodies revealed the presence of three stable CagA protein species in phagocytes: (i) 130-140 kDa full-length CagA (p135CagA), (ii) a 100-105 kDa fragment (p100CagA) and (iii) a 30-40 kDa fragment (p35CagA). Unlike p135CagA, p35CagA and p100CagA were also detected in much lower amounts in H. pylori without host cell contact. Therefore, breakage or processing leads to the production of p35CagA and p100CagA, a process that is enhanced after translocation into host cells. MALDI-MS data and the isoelectric point determined by both 2-DE and sequence analysis suggested that p35CagA represents the C-terminal part of CagA and p100CagA corresponds to the remaining amino (N)-terminal fragment. The possible function of CagA in host signal transduction and development of gastric disease is discussed.

Identification of E-cadherin signature motifs functioning as cleavage sites for Helicobacter pylori HtrA - Schmidt, Thomas P.; Perna, Anna M.; Fugmann, Tim; Böhm, Manja; Hiss, Jan; Haller, Sarah; Goetz, Camilla; Tegtmeyer, Nicole; Hoy, Benjamin; Rau, Tilman; Neri, Dario; Backert, Steffen; et al. (Scientific Reports, 2016)
The cell adhesion protein and tumour suppressor E-cadherin exhibits important functions in the prevention of gastric cancer. As a class-I carcinogen, Helicobacter pylori (H. pylori) has developed a unique strategy to interfere with E-cadherin functions. In previous studies, we have demonstrated that H. pylori secretes the protease high temperature requirement A (HtrA) which cleaves off the E-cadherin ectodomain (NTF) on epithelial cells. This opens cell-to-cell junctions, allowing bacterial transmigration across the polarised epithelium. Here, we investigated the molecular mechanism of the HtrA-E-cadherin interaction and identified E-cadherin cleavage sites for HtrA. Mass-spectrometry-based proteomics and Edman degradation revealed three signature motifs containing the [VITA]-[VITA]-x-x-D-[DN] sequence pattern, which were preferentially cleaved by HtrA. Based on these sites, we developed a substrate-derived peptide inhibitor that selectively bound and inhibited HtrA, thereby blocking transmigration of H. pylori. The discovery of HtrA-targeted signature sites might further explain why we detected a stable 90 kDa NTF fragment during H. pylori infection, but also additional E-cadherin fragments ranging from 105 kDa to 48 kDa in in vitro cleavage experiments. In conclusion, HtrA targets E-cadherin signature sites that are accessible in in vitro reactions, but might be partially masked on epithelial cells through functional homophilic E-cadherin interactions.
EVALuna2:6912

Immune Cell Signaling by Helicobacter pylori: Impact on Gastric Pathology - Blaser, Nicole; Backert, Steffen; Suneesh Kumar, Pachathundikandi (Advances in Experimental Medicine and Biology, 2019)
Helicobacter pylori represents a highly successful colonizer of the human stomach. Infections with this Gram-negative bacterium can persist lifelong, and although in the majority of cases colonization is asymptomatic, it can trigger pathologies ranging from chronic gastritis and peptic ulceration to gastric cancer. The interaction of the bacteria with the human host modulates immune responses in different ways to enable bacterial survival and persistence. H. pylori uses various pathogenicity-associated factors such as VacA, NapA, CGT, GGT, lipopolysaccharide, peptidoglycan, heptose 1,7-bisphosphate, ADP-heptose, cholesterol glucosides, urease and a type IV secretion system for controlling immune signaling and cellular functions. It appears that H. pylori manipulates multiple extracellular immune receptors such as integrin-β2 (CD18), EGFR, CD74, CD300E, DC-SIGN, MINCLE, TRPM2, T-cell and Toll-like receptors as well as a number of intracellular receptors including NLRP3, NOD1, NOD2, TIFA and ALPK1. Consequently, downstream signaling pathways are hijacked, inducing tolerogenic dendritic cells, inhibiting effector T cell responses and changing the gastrointestinal microbiota. Here, we discuss in detail the interplay of bacterial factors with multiple immuno-regulatory cells and summarize the main immune evasion and persistence strategies employed by H. pylori.
CRIS-Team Scopus Importer:2019-11-01
Keywords: Inflammasome; PAMP; PRR; T4SS; TLR

Immunopathological properties of the Campylobacter jejuni flagellins and the adhesin CadF as assessed in a clinical murine infection model - Schmidt, Anna Maria; Escher, Ulrike; Mousavi, Soraya; Tegtmeyer, Nicole; Böhm, Manja; Backert, Steffen; Bereswill, Stefan; Heimesaat, Markus M. (Gut Pathogens, 2019)
Background: Campylobacter jejuni infections constitute serious threats to human health with increasing prevalences worldwide. Our knowledge regarding the molecular mechanisms underlying host-pathogen interactions is still limited. Our group has established a clinical C. jejuni infection model based on abiotic IL-10 -/- mice mimicking key features of human campylobacteriosis. In order to further validate this model for unraveling pathogen-host interactions mounting in acute disease, we here surveyed the immunopathological features of the important C. jejuni virulence factors FlaA and FlaB and the major adhesin CadF (Campylobacter adhesin to fibronectin), which play a role in bacterial motility, protein secretion and adhesion, respectively. Methods and results: Therefore, abiotic IL-10 -/- mice were perorally infected with C. jejuni strain 81-176 (WT) or with its isogenic flaA/B (ΔflaA/B) or cadF (ΔcadF) deletion mutants. Cultural analyses revealed that WT and ΔcadF but not ΔflaA/B bacteria stably colonized the stomach, duodenum and ileum, whereas all three strains were present in the colon at comparably high loads on day 6 post-infection. Remarkably, despite high colonic colonization densities, murine infection with the ΔflaA/B strain did not result in overt campylobacteriosis, whereas mice infected with ΔcadF or WT were suffering from acute enterocolitis at day 6 post-infection. These symptoms coincided with pronounced pro-inflammatory immune responses, not only in the intestinal tract, but also in other organs such as the liver and kidneys and were accompanied with systemic inflammatory responses as indicated by increased serum MCP-1 concentrations following C. jejuni ΔcadF or WT, but not ΔflaA/B strain infection. Conclusion: For the first time, our observations revealed that the C. jejuni flagellins A/B, but not adhesion mediated by CadF, are essential for inducing murine campylobacteriosis. Furthermore, the secondary abiotic IL-10 -/- infection model has been proven suitable not only for detailed investigations of immunological aspects of campylobacteriosis, but also for differential analyses of the roles of distinct C. jejuni virulence factors in induction and progression of disease.
CRIS-Team Scopus Importer:2019-05-28
Keywords: Bacterial translocation; CadF; Campylobacter jejuni; Extra-intestinal immune responses; FlaA/B; Flagellin; Host-pathogen-interaction; IL-10; Intestinal immunopathology; Pro-inflammatory immune responses; Secondary abiotic (gnotobiotic) mice; Systemic immune responses

Importance of cortactin for efficient epithelial NF-kappa B activation by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa, but not Campylobacter spp. - Tegtmeyer-Backert, Nicole; Soltan Esmaeili, Delara; Sharafutdinov, Irshad; Knorr, Jakob; Naumann, Michael; Alter, Thomas; Backert, Steffen (European Journal of Microbiology and Immunology, 2021)
Transcription factors of the nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kappa B) family control important signaling pathways in the regulation of the host innate immune system. Various bacterial pathogens in the human gastrointestinal tract induce NF-kappa B activity and provoke pro-inflammatory signaling events in infected epithelial cells. NF-kappa B activation requires the phosphorylation-dependent proteolysis of inhibitor of kappa B (I kappa B) molecules including the NF-kappa B precursors through ubiquitin-mediated proteolysis. The canonical NF-kappa B pathway merges on I kappa B kinases (IKKs), which are required for signal transduction. Using CRISPR-Cas9 technology, secreted embryonic alkaline phosphatase (SEAP) reporter assays and cytokine enzyme-linked immunosorbent assay (ELISA), we demonstrate that the actin-binding protein cortactin is involved in NF-kappa B activation and subsequent interleukin-8 (IL-8) production upon infection by Helicobacter pylori, Salmonella enterica and Pseudomonas aeruginosa. Our data indicate that cortactin is needed to efficiently activate the c-Sarcoma (Src) kinase, which can positively stimulate NF-kappa B during infection. In contrast, cortactin is not involved in activation of NF-kappa B and IL-8 expression upon infection with Campylobacter species C. jejuni, C. coli or C. consisus, suggesting that Campylobacter species pluralis (spp.) induce a different signaling pathway upstream of cortactin to trigger the innate immune response.
CRIS-Team WoS Importer:2022-02-25
Keywords: ADP-heptose; NF-ĸB; Helicobacter pylori; T4SS; cortactin; Src; interleukin-8; inflammation

Importance of EGF receptor, HER2/Neu and Erk1/2 kinase signalling for host cell elongation and scattering induced by the Helicobacter pylori CagA protein: Antagonistic effects of the vacuolating cytotoxin VacA - Tegtmeyer, Nicole; Zabler, Dana; Schmidt, Diana; Hartig, Roland; Brandt, Sabine; Backert, Steffen (Cellular Microbiology, 2009)
Helicobacter pylori is the causative agent of gastric pathologies ranging from chronic gastritis to peptic ulcers and even cancer. Virulent strains carrying both the cag pathogenicity island (cag PAI) and the vacuolating cytotoxin VacA are key players in disease development. The ca gPAI encodes a type IV secretion system (T4SS) which forms a pilus for injection of the CagA protein into gastric epithelial cells. Injected CagA undergoes tyrosine phosphorylation and induces actin-cytoskeletal rearrangements involved in host cell scattering and elongation. We show here that the CagA-induced responses can be inhibited in strains expressing highly active VacA. Further investigations revealed that VacA does not interfere with known activities of phosphorylated CagA such as inactivation of Src kinase and cortactin dephosphorylation. Instead, we demonstrate that VacA exhibits inactivating activities on the epidermal growth factor receptor EGFR and HER2/Neu, and subsequently Erk1/2 MAP kinase which are important for cell scattering and elongation. Inactivation of vacA gene, downregulation of the VacA receptor RPTP-α, addition of EGF or expression of constitutive-active MEK1 kinase restored the capability of H.pylori to induce the latter phenotypes. These data demonstrate that VacA can downregulate CagA's effects on epithelial cells, a novel molecular mechanism showing how H.pylori can avoid excessive cellular damage. © 2009 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Importance of two PDZ domains for the proteolytic and chaperone activities of Helicobacter pylori serine protease HtrA - Zarzecka, Urszula; Matkowska, Dorota; Backert, Steffen; Skorko-Glonek, Joanna (Cellular Microbiology, 2020)
The Helicobacter pylori HtrA protein (HtrAHp) is an important virulence factor involved in the infection process by proteolysis of components of the tight (claudin-8 and occludin) and adherens junctions (E-cadherin) between epithelial cells. As a protease and chaperone, HtrAHp is involved in protein quality control, which is particularly important under stress conditions. HtrAHp contains a protease domain and two C-terminal PDZ domains (PDZ1 and PDZ2). In the HtrA protein family, the PDZ domains are proposed to play important roles, including regulation of proteolytic activity. We therefore mutated the PDZ1 and PDZ2 domains in HtrAHp and studied the maintenance of proteolytic activity, assembly and rearrangement of the corresponding oligomeric forms. Our in vitro experiments demonstrated that at least PDZ1 is important for efficient substrate cleavage, while both PDZ domains are dispensable for the chaperone-like activity. However, in living H. pylori cells, only the mutant containing at least PDZ1, but not PDZ2, ensured bacterial growth under stressful conditions. Moreover, we can demonstrate that PDZ1 is crucial for HtrAHp oligomerization. Interestingly, all truncated proteolytically active HtrAHp variants were functional in the in vitro infection assay and caused damage to the E-cadherin-based adherens junctions. These findings provide valuable new insights into the function of HtrAHp in an important pathogen of humans.
CRIS-Team Scopus Importer:2020-12-25
Keywords: chaperone; E-cadherin; Helicobacter pylori; HtrA; oligomerization; PDZ domain; protease; stress endurance

Induction and modulation of inflammatory networks by bacterial protein toxins - Backert, Steffen; König, Wolfgang; König, Brigitte; Arnold, Ralf (The Comprehensive Sourcebook of Bacterial Protein Toxins, 2006)
An understanding of infectious pathobiology also needs to consider the combined action of bacterial toxins in conjunction with the whole microorganism, as well as its soluble exoproducts in a complete system. This may result in altered cellular responses compared to the individual toxin on its own. This chapter focuses on individual pathogenicitiy factors, but also on defined and up to now unresolved disease processes. The complexity of host defense have been described with emphasis on the mucosal system, as well as inflammatory cells and mediators. Today, sophisticated biochemical and genetic tools are being used to elucidate the molecular details surrounding host-pathogen interactions. These studies continue to provide detailed information on basic cellular mechanisms and offer novel avenues of potential chemotherapeutic intervention and even the possibility of introducing beneficial agents into eukaryotic cells. However, bacterial proteins including toxins can enter the cells, they can integrate themselves, and sometimes they abuse eukaryotic signaling mechanisms or deviate the immune response by their mimicry. Although a wide range of microbe-host relation ships can ultimately lead to disease, the two most general strategies used by pathogenic microbes may be described in military terms as "frontal" and "stealth" assaults. © 2006 Elsevier Inc. All rights reserved.
Created from Fastlane, Scopus look-up

Induction of TLR-2 and TLR-5 expression by helicobacter pylori switches cagPAI-dependent signalling leading to the secretion of IL-8 and TNF-α - Pachathundikandi, Suneesh Kumar; Brandt, Sabine; Madassery, Joseph; Backert, Steffen (PLoS ONE, 2011)
Helicobacter pylori is the causative agent for developing gastritis, gastric ulcer, and even gastric cancer. Virulent strains carry the cag pathogenicity island (cagPAI) encoding a type-IV secretion system (T4SS) for injecting the CagA protein. However, mechanisms of sensing this pathogen through Toll-like receptors (TLRs) and downstream signalling pathways in the development of different pathologies are widely unclear. Here, we explored the involvement of TLR-2 and TLR-5 in THP-1 cells and HEK293 cell lines (stably transfected with TLR-2 or TLR-5) during infection with wild-type H. pylori and isogenic cagPAI mutants. H. pylori triggered enhanced TLR-2 and TLR-5 expression in THP-1, HEK293-TLR2 and HEK293-TLR5 cells, but not in the HEK293 control. In addition, IL-8 and TNF-α cytokine secretion in THP-1 cells was induced in a cagPAI-dependent manner. Furthermore, we show that HEK293 cells are not competent for the uptake of T4SS-delivered CagA, and are therefore ideally suited for studying TLR signalling in the absence of T4SS functions. HEK293 control cells, which do not induce TLR-2 and TLR-5 expression during infection, only secreted cytokines in small amounts, in agreement with T4SS functions being absent. In contrast, HEK293-TLR2 and HEK293-TLR5 cells were highly competent for inducing the secretion of IL-8 and TNF-α cytokines in a cagPAI-independent manner, suggesting that the expression of TLR-2 or TLR-5 has profoundly changed the capability to trigger pro-inflammatory signalling upon infection. Using phospho-specific antibodies and luciferase reporter assays, we further demonstrate that H. pylori induces IRAK-1 and IκB phosphorylation in a TLR-dependent manner, and this was required for activation of transcription factor NF-κB. Finally, NF-κB activation in HEK293-TLR2 and HEK293-TLR5 cells was confirmed by expressing p65-GFP which was translocated from the cytoplasm into the nucleus. These data indicate that H. pylori-induced expression of TLR-2 and TLR-5 can qualitatively shift cagPAI-dependent to cagPAI-independent pro-inflammatory signalling pathways with possible impact on the outcome of H. pylori-associated diseases. © 2011 Kumar Pachathundikandi et al.
Created from Fastlane, Scopus look-up

Inflammasome activation by helicobacter pylori and its implications for persistence and immunity - Suneesh Kumar, Pachathundikandi; Müller, Anne; Backert, Steffen (Inflammasome Signaling and Bacterial Infections, 2016)
Infection with the Gram-negative pathogen Helicobacter pylori is the most prevalent chronic bacterial infection affecting about 50 % of the human world population and is the main risk factor for gastric cancer development. The pro-inflammatory cytokine IL-1β plays a crucial role in the development of gastric tumors, and polymorphisms in the IL-1 gene cluster resulting in increased IL-1β production have been associated with increased risk for gastric cancer. Recently, Helicobacter pylori was postulated to activate the inflammasome in human and mouse immune cells, and the molecular mechanisms and the bacterial virulence factors activating the inflammasome were elucidated in cell culture as well as animal models. It appears that H. pylori-induced IL-1β secretion is mediated by activation of toll-like receptor 2 (TLR-2), Nod-like receptor family member NLRP3 and caspase-1. The cag pathogenicity island-encoded type IV secretion system, lipopolysaccharide, vacuolating cytotoxin, and urease B subunit appear to play a role in inflammasome activation. In addition, recent results indicate that the TLR-2 → NLRP3 → caspase-1 → IL-18 axis is critical to H. pylori-specific immune regulation conferring protection against allergen-induced asthma and inflammatory bowel disease in murine models. The present chapter will review the proposed mechanisms of NLRP3 inflammasome activation during H. pylori infection and discuss the recent progress in this important research field.
Created from Fastlane, Scopus look-up
Keywords: Inflammasome; NOD-like receptor; Caspase; Cytokine; Urease; LPS; Pyroptosis; Toll-like receptor; Type IV secretion

Inflammasome Signaling and Bacterial Infections Preface - Backert, Steffen (Inflammasome Signaling and Bacterial Infections, 2016)

"Inflammasome signalling and bacterial infections" - Backert, Steffen (Springer, 2016)

In silico proteomic and phylogenetic analysis of the outer membrane protein repertoire of gastric Helicobacter species. - Bauwens, Eva; Joosten, Myrthe; Taganna, Joemar; Rossi, Mirko; Debraekeleer, Ayla; Tay, Alfred; Peters, Fanny; Backert, Steffen; Fox, James; Ducatelle, Richard; Remaut, Han; Haesebrouck, Freddy; et al. (Scientific Reports, 2018)

Interaction of Helicobacter pylori with Toll-Like receptors: role in infection control and resolution of inflammation - Backert, Steffen; Suneesh Kumar, Pachathundikandi; Neddermann, Matthias; Lind, Judith; Tegtmeyer, Nicole (HELICOBACTER, 2019)
CRIS-Team WoS Importer:2019-10-04

Interplay of bacterial toxins with host defence: Molecular mechanisms of immunomodulatory signalling - Backert, Steffen; König, Wolfgang (International Journal of Medical Microbiology, 2005)
Mucosal surfaces are protected by a first line of defence termed the innate immune system, which controls the resident microflora to effectively prevent microbial diseases. Inflammatory processes are activated as a consequence of a complex interplay between microbes and host target cells. Many bacterial pathogens have developed mechanisms to avoid host recognition. Some are even able to exploit the immune response through sophisticated interactions with the host signalling cascades in order to increase their replication and propagation. While in the past major emphasis on bacterial protein toxins was directed towards their cytotoxic role, it is increasingly evident that toxins can also modulate various cellular functions at non-cytolytic concentrations. Here, we review important aspects on the molecular mechanisms of immunomodulatory interference by bacterial toxins, with emphasis on the signalling induced in the intestinal epithelium. © 2005 Elsevier GmbH. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Innate immunity; MAP kinases; NF-κB; Signalling; Toll-like receptors; Toxin

Interplay of the gastric pathogen helicobacter pylori with toll-like receptors - Suneesh Kumar, Pachathundikandi; Lind, Judith; Tegtmeyer, Nicole; El-Omar, Emad M.; Backert, Steffen (BioMed Research International, 2015)
Toll-like receptors (TLRs) are crucial for pathogen recognition and downstream signaling to induce effective immunity. The gastric pathogen Helicobacter pylori is a paradigm of persistent bacterial infections and chronic inflammation in humans. The chronicity of inflammation during H. pylori infection is related to the manipulation of regulatory cytokines. In general, the early detection of H. pylori by TLRs and other pattern recognition receptors (PRRs) is believed to induce a regulatory cytokine or chemokine profile that eventually blocks the resolution of inflammation. H. pylori factors such as LPS, HSP-60, NapA, DNA, and RNA are reported in various studies to be recognized by specific TLRs. However, H. pylori flagellin evades the recognition of TLR5 by possessing a conserved N-terminal motif. Activation of TLRs and resulting signal transduction events lead to the production of pro- and anti-inflammatory mediators through activation of NF-B, MAP kinases, and IRF signaling pathways. The genetic polymorphisms of these important PRRs are also implicated in the varied outcome and disease progression. Hence, the interplay of TLRs and bacterial factors highlight the complexity of innate immune recognition and immune evasion as well as regulated processes in the progression of associated pathologies. Here we will review this important aspect of H. pylori infection.
Created from Fastlane, Scopus look-up

Investigation of plant organellar DNAs by pulsed-field gel electrophoresis - Backert, Steffen; Dörfel, Peter; Börner, Thomas (Current Genetics, 1995)
Mitochondrial (mt) DNAs from several higher-plant species (Arabidopsis thaliana, Beta vulgaris, Brassica hirta, Chenopodium album, Oenothera berteriana, Zea mays) were separated by pulsed-field gel electrophoresis (PFGE). Hybridization of the separated DNA with mtDNA-specific probes revealed an identical distribution of mtDNA sequences in all cases: part of the DNA formed a smear of linear molecules migrating into the gel, the rest remained in the well. Hybridization signals in the compression zone of the gels disappeared after RNase or alkaline treatment. It was shown that the linear molecules are not products of unspecific degradation by nucleases. All plastid (pt) DNA from leaves of Nicotiana tabacum remained in the well after PFGE. Separation of linear monomers and oligomers of the chloroplast chromosomes of N. tabacum was achieved by mild DNase treatment of the well-bound DNA. DNase treatment of well-bound mtDNA, however, generated a smear of linear molecules. PtDNA from cultured cells of C. album was found after PFGE to be partly well-bound, and partly separated into linear molecules with sizes of monomeric and oligomeric chromosomes. The ease with which it was possible to detect large linear molecules of plastid DNA indicates that shearing forces alone can not explain the smear of linear molecules obtained after PFGE of mtDNA. The results are discussed in relation to the structural organization of the mt genome of higher plants. © 1995 Springer-Verlag.
Created from Fastlane, Scopus look-up
Keywords: Chenopodium album; Chloroplast DNA; Mitochondrial DNA; Pulsed-field gel electrophoresis

In vitro replication of mitochondrial plasmid mp1 from the higher plant Chenopodium album (L.): A remnant of bacterial rolling circle and conjugative plasmids? - Backert, Steffen; Kunnimalaiyaan, Muthusamy; Börner, Thomas; Nielsen, Brent Lynn (Journal of Molecular Biology, 1998)
According to the endosymbiotic theory, mitochondrial genomes evolved from the chromosome of an α-proteobacterum-like ancestor and developed during evolution an extraordinary variation in size, structure and replication. We studied in vitro DNA replication of the mitochondrial circular plasmid mp1 (1309 bp) from the higher plant Chenopodium album (L.) as a model system that replicates in a manner reminiscent of bacterial rolling circle plasmids. Several mp1 subclones were tested for their ability to support DNA replication using a newly developed in vitro system. Neutral/neutral two-dimensional gel electrophoresis of the in vitro products revealed typical simple Y patterns of intermediates consistent with a rolling circle type of replication. Replication activity was very high for a BamHI-restricted total plasmid DNA clone, a 464 bp BamHI/KpnI fragment and a 363 bp BamHI/SmaI fragment. Further subcloning of a 148 by BamHI/EcoRI fragment resulted in the strongest in vitro DNA replication activity, while a 1161 bp-template outside of this region resulted in a substantial loss of activity. Electron microscopic studies of in vitro DNA replication products from the highly active clones also revealed sigma-shaped molecules. These results support our in vivo data for the presence of a predominant replication origin between positions 628 and 776 on the plasmid map. This sequence shares homology with double-stranded rolling circle origin (dso) or transfer origin (oriT) nicking motifs from bacterial plasmids. mp1 is the first described rolling circle plasmid in eukaryotes.
Created from Fastlane, Scopus look-up
Keywords: Chenopodium album; Double-stranded origin; Electron microscopy; Mitochondrial plasmid; Rolling circle replication

Live Helicobacter pylori in the root canal of endodontic-infected deciduous teeth - Hirsch, Christian; Tegtmeyer, Nicole; Rohde, Manfred; Rowland, Marion; Oyarzabal, Omar A.; Backert, Steffen (Journal of Gastroenterology, 2012)
Background: Many polymerase chain reaction (PCR)- based studies have shown that Helicobacter pylori DNA is prevalent in the oral cavity, but reports on the isolation of live bacteria are extremely rare. Thus, it is still unclear whether H. pylori can indeed survive in the oral environment. Methods: Here we used electron microscopy, selective growth techniques, urease assays, 16S rRNA PCR, and western blotting to investigate the possible presence of live H. pylori in 10 root canal and corresponding plaque samples of endodontic-infected deciduous teeth in three children. Results: Although H. pylori DNA was verifiable by PCR in several plaque and root canal samples, bacterial colonies could only be grown from two root canals, but not from plaque. These colonies were unequivocally identified as H. pylori by microscopic, genetic, and biochemical approaches. Conclusions: Our findings show that root canals of endodontic- infected teeth may be a reservoir for live H. pylori that could serve as a potential source for transmission. © Springer 2012.
Created from Fastlane, Scopus look-up
Keywords: Deciduous teeth; Electron microscopy; Endodontics; Helicobacter pylori; Protein profiling; Root canal

Macroevolution of gastric Helicobacter species unveils interspecies admixture and time of divergence - Smet, Annemieke; Yahara, Koji; Rossi, Mirko; Tay, Alfred; Backert, Steffen; Enßer, Armin; Fox, James G.; Flahou, Bram; Ducatelle, Richard; Haesebrouck, Freddy; Corander, Jukka (Isme Journal, 2018)
Since the discovery of the human pathogen Helicobacter pylori, various other Helicobacter species have been identified in the stomach of domesticated and wild mammals. To better understand the evolutionary history of these ecologically similar but genetically distinct species, we analyzed 108 gastric Helicobacter genomes and included 54 enterohepatic Helicobacter genomes for comparison purposes. An admixture analysis supported the presence of an ecological barrier, preventing the genetic exchange between the gastric and enterohepatic Helicobacter species, and unraveled many gene flow events within and across species residing in the stomach. As pets can be colonized by multiple gastric Helicobacter species, the genetic exchange between the canine and feline strains was evident, with H. heilmannii and H. bizzozeronii showing the highest interspecies recombination. An admixture between H. pylori (in particular, the ancestral African strains), H. acinonychis from wild felines and H. cetorum from marine mammals was also identified. Because these latter species do not share the same host, this phenomenon is most likely a remaining signal of shared ancestry. A reconstruction of the time of divergence of the gastric Helicobacter spp. revealed that the domestic animal-related Helicobacter species evolved in parallel with H. pylori and its two closest relatives (H. acinonychis and H. cetorum), rather than together.
EVALuna2:35812

Macroevolution of gastric Helicobacter species unveils interspecies admixture and time of divergence (vol 12, pg 2518, 2018) - Smet, Annemieke; Yahara, Koji; Rossi, Mirko; Tay, Alfred; Backert, Steffen; Enßer, Armin; Fox, James G.; Flahou, Bram; Ducatelle, Richard; Haesebrouck, Freddy; Corander, Jukka (Isme Journal, 2019)

Major host factors involved in epithelial cell invasion of Campylobacter jejuni: role of fibronectin, integrin beta1, FAK, Tiam-1, and DOCK180 in activating Rho GTPase Rac1 - Boehm, Manja; Krause-Gruszczynska, Malgorzata; Rohde, Manfred; Tegtmeyer, Nicole; Takahashi, Seiichiro; Oyarzabal, Omar A.; Backert, Steffen (Frontiers in Cellular and Infection Microbiology, 2011)
Host cell entry by the food-borne pathogen Campylobacter jejuni has been reported as one of the primary reasons of tissue damage in infected humans, however, molecular invasion mechanisms and cellular factors involved in this process are widely unclear. Here we used knockout cell lines derived from fibronectin(-/-), integrin beta1(-/-), and focal adhesion kinase (FAK)(-/-) deficient mice and corresponding wild-type (WT) controls, to study C. jejuni-induced signaling cascades involved in the bacterial invasion process. Using high resolution scanning electron microscopy, GTPase pull-downs, G-LISA, and gentamicin protection assays we found that each of these host cell factors is indeed required for activation of the small Rho GTPase member Rac1 and maximal host cell invasion of this pathogen. Interestingly, membrane ruffling, tight engulfment of bacteria and invasion were only seen during infection of WT control cells, but not in fibronectin(-/-), integrin beta1(-/-), and FAK(-/-) knockout cell lines. We also demonstrate that C. jejuni activates FAK autophosphorylation activity at Y-397 and phosphorylation of Y-925, which is required for stimulating two downstream guanine exchange factors, DOCK180 and Tiam-1, which are upstream of Rac1. Small interfering (si) RNA studies further show that DOCK180 and Tiam-1 act cooperatively to trigger Rac1 activation and C. jejuni invasion. Moreover, mutagenesis data indicate that the bacterial fibronectin-binding protein CadF and the intact flagellum are involved in Rho GTPase activation and host cell invasion. Collectively, our results suggest that C. jejuni infection of host epithelial target cells hijacks a major fibronectin → integrin beta1 → FAK → DOCK180/Tiam-1 signaling cascade, which has a crucial role for Rac1 GTPase activity and bacterial entry into host target cells.
Created from Fastlane, Scopus look-up
Keywords: cellular invasion; molecular pathogenesis; Rho family GTPases; signaling; virulence

Masking of typical TLR4 and TLR5 ligands modulates inflammation and resolution by Helicobacter pylori - Suneesh Kumar, Pachathundikandi; Tegtmeyer-Backert, Nicole; Backert, Steffen (Trends in Microbiology, 2023)
Helicobacter pylori is a paradigm of chronic bacterial infection and is associated with peptic ulceration and malignancies. H. pylori uses specific masking mechanisms to avoid canonical ligands from activating Toll-like receptors (TLRs), such as lipopolysaccharide (LPS) modification and specific flagellin sequences that are not detected by TLR4 and TLR5, respectively. Thus, it was believed for a long time that H. pylori evades TLR recognition as a crucial strategy for immune escape and bacterial persistence. However, recent data indicate that multiple TLRs are activated by H. pylori and play a role in the pathology. Remarkably, H. pylori LPS, modified through changes in acylation and phosphorylation, is mainly sensed by other TLRs (TLR2 and TLR10) and induces both pro- and anti-inflammatory responses. In addition, two structural components of the cag pathogenicity island-encoded type IV secretion system (T4SS), CagL and CagY, were shown to contain TLR5-activating domains. These domains stimulate TLR5 and enhance immunity, while LPS-driven TLR10 signaling predominantly activates anti-inflammatory reactions. Here, we discuss the specific roles of these TLRs and masking mechanisms during infection. Masking of typical TLR ligands combined with evolutionary shifting to other TLRs is unique for H. pylori and has not yet been described for any other species in the bacterial kingdom. Finally, we highlight the unmasked T4SS-driven activation of TLR9 by H. pylori, which mainly triggers anti-inflammatory responses.
CRIS-Team Scopus Importer:2023-04-14
Keywords: H. pylori; inflammation; PAMP; PRR; T4SS; TLR

Mechanisms of inflammasome signaling, microRNA induction and resolution of inflammation by helicobacter pylori - Suneesh Kumar, Pachathundikandi; Blaser, Nicole; Backert, Steffen (Molecular Mechanisms of Inflammation: Induction, Resolution and Escape by Helicobacter pylori, 2019)
Inflammasome-controlled transcription and subsequent cleavage-mediated activation of mature IL-1β and IL-18 cytokines exemplify a crucial innate immune mechanism to combat intruding pathogens. Helicobacter pylori represents a predominant persistent infection in humans, affecting approximately half of the population worldwide, and is associated with the development of chronic gastritis, peptic ulcer disease, and gastric cancer. Studies in knockout mice have demonstrated that the pro-inflammatory cytokine IL-1β plays a central role in gastric tumorigenesis. Infection by H. pylori was recently reported to stimulate the inflammasome both in cells of the mouse and human immune systems. Using mouse models and in vitro cultured cell systems, the bacterial pathogenicity factors and molecular mechanisms of inflammasome activation have been analyzed. On the one hand, it appears that H. pylori-stimulated IL-1β production is triggered by engagement of the immune receptors TLR2 and NLRP3, and caspase-1. On the other hand, microRNA hsa-miR-223-3p is induced by the bacteria, which controls the expression of NLRP3. This regulating effect by H. pylori on microRNA expression was also described for more than 60 additionally identified microRNAs, indicating a prominent role for inflammatory and other responses. Besides TLR2, TLR9 becomes activated by H. pylori DNA and further TLR10 stimulated by the bacteria induce the secretion of IL-8 and TNF, respectively. Interestingly, TLR-dependent pathways can accelerate both pro- and anti-inflammatory responses during H. pylori infection. Balancing from a pro-inflammation to anti-inflammation phenotype results in a reduction in immune attack, allowing H. pylori to persistently colonize and to survive in the gastric niche. In this chapter, we will pinpoint the role of H. pylori in TLR- and NLRP3 inflammasome-dependent signaling together with the differential functions of pro- and anti-inflammatory cytokines. Moreover, the impact of microRNAs on H. pylori–host interaction will be discussed, and its role in resolution of infection versus chronic infection, as well as in gastric disease development.
CRIS-Team Scopus Importer:2019-06-18
Keywords: CagA; Caspase; miRNA; T4SS; TLR2; Urease

Microbial Food Safety An Introduction - Oyarzabal, Omar A.; Backert, Steffen (Springer, 2012)

Microtubules as platforms for assaying actin polymerization in vivo - Oelkers, J. Margit; Vinzenz, Marlene; Nemethova, Maria; Jacob, Sonja; Lai, Frank P. L.; Block, Jennifer; Szczodrak, Malgorzata; Kerkhoff, Eugen; Backert, Steffen; Schlueter, Kai; Stradal, Theresia E. B.; Small, J. Victor; et al. (PLoS ONE, 2011)
The actin cytoskeleton is continuously remodeled through cycles of actin filament assembly and disassembly. Filaments are born through nucleation and shaped into supramolecular structures with various essential functions. These range from contractile and protrusive assemblies in muscle and non-muscle cells to actin filament comets propelling vesicles or pathogens through the cytosol. Although nucleation has been extensively studied using purified proteins in vitro, dissection of the process in cells is complicated by the abundance and molecular complexity of actin filament arrays. We here describe the ectopic nucleation of actin filaments on the surface of microtubules, free of endogenous actin and interfering membrane or lipid. All major mechanisms of actin filament nucleation were recapitulated, including filament assembly induced by Arp2/3 complex, formin and Spir. This novel approach allows systematic dissection of actin nucleation in the cytosol of live cells, its genetic re-engineering as well as screening for new modifiers of the process. © 2011 Oelkers et al.
Created from Fastlane, Scopus look-up

Mitochondrial DNA recombination in Brassica campestris - Manchekar, Medha; Scissum-Gunn, Karyn D.; Hammett, Lisa A.; Backert, Steffen; Nielsen, Brent L. (Plant Science, 2009)
The structure of the mitochondrial genome in plants is unclear, but appears to consist of mostly linear DNA with some other structures, including branched molecules and subgenomic circles. Mitochondrial DNA (mtDNA) recombination was analyzed in Brassica campestris, which has one of the smallest mitochondrial genomes (218 kb) in higher plants. Field-inversion gel electrophoresis (FIGE) separated mtDNA into discrete populations that each represents the entire genome. Electron microscopy revealed large, mostly linear molecules trapped in the wells, slower migrating populations with mostly linear DNA and a low level of circular and networked mtDNA molecules of 10-140 kbp, and a fast migrating population of 10-50 kbp linear mtDNA. Some smaller than genome size circular molecules and circles with tails were observed, and may represent recombination or rolling circle replication intermediates. Hybridization of end-labeled mtDNA suggests there may be specific ends (or recombination hotspots) for some linear molecules. Analysis of mtDNA enriched by BND-cellulose and separated by two-dimensional agarose gel electrophoresis shows the presence of complex recombination structures and the presence of significant single-stranded regions in mtDNA. These findings provide further evidence that DNA recombination contributes to the complex structure of mtDNA in plants. © 2009 Elsevier Ireland Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Brassica; DNA recombination; Genome structure; Mitochondrial DNA; Two-dimensional agarose gel electrophoresis

Molecular evolution of the VacA p55 binding domain of Helicobacter pylori in mestizos from a high gastric cancer region of Colombia - Gutierrez-Escobar, Andres J.; Bravo, Maria M.; Acevedo, Orlando; Backert, Steffen (PeerJ, 2019)
The stomach bacterium Helicobacter pylori is one of the most prevalent pathogens in humans, closely linked with serious diseases such as gastric cancer. The microbe has been associated with its host for more than 100,000 years and escorted modern humans out of Africa. H. pylori is predominantly transmitted within families and dispersed globally, resulting in distinct phylogeographic patterns, which can be utilized to investigate migrations and bioturbation events in human history. Latin America was affected by several human migratory waves due to the Spanish colonisation that drastically changed the genetic load and composition of the bacteria and its host. Genetic evidence indicates that independent evolutionary lines of H. pylori have evolved in mestizos from Colombia and other countries in the region during more than 500 years since colonisation. The vacuolating cytotoxin VacA represents a major virulence factor of the pathogen comprising two domains, p33 and p55, the latter of which is essential for binding to the host epithelial cell. The evolution of the VacA toxin in Colombia has been strongly biased due to the effects of Spanish colonization. However, the variation patterns and microevolution of the p55 domain have not yet been described for this population. In the present study, we determined the genetic polymorphisms and deviations in the neutral model of molecular evolution in the p55 domain of 101 clinical H. pylori isolates collected in Bogota, a city located in Andean mountains characterized by its high gastric cancer risk and its dominant mestizo population. The microevolutionary patterns of the p55 domain were shaped by recombination, purifying and episodic diversifying positive selection. Furthermore, amino acid positions 261 and 321 in the p55 domain of VacA show a high variability among mestizos clinical subsets, suggesting that natural selection in H. pylori may operate differentially in patients with different gastric diseases.
CRIS-Team WoS Importer:2019-05-21

Molecular Mechanism of Inflammation: Induction, Resolution and Escape by Helicobacter pylori - Backert, Steffen (Springer, 2019)

Molecular mechanisms of epithelial-barrier disruption by Helicobacter pylori. - Wessler, Silja; Backert, Steffen (Trends in Microbiology, 2008)
Intact intercellular junctions and cell-matrix contacts are important structures in the formation and maintenance of epithelial-barrier functions against microbes. The human gastric pathogen Helicobacter pylori developed a remarkable network of strategies to alter these epithelial cell-cell and cell-matrix adhesions, which are implicated in inflammation, proliferation, cell migration and invasive growth. This review focuses on recent findings on H. pylori-induced host-cell signaling. We propose a stepwise model for how H. pylori interacts with components of focal adhesions and intercellular tight and adherens junctions to disrupt the epithelial layer, providing novel insights into the pathogenesis of H. pylori.

Molecular mechanisms of gastric epithelial cell adhesion and injection of CagA by Helicobacter pylori - Backert, Steffen; Clyne, Marguerite; Tegtmeyer, Nicole (Cell Communication and Signaling, 2011)
Helicobacter pylori is a highly successful pathogen uniquely adapted to colonize humans. Gastric infections with this bacterium can induce pathology ranging from chronic gastritis and peptic ulcers to gastric cancer. More virulent H. pylori isolates harbour numerous well-known adhesins (BabA/B, SabA, AlpA/B, OipA and HopZ) and the cag (cytotoxin-associated genes) pathogenicity island encoding a type IV secretion system (T4SS). The adhesins establish tight bacterial contact with host target cells and the T4SS represents a needle-like pilus device for the delivery of effector proteins into host target cells such as CagA. BabA and SabA bind to blood group antigen and sialylated proteins respectively, and a series of T4SS components including CagI, CagL, CagY and CagA have been shown to target the integrin β§ssub§1 §esub§receptor followed by injection of CagA across the host cell membrane. The interaction of CagA with membrane-anchored phosphatidylserine may also play a role in the delivery process. While substantial progress has been made in our current understanding of many of the above factors, the host cell receptors for OipA, HopZ and AlpA/B during infection are still unknown. Here we review the recent progress in characterizing the interactions of the various adhesins and structural T4SS proteins with host cell factors. The contribution of these interactions to H. pylori colonization and pathogenesis is discussed. © 2011 Backert et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: adherence; adhesin; Helicobacter pylori; integrin; receptor; signalling; type IV secretion

Molecular methods to investigate adhesion, transmigration, invasion and intracellular survival of the foodborne pathogen campylobacter jejuni - Backert, Steffen; Hofreuter, Dirk (Journal of Microbiological Methods, 2013)
Campylobacter jejuni is a spiral-shaped Gram-negative pathogen and major agent of gastrointestinal foodborne illness in humans worldwide. This pathogen encodes numerous described pathogenicity-associated factors involved in important processes including bacterial adhesion to, transmigration across, invasion into and intracellular survival within intestinal epithelial cells. This review article highlights various molecular techniques applied in the studies of each of these individual steps of C. jejuni host cell interactions in vitro including gentamicin protection assay, chemotaxis and motility assays, transwell and intracellular survival assays, G-Lisa, siRNA knockdown, immunohistochemistry, immunofluorescence, electron microscopy and luciferase reporter assays. We discuss the strengths and limitations of the methods as well as the different cell model systems applied. Future work should employ new technologies including modern microscopic, proteomics-based and cell signaling approaches to identify and characterise novel virulence mechanisms, which are crucial to provide fresh insights into the diversity of strategies employed by this important pathogen to cause disease. © 2013 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Cellular invasion; Molecular pathogenesis; Signalling; Virulence

Molecular Pathogenesis and Signal Transduction by Helicobacter pylori - Tegtmeyer, Nicole; Backert, Steffen (Springer, 2017)

Molecular Pathogenesis and Signal Transduction by Helicobacter pylori Preface - Tegtmeyer, Nicole; Backert, Steffen (Molecular Pathogenesis and Signal Transduction by Helicobacter pylori, 2017)

Molecular Targets in Campylobacter Infections - Heimesaat, Markus M.; Backert, Steffen; Alter, Thomas; Bereswill, Stefan (Biomolecules, 2023)
Human campylobacteriosis results from foodborne infections with Campylobacter bacteria such as Campylobacter jejuni and Campylobacter coli, and represents a leading cause of bacterial gastroenteritis worldwide. After consumption of contaminated poultry meat, constituting the major source of pathogenic transfer to humans, infected patients develop abdominal pain and diarrhea. Post-infectious disorders following acute enteritis may occur and affect the nervous system, the joints or the intestines. Immunocompromising comorbidities in infected patients favor bacteremia, leading to vascular inflammation and septicemia. Prevention of human infection is achieved by hygiene measures focusing on the reduction of pathogenic food contamination. Molecular targets for the treatment and prevention of campylobacteriosis include bacterial pathogenicity and virulence factors involved in motility, adhesion, invasion, oxygen detoxification, acid resistance and biofilm formation. This repertoire of intervention measures has recently been completed by drugs dampening the pro-inflammatory immune responses induced by the Campylobacter endotoxin lipo-oligosaccharide. Novel pharmaceutical strategies will combine anti-pathogenic and anti-inflammatory effects to reduce the risk of both anti-microbial resistance and post-infectious sequelae of acute enteritis. Novel strategies and actual trends in the combat of Campylobacter infections are presented in this review, alongside molecular targets applied for prevention and treatment strategies.
CRIS-Team Scopus Importer:2023-04-07
Keywords: Campylobacter jejuni infection models; campylobacteriosis; infection prevention strategies; one health concept

Molecular typing, serotyping and cytotoxicity testing of Campylobacter jejuni strains isolated from commercial broilers in Puerto Rico - Oyarzabal, O. A.; Backert, Steffen; Williams, L. L.; Lastovica, A. J.; Miller, R. S.; Pierce, S. J.; Vieira, S. L.; Rebollo-Carrato, F. (Journal of Applied Microbiology, 2008)
Aims: Thirty Campylobacter jejuni strains isolated from fecal samples (n = 94; 32%) from 13 positive farms (n = 17; 76%) from commercial broiler chickens in Puerto Rico were analysed by molecular methods. Methods and Results: Isolates were identified with multiplex polymerase chain reaction assays, tested for their antimicrobial susceptibility and characterized with pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), serotyping and bacterial cytotoxicity in mammalian cells. Isolates exhibited high resistance to vancomycin (minimum inhibitory concentration, MIC of >256 μg ml -1) and trimethoprim (MIC of >32 μg ml-1); few were resistant to clindamycin (MIC90 4 μg ml-1), erythromycin (MIC90 8 μg ml-1) and tetracycline (MIC90 8 μg ml-1); but none was resistant to azithromycin (MIC90 4 μg ml-1), ciprofloxacin (MIC 90 1 μg ml-1) or gentamycin (MIC90 4 μg ml-1). Most strains restricted with SmaI, but a combination of SmaI-KpnI digestion was more discriminatory. MLST analysis yielded four sequence types (ST), and ST-2624 was the predominant one. Phylogenetic analysis revealed a high degree of recombination for glnA and pgm genes. The predominant serotypes were O:3 and O:5. Most strains had lowest cytotoxicity potential with Caco-2 cells, medium cytotoxicity with INT-407 and Hep-2 cells and high cytotoxicity with CHO cells. Conclusion: A low degree of antimicrobial resistance, 13 PFGE profiles, 4 ST and a large variability in cytotoxicity assays were found for these strains. Significance and Impact of the Study: This is the first characterization of C. jejuni strains isolated from broilers in Puerto Rico. The genetic diversity of these strains suggests that several techniques are needed for strain characterization. © 2008 The Authors.
Created from Fastlane, Scopus look-up
Keywords: Broiler; Campylobacter; Chicken; Cytotoxicity assays; MLST; PFGE; Serotyping

Morphologic, genetic, and biochemical characterization of Helicobacter magdeburgensis, a novel species isolated from the intestine of laboratory mice - Traverso, Francisco Rivas; Bohr, Ulrich R. M.; Oyarzabal, Omar A.; Rohde, Manfred; Clarici, Alexandra; Wex, Thomas; Kuester, Doerthe; Malfertheiner, Peter; Fox, James G.; Backert, Steffen (Helicobacter, 2010)
Background: The presence of enterohepatic Helicobacter species (EHS) is commonly noted in mouse colonies. These infections often remain unrecognized but can cause severe health complications or more subtle host immune perturbations and therefore can confound the results of animal experiments. The aim of this study was to isolate and characterize a putative novel EHS that has previously been detected by PCR screening of specific-pathogen-free mice. Materials and Methods: Biochemical analysis of enzyme activities (API campy), morphologic investigation (Gram-staining and electron microscopy) and genetic analyses (16SrRNA and 23SrRNA analyses, DNA fingerprinting, restriction fragment polymorphisms, and pulsed-field gel electrophoresis) were used to characterize isolated EHS. Genomic DNA fragments were sequenced to develop a species-specific PCR detection assay. Results: Scanning electron microscopy revealed the presence of spiral-shaped EHS, which varied in length (2.5-6 μm) and contained single monopolar or single bipolar sheathed flagella. The bacteria were grown under anaerobic conditions, preferably on agar plates containing serum or blood. The 16SrRNA, genetic, and biochemical analyses indicated the identification of a novel EHS species, named Helicobacter magdeburgensis. We also examined the genome content using pulsed-field gel electrophoresis. Based on the pattern produced by two restriction enzymes, BamIII and KspI, the genome size was determined to be about 1.7-1.8 Mbp. Conclusion: We isolated and characterized a novel EHS species, H. magdeburgensis, morphologically, biochemically, and genetically. These results are important for future studies on the prevalence and pathophysiologic relevance of such infections. Our PCR assay can be used to detect and discriminate H. magdeburgensis from other Helicobacter species. © 2010 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up
Keywords: electron microscopy; Enterohepatic Helicobacter; genome; pulsed-field gel electrophoresis; RAPD fingerprinting

Mutational analysis differentiating sporadic carcinomas from colitis-associated colorectal carcinomas - Dregelies, Theresa; Haumaier, Franziska; Sterlacci, William; Backert, Steffen; Vieth, Michael (Cell Communication and Signaling, 2024)
BACKGROUND: Ulcerative colitis (UC) is a chronic inflammatory bowel disease (IBD) that is associated with increased risk of developing colitis-associated carcinoma (CAC). The genetic profile of CACs is fairly similar to the sporadic colorectal carcinomas (sCRCs), although showing certain differences in the timing and sequence of alterations that contribute to carcinogenesis. Also, both cancer types typically show a strong histological resemblance, which complicates the pathologists' diagnosis. Due to the different clinical consequences, it is of utmost importance to categorize the corresponding cancer type correctly. METHODS: In this study, we determined the mutation profiles of 64 CACs and sCRCs in the hotspot regions of 50 cancer-associated genes and compared them to 29 controls to identify genetic gene variants that can facilitate the pathologists' diagnosis. Pearson Chi-Square or Fisher's exact tests were used for statistical analyses. RESULTS: We found that sCRCs tend to mutate more frequently in APC and PIK3CA genes than CACs and that mainly males were affected. Our CAC cohort identified the KRAS G12D mutation as group-specific variant that was not detected in the sCRCs. When separating conventional from non-conventional CACs, it was discovered that the conventional type shows significantly more mutations for ATM. CONCLUSIONS: Taken together, our data highlights genetic differences between sCRC and CAC and enables the possibility to utilize specific gene alterations to support the pathologist's diagnosis.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Colitis-associated carcinoma; Conventional carcinoma; Mutation; Non-conventional carcinoma; Sporadic carcinoma; Ulcerative colitis

Natürliche und adaptive Immunität des Respirationstraktes – Bedeutung mikrobieller Faktoren für Infektabwehr und Sensibilisierung – Teil I - König, Wolfgang; Lauf, H.; Arnold, U.; Tammer, Ina; Ghebremedhin, B.; Clarici, Alexandra; Thies, F. L.; Drynda, A.; Schmalcz, A.; Kwok, Terry; Arnold, Ralf; Backert, Steffen; et al. (Atemwegs- und Lungenkrankheiten, 2004)
Keywords: Asthma; Atopic dermatitis; Toll-like receptors; Defensins; Eosinophils; Chemokines; Cytokines; Innate and adaptive immunity; Leukotrienes; Epithelial cells; Histamine; TH1/TH2 dichotomy; Tissue remodelling; Mast cells; T-regulatory cells

Natürliche und adaptive Immunität des Respirationstraktes – Bedeutung mikrobieller Faktoren für Infektabwehr und Sensibilisierung – Teil II - König, Wolfgang; Lauf, H.; Arnold, U.; Tammer, Ina; Ghebremedhin, B.; Clarici, Alexandra; Thies, F. L.; Drynda, A.; Schmalcz, A.; Kwok, Terry; Arnold, Ralf; Backert, Steffen; et al. (Atemwegs- und Lungenkrankheiten, 2004)
Under the "umbrella" of various inflammatory signals, the dendritic cells on interaction with exogenous compounds, e.g. bacteria, viruses, allergens, pollutants, mature and transmit the signal to the peripheral lymph node, thus interacting and tuning diverse effector T cells. The result of this is under a control of T-regulatory cells which either allows the dichotomy of TH1- or TH2-induced cellular functions with the generation of IL-2 and Interferon-γ for Th1 or IL-4, IL-5, IL-13, IL-10 for Th2. Clearly, the opposite action does not necessarily imply protection or damage but is the result of the appropriate response in host defense either allowing a humoral or cell-mediated immune response. Obviously, when outbalanced inflammatory and allergic disease processes may occur, which in rare cases are exclusively either TH2- or TH1-directed. Basically, the majority of reactions finally shows a complex mixture of TH2 and TH1 processes as is observed in allergy, asthma as well as atopic dermatitis. The respiratory tract in contrast to the gastrointestinal tract clearly shows differences with regard to the efficacy of T effector cell function. In the gastrointestinal tract, the T-regulatory system seems to be overwhelming primarily in the response as far as antigens and allergens are concerned leading to a status of tolerance. This is obligatory in order to comply with the huge commensal microbial flora which is present in the intestinal lumen. The pathogenicity within the gastrointestinal lumen is certainly a result of defined microbial pathogenicity factors or a deficiency of the commensal flora within the lumen which has protective functions. Within the respiratory tract, additional mechanisms are operative which are supported by components of the innate immune system within the surfactant system or other structures which may eliminate the influx of allergens, antigens and microorganisms. The protective cellular function is often overridden by the fact that the majority of allergens also have protease activities and there is indication that a basic general enzyme activity (chitinase) might be the clue to allergy. Protease-associated allergens induce inflammatory mediators from mast cells, thus providing histamine, leukotrienes and cytokines which tune the effector T cell function to a TH2 profile with the predominant release of IL-4 and IL-5. This then allows the induction of IgE responses and eosinophil activation, which most likely is not necessarily associated with asthma. Basically, IgE is not only regarded as the bridging molecule for the induction of mast cell mediator release. By the diversity of various receptors for IgE, an amplified inflammatory response via FcεRI and FcεRII on interaction with allergens and antigens may occur. In addition, the occurrence of IgE also modulates structural functions of the IgE receptor and initiates the generation of inflammatory mediators and the increase of e.g. cellular histamine content. The detailed studies on inflammatory mediators, such as histamine, prostaglandins and leukotrienes, clearly led to the identification of receptors for these molecules which are 7 transmembrane G-protein-coupled receptors. By their presence on various cells and their diversity, a single mediator such as histamine can either activate or downregulate the inflammatory processes by induction of e.g. IL-10 or TGF-β.
Created from Fastlane, Scopus look-up
Keywords: Asthma; Atopic dermatitis; Chemokines; Cytokines; Defensins; Eosinophils; Epithelial cells; Histamine; Innate and adaptive immunity; Leukotrienes; Mast cells; TH1/TH2 dichotomy; Tissue remodelling; Toll-like receptors; Tr-regulatory cells

Natürliche und adaptive Immunität des Respirationstraktes – Bedeutung mikrobieller Faktoren für Infektabwehr und Sensibilisierung Teil III - Werchau, H.; Backert, Steffen; König, Brigitte; König, Wolfgang; Lauf, H.; Tammer, Ina; Ghebremedhin, B.; Clarici, Alexandra; Thies, F. L.; Drynda, A.; Schmalcz, A.; Kwok, Terry; et al. (Atemwegs- und Lungenkrankheiten, 2005)
Keywords: Asthma; Atopic dermatitis; Tt-regulatory cells; Defensins; Eosinophils; Chemokines; Cytokines; Innate and adaptive immunity; Leukotrienes; Epithelial cells; Histamine; Tissue remodelling; Toll-Like receptors; Mast cells; TH1/TH2 dichotomy

NF-κB activation and potentiation of proinflammatory responses by the Helicobacter pylori CagA protein - Brandt, Sabine; Kwok, Teriy; Hartig, Roland; König, Wolfgang; Backert, Steffen (Proceedings of the National Academy of Sciences of the United States of America, 2005)
The Helicobarter pylori immunodominant protein, CagA, is associated with severe gastritis and carcinoma. Injection of CagA into gastric epithelial cells by type IV secretion leads to actin-cytoskeletal rearrangements and cell scattering. CagA has been reported to have no role in the induction of transcription factor NF-κB and IL-8, which are crucial determinants for chronic inflammation. Here, we provide several lines of evidence showing that CagA is able to induce IL-8 in a time- and strain-dependent manner. We also show that by exchanging specific cagA genes, high IL-8-inducing H. pylori strains could be converted into low inducing strains and vice versa. Our results suggest that IL-8 release induced by CagA occurs via a Ras→Raf→Mek→ Erk→NF-κB signaling pathway in a Shp-2- and c-Met-independent manner. Thus, CagA is a multifunctional protein capable of effecting both actin remodeling and potentiation of chemokine release. © 2005 by The National Academy of Sciences of the USA.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; Type IV secretion; Virulence

Overexpression of serine protease HtrA enhances disruption of adherens junctions, paracellular transmigration and type IV secretion of CagA by Helicobacter pylori - Harrer, Aileen; Böhm, Manja; Backert, Steffen; Tegtmeyer, Nicole (Gut Pathogens, 2017)
Background: The serine protease HtrA is an important factor for regulating stress responses and protein quality control in bacteria. In recent studies, we have demonstrated that the gastric pathogen Helicobacter pylori can secrete HtrA into the extracellular environment, where it cleaves-off the ectodomain of the tumor suppressor and adherens junction protein E-cadherin on gastric epithelial cells. Results: E-cadherin cleavage opens cell-to-cell junctions, allowing paracellular transmigration of the bacteria across polarized monolayers of MKN-28 and Caco-2 epithelial cells. However, rapid research progress on HtrA function is mainly hampered by the lack of ΔhtrA knockout mutants, suggesting that htrA may represent an essential gene in H. pylori. To circumvent this major handicap and to investigate the role of HtrA further, we overexpressed HtrA by introducing a second functional htrA gene copy in the chromosome and studied various virulence properties of the bacteria. The resulting data demonstrate that overexpression of HtrA in H. pylori gives rise to elevated rates of HtrA secretion, cleavage of E-cadherin, bacterial transmigration and delivery of the type IV secretion system (T4SS) effector protein CagA into polarized epithelial cells, but did not affect IL-8 chemokine production or the secretion of vacuolating cytotoxin VacA and γ-glutamyl-transpeptidase GGT. Conclusions: These data provide for the first time genetic evidence in H. pylori that HtrA is a novel major virulence factor controlling multiple pathogenic activities of this important microbe.
Created from Fastlane, Scopus look-up
Keywords: Abl; Adherens junction; CagA; E-cadherin; EPIYA; Helicobacter pylori; HtrA; Integrin; Protease; Src; T4SS; Tight junction; Transwell; Type IV secretion system

Pathogenesis of Helicobacter pylori Infection - Backert, Steffen; Clyne, Marguerite (Helicobacter, 2011)

Pathogenesis of Helicobacter pylori infection - Backert, Steffen; Neddermann, Matthias; Maubach, Gunter; Naumann, Michael (Helicobacter, 2016)
Helicobacter pylori is estimated to infect more than half of the worlds human population and represents a major risk factor for chronic gastritis, peptic ulcer disease, MALT lymphoma, and gastric adenocarcinoma. H. pylori infection and clinical consequences are controlled by highly complex interactions between the host, colonizing bacteria, and environmental parameters. Important bacterial determinants linked with gastric disease development include the cag pathogenicity island encoding a type IV secretion system (T4SS), the translocated effector protein CagA, vacuolating cytotoxin VacA, adhesin BabA, urease, serine protease HtrA, secreted outer membrane vesicles, and many others. The high quantity of these factors and allelic changes in the corresponding genes reveals a sophisticated picture and problems in evaluating the impact of each distinct component. Extensive work has been performed to pinpoint molecular processes related to H. pylori-triggered pathogenesis using Mongolian gerbils, mice, primary tissues, as well as novel in vitro model systems such as gastroids. The manipulation of host signaling cascades by the bacterium appears to be crucial for inducing pathogenic downstream activities and gastric disease progression. Here, we review the most recent advances in this important research area.
Created from Fastlane, Scopus look-up
Keywords: CagA; CagL; gastric cancer; gastroids; HtrA; inflammation; pathogenicity island; signaling; TlpB; type IV secretion system; urease; VacA

Pathogenesis of Helicobacter pylori infections - Torres, Javier; Backert, Steffen (Helicobacter, 2008)
The clinical outcome of Helicobacter pylori infection is determined by a complex scenario of interactions between the bacterium and the host. The main bacterial factors associated with colonization and pathogenicity comprise outer membrane proteins including BabA, SabA, OipA, AlpA/B, as well as the virulence factors CagA in the cag pathogenicity island (cagPAI) and the vacuolating cytotoxin VacA. The multitude of these proteins and allelic variation makes it extremely difficult to test the contribution of each individual factor. Much effort has been put into identifying the mechanism associated with H. pylori‐associated carcinogenesis. Interaction between bacterial factors such as CagA and host signal transduction pathways seems to be critical for mediating the induction of membrane dynamics, actin‐cytoskeletal rearrangements and the disruption of cell‐to‐cell junctions as well as proliferative, pro‐inflammatory and antiapoptotic nuclear responses. An animal model using the Mongolian gerbil is a useful system to study the gastric pathology of H. pylori infection.<br
Keywords: Helicobacter pylori; Cancer; Type IV secretion system; Signaling; Vacuolating cytotoxin

Pathogen-induced ubiquitin-editing enzyme A20 bifunctionally shuts off NF-kappa B and caspase-8-dependent apoptotic cell death - Lim, Michelle C. C.; Maubach, Gunter; Sokolova, Olga; Feige, Michael H.; Diezko, Rolf; Buchbinder, Joern; Backert, Steffen; Schlueter, Dirk; Lavrik, Inna N.; Naumann, Michael (Cell Death and Differentiation, 2017)
The human pathogen Helicobacter pylori infects more than half of the world's population and is a paradigm for persistent yet asymptomatic infection but increases the risk for chronic gastritis and gastric adenocarcinoma. For successful colonization, H. pylori needs to subvert the host cell death response, which serves to confine pathogen infection by killing infected cells and preventing malignant transformation. Infection of gastric epithelial cells by H. pylori provokes direct and fast activation of the proinflammatory and survival factor NF-kappa B, which regulates target genes, such as CXCL8, BIRC3 and TNFAIP3. However, it is not known how H. pylori exploits NF-kappa B activation and suppresses the inflammatory response and host apoptotic cell death, in order to avert the innate immune response and avoid cell loss, and thereby enhance colonization to establish long-term infection. Here we assign for the first time that H. pylori and also Campylobacter jejuni-induced ubiquitin-editing enzyme A20 bifunctionally terminates NF-kappa B activity and negatively regulates apoptotic cell death. Mechanistically, we show that the deubiquitinylase activity of A20 counteracts cullin3-mediated K63-linked ubiquitinylation of procaspase-8, therefore restricting the activity of caspase-8. Interestingly, another inducible NF-kappa B target gene, the scaffold protein p62, ameliorates the interaction of A20 with procaspase-8. In conclusion, pathogen-induced de novo synthesis of A20 regulates the shut-off of the survival factor NF-kappa B but, on the other hand, also impedes caspase-8-dependent apoptotic cell death so as to promote the persistence of pathogens.

Peptidase PepP is a novel virulence factor of Campylobacter jejuni contributing to murine campylobacteriosis - Heimesaat, Markus M.; Schmidt, Anna Maria; Mousavi, Soraya; Escher, Ulrike; Tegtmeyer, Nicole; Wessler, Silja; Gadermaier, Gabriele; Briza, Peter; Hofreuter, Dirk; Bereswill, Stefan; Backert, Steffen (Gut Microbes, 2020)
Mechanisms of host–pathogen interactions resulting in immunopathological responses upon human Campylobacter jejuni infection are not completely understood, but the recent availability of murine infection models mimicking key features of campylobacteriosis helps solving this dilemma. During a screen for proteases expressed by C. jejuni, we identified a peptidase of the M24 family as a potential novel virulence factor, which was named PepP. The gene is strongly conserved in various Campylobacter species. A constructed deletion mutant ΔpepP of C. jejuni strain 81–176 grew as efficiently compared to isogenic wild-type (WT) or pepP complemented bacteria. To shed light on the potential role of this protease in mediating immunopathological responses in the mammalian host, we perorally challenged microbiota-depleted IL-10−/- mice with these strains. All strains stably colonized the murine gastrointestinal tract with comparably high loads. Remarkably, pepP deficiency was associated with less severe induced malaise, with less distinct apoptotic and innate immune cell responses, but also with more pronounced proliferative/regenerative epithelial cell responses in the large intestine at d6 post-infection. Furthermore, pro-inflammatory mediators were lower in the colon, ileum, and mesenteric lymph nodes of mice that had been challenged with the ΔpepP mutant compared to the WT or pepP complemented strains. This also held true for extra-intestinal organs including liver, kidneys, and lungs, and, strikingly, to systemic compartments. Taken together, protease PepP is a novel virulence determinant involved in mediating campylobacteriosis. The finding that apoptosis in the colon is significantly diminished in mice infected with the pepP mutant highlights the epithelial layer as the first and main target of PepP in the intestine.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Campylobacteriosis; host–pathogen interaction; M24 peptidase family; pepP; pro-inflammatory immune responses; secondary abiotic IL-10; Xaa-Pro aminopeptidase

Peptidoglycan maturation enzymes affect flagellar functionality in bacteria - Roure, Sophie; Bonis, Mathilde; Chaput, Catherine; Ecobichon, Chantal; Mattox, Austin; Barriere, Charlotte; Geldmacher, Nina; Guadagnini, Stephanie; Schmitt, Christine; Prevost, Marie-Christine; Labigne, Agnes; Backert, Steffen; et al. (Molecular Microbiology, 2012)
The flagellar machinery is a highly complex organelle composed of a free rotating flagellum and a fixed stator that converts energy into movement. The assembly of the flagella and the stator requires interactions with the peptidoglycan layer through which the organelle has to pass for externalization. Lytic transglycosylases are peptidoglycan degrading enzymes that cleave the sugar backbone of peptidoglycan layer. We show that an endogenous lytic transglycosylase is required for full motility ofHelicobacter pylori and colonization of the gastric mucosa. Deficiency of motility resulted from a paralysed phenotype implying an altered ability to generate flagellar rotation. Similarly, another Gram-negative pathogen Salmonella typhimurium and the Gram-positive pathogen Listeria monocytogenes required the activity of lytic transglycosylases, Slt or MltC, and a glucosaminidase (Auto), respectively,for full motility. Furthermore, we show that in absence of the appropriate lytic transglycosylase theflagellar motor protein MotB from H. pylori does not localize properly to the bacterial pole.We present a new model involving the maturation of the surrounding peptidoglycan for the proper anchoring and functionality of the flagellar motor. © 2012 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Phage T4-like intermediates of DNA replication and recombination in the mitochondria of the higher plant Chenopodium album (L.). - Backert, Steffen; Börner, T. (Current Genetics, 2000)
We have studied intermediates of the recombination and replication of chromosomal mitochondrial (mt) DNA prepared from suspension cultured cells of Chenopodium album (L.) by electron microscopy during the whole growth cycle. We identified several types of potential recombination and replication intermediates including rosette-like structures, as well as other branched and sigma-like molecules. The absolute and relative amounts of these structures changed dramatically during the growth cycle, indicating high dynamics in the structural organization of the mt genome. The rosette-like molecules had sizes of 2-5 genome units and were found to contain putative replication forks and 'Holliday'-junctions known from recombination intermediates. The high number of rosettes during the first days of culture, and their drastic reduction in the stationary growth stage, were found to be inversely related to changes in the quantity of linear molecules of 40-200 kb. This observation suggests that linear molecules participate in the formation of giant branched rosette-like structures. Most linear molecules were previously found to have at least one single-stranded end, which may allow recombinative invasion of other double-stranded molecules. Thus, recombination events may lead to the formation of more complex molecules and initiate replication similar to phage T4. We propose the coexistence of a recombination-dependent mode of replication with a presumably recombination-independent rolling-circle mode of replication in the mitochondria of C. album.

Phosphorylation of tyrosine 972 of the Helicobacter pylori CagA protein is essential for induction of a scattering phenotype in gastric epithelial cells. - Backert, Steffen; Moese, S.; Selbach, M.; Brinkmann, V.; Meyer, Thomas F. (Molecular Microbiology, 2001)
Helicobacter pylori colonizes the human stomach and is the causative agent of a variety of gastric diseases. After bacterial attachment, the H. pylori CagA protein is translocated into gastric epithelial cells and tyrosine phosphorylated. This process is associated with characteristic cytoskeletal rearrangements, resulting in a scatter factor-like ('hummingbird') phenotype. In this study, using a cagA mutant complemented with wild-type cagA and transiently expressing CagA in AGS cells, we have demonstrated that translocated CagA is necessary for rearrangements of the actin cytoskeleton to occur. Anti-phosphotyrosine immunoblotting studies and treatment of infected cells with phosphotyrosine kinase inhibitors suggested that not only translocation but also phosphorylation of CagA is important in this process. Transient expression of CagA-green fluorescent protein (GFP) fusion proteins and two-dimensional gel electrophoresis of CagA protein species demonstrated tyrosine phosphorylation in the C-terminus. Site-directed mutagenesis of CagA revealed that tyrosine residue 972 is essential for induction of the cellular phenotype. We have also demonstrated that translocation and phosphorylation of CagA is necessary but not sufficient for induction of the hummingbird phenotype in AGS cells, indicating the involvement of as yet unidentified bacterial factor(s).

PKA-mediated phosphorylation of EPEC-Tir at serine residues 434 and 463: A novel pathway in regulating Rac1 GTPase function - Backert, Steffen; Kenny, Brendan; Gerhard, Ralf; Tegtmeyer, Nicole; Brandt, Sabine (Gut Microbes, 2010)
Type-III or type-IV secretion systems of many Gram-negative bacterial pathogens inject effector proteins into host cells that modulate cellular functions in their favour. A preferred target of these effectors is the actin-cytoskeleton as shown by studies using the gastric pathogens Helicobacter pylori (H. pylori) and enteropathogenic Escherichia coli (EPEC). We recently developed a co-infection approach to study effector protein function and molecular mechanisms by which they highjack cellular signalling cascades. This is exemplified by our observation that EPEC profoundly blocks H. pylori-induced epithelial cell scattering and elongation, a disease-related event requiring the activity of small Rho GTPase Rac1. While this suppressive effect is dependent on the effector protein Tir and the outer-membrane protein Intimin, it unexpectedly revealed evidence for Tir-signalling independent of phosphorylation of Tir at tyrosine residues 454 and 474. Instead, our studies revealed a previously unidentified function for protein kinase A (PKA)- mediated phosphorylation of Tir at serine residues 434 and 463. We demonstrated that EPEC infection activates PKA for Tir phosphorylation. Activated PKA then phosphorylates Rac1 at its serine residue 71 associated with reduced GTP-load and inhibited cell elongation. Phosphorylation of Rho GTPases such as Rac1 might be an interesting novel strategy in microbial pathogenesis. © 2010 Landes Bioscience.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; type III and type IV secretion; Virulence

Potential role of two Helicobacter pylori relaxases in DNA transfer? - Backert, Steffen; von Nickisch‐Rosenegk, Eva; Meyer, Thomas F. (Molecular Microbiology, 1998)
Created from Fastlane, Scopus look-up

Prevalence and spread of enterohepatic Helicobacter species in mice reared in a specific-pathogen-free animal facility - Bohr, U. R.M.; Selgrad, M.; Ochmann, C.; Backert, Steffen; König, Wolfgang; Fenske, A.; Wex, T.; Malfertheiner, P. (Journal of Clinical Microbiology, 2006)
Infections with enterohepatic Helicobacter species (EHS) can change the results of animal experiments. However, there is little information about the prevalence of EHS in noncommercial animal facilities. The aim of this study was to investigate the prevalence and the spread of EHS in specific-pathogen-free (SPF) mice. Fecal samples of 40 mouse lines were analyzed for members of the family Helicobacteraceae using a group-specific PCR targeting the 16S rRNA gene. Additional experiments were carried out to evaluate the spread of EHS among mice harbored in different caging systems. Helicobacter species were detected in 87.5% of the mouse lines tested. Five different Helicobacter species were identified: H. ganmani, H. hepaticus, H. typhlonicus, and the putative Helicobacter species represented by the isolates hamster B and MIT 98-5357. Helicobacter infection did not spread between animals in neighboring cages when individually ventilated cages were used; in contrast, when the mice were reared in open-air cages, EHS were found to spread from cage to cage. However, the spread was prevented by adding polycarbonate filter tops to the cages. When Helicobacter-negative and infected mice shared the same cage, transmission of the infection occurred in 100% within 2 weeks. Furthermore, we found that mice from commercial breeding facilities may carry undetected Helicobacter infections. Taken together, we show that infection with EHS may frequently occur and spread easily in mice reared under SPF conditions despite extensive safety precautions. Moreover, there is a high prevalence of rather uncommon Helicobacter species that may be a consequence of the current routine procedures used for health screening of SPF mice. Copyright © 2006, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Properties of the HtrA Protease From Bacterium Helicobacter pylori Whose Activity Is Indispensable for Growth Under Stress Conditions - Zarzecka, Urszula; Modrak-Wojcik, Anna; Figaj, Donata; Apanowicz, Malgorzata; Lesner, Adam; Bzowska, Agnieszka; Lipinska, Barbara; Zawilak-Pawlik, Anna; Backert, Steffen; Skorko-Glonek, Joanna (Frontiers in Microbiology, 2019)
The protease high temperature requirement A from the gastric pathogen Helicobacter pylori (HtrA(Hp)) belongs to the well conserved family of serine proteases. HtrA(Hp) is an important secreted virulence factor involved in the disruption of tight and adherens junctions during infection. Very little is known about the function of HtrA(Hp) in the H. pylori cell physiology due to the lack of htrA knockout strains. Here, using a newly constructed Delta htrA mutant strain, we found that bacteria deprived of HtrA(Hp) showed increased sensitivity to certain types of stress, including elevated temperature, pH and osmotic shock, as well as treatment with puromycin. These data indicate that HtrA(Hp) plays a protective role in the H. pylori cell, presumably associated with maintenance of important periplasmic and outer membrane proteins. Purified HtrA(Hp) was shown to be very tolerant to a wide range of temperature and pH values. Remarkably, the protein exhibited a very high thermal stability with the melting point (T-m) values of above 85 degrees C. Moreover, HtrA(Hp) showed the capability to regain its active structure following treatment under denaturing conditions. Taken together, our work demonstrates that HtrA is well adapted to operate under harsh conditions as an exported virulence factor, but also inside the bacterial cell as an important component of the protein quality control system in the stressed cellular envelope.
CRIS-Team WoS Importer:2019-05-21

Protease Activity of Campylobacter jejuni HtrA Modulates Distinct Intestinal and Systemic Immune Responses in Infected Secondary Abiotic IL-10 Deficient Mice - Schmidt, Anna-Maria; Escher, Ulrike; Mousavi, Soraya; Böhm, Manja; Backert, Steffen; Bereswill, Stefan; Heimesaat, Markus M. (Frontiers in Cellular and Infection Microbiology, 2019)
Even though human Campylobacter jejuni infections are progressively increasing worldwide, the underlying molecular mechanisms of pathogen-host-interactions are still not fully understood. We have recently shown that the secreted serine protease HtrA plays a key role in C. jejuni cellular invasion and transepithelial migration in vitro, and is involved in the onset of intestinal pathology in murine infection models in vivo. In the present study, we investigated whether the protease activity of HtrA had an impact in C. jejuni induced acute enterocolitis. For this purpose, we perorally infected secondary abiotic IL-10(-/-) mice with wildtype C. jejuni strain NCTC11168 (11168(WT))or isogenic bacteria carrying protease-inactive HtrA with a single point mutation at S197A in the active center (11168(HtrA-S197A)) Irrespective of the applied pathogenic strain, mice harbored similar C. jejuni loads in their feces and exhibited comparably severe macroscopic signs of acute enterocolitis at day 6 postinfection (p.i.). Interestingly, the 11168(HtrA-S197A) infected mice displayed less pronounced colonic apoptosis and immune cell responses, but enhanced epithelial proliferation as compared to the 11168(WT) strain infected controls. Furthermore, less distinct microscopic sequelae in 11168(HtrA-S197A) as compared to parental strain infected mice were accompanied by less distinct colonic secretion of pro-inflammatory cytokines such as MCP-1, IL-6, TNF, and IFN-gamma in the former as compared to the latter. Strikingly, the S197A point mutation was additionally associated with less pronounced systemic pro-inflammatory immune responses as assessed in serum samples. In conclusion, HtrA is a remarkable novel virulence determinant of C. jejuni, whose protease activity is not required for intestinal colonization and establishment of disease, but aggravates campylobacteriosis by triggering apoptosis and pro-inflammatory immune responses.
CRIS-Team WoS Importer:2019-04-12

Quantification of serine protease HtrA molecules secreted by the foodborne pathogen Campylobacter jejuni - Neddermann, Matthias; Backert, Steffen (Gut Pathogens, 2019)
Background: Campylobacter jejuni is a major food-borne pathogen and a worldwide health threat. Utilizing different virulence factors, C. jejuni invades the host's intestinal epithelial cell layer. One important factor in this process is the serine protease HtrA, which is secreted into the extracellular space, and helps the bacteria to transmigrate across the gut epithelium by cleaving various cell-cell adhesion proteins. The aim of the present study is to quantify the amount of HtrA molecules secreted per bacterial cell in liquid culture and during infection.
CRIS-Team WoS Importer:2019-04-30

Quorum sensing dependent phenotypes and their molecular mechanisms inCampylobacterales - Gölz, Greta; Sharbati, S.; Backert, Steffen; Alter, T. (European Journal of Microbiology and Immunology, 2012)
Quorum sensing comprises the mechanism of communication between numerous bacteria via small signalling molecules, termed autoinducers (AI). Using quorum sensing, bacteria can regulate the expression of multiple genes involved in virulence, toxin production, motility, chemotaxis and biofilm formation, thus contributing to adaptation as well as colonisation. The current understanding of the role of quorum sensing in the lifecycle of Campylobacterales is still incomplete. Campylobacterales belong to the class of Epsilonproteobacteria representing a physiologically and ecologically diverse group of bacteria that are rather distinct from the more commonly studied Proteobacteria, such as Escherichia and Salmonella. This review summarises the recent knowledge on distribution and production of AI molecules, as well as possible quorum sensing dependent regulation in the mostly investigated species within the Campylobacterales group: Campylobacter jejuni and Helicobacter pylori.<br
Keywords: quorum sensing; LuxS; AI-2; Campylobacter; Helicobacter

Rapid Detection of Quinolone Resistance Mutations in gyrA of Helicobacter pylori by Real-Time PCR - Haumaier, Franziska; Schneider-Fuchs, Anna; Backert, Steffen; Sterlacci, William; Wöhrl, Birgitta M.; Vieth, Michael (Pathogens, 2022)
The treatment of infections by the gastric pathogen Helicobacter pylori (H. pylori) has become more difficult due to increased rates of resistances against various antibiotics. Typically, atriple ther-apy, employing a combination of at least two antibiotics and a proton pump inhibitor, is used to cure H. pylori infections. In case of first-line therapy failure, quinolones are commonly applied in a second-line therapy. To prevent second-line treatment failures, we developed an improved method to detect the most common quinolone-resistance mutations located in the quinolone-resistance-determining region (QRDR) of the bacterial gyrA gene. Biopsy material from the gastric mucosa of infected patients was used to identify quinolone-resistant strains before the onset of drug administration. Two different wild-type and six mutant QRDR sequences were included. Melting curve analyses were performed with corresponding gyrA plasmid DNAs using a real-time polymerase chain reaction (RT-PCR) assay. By applying a combination of only two different fluorescent probes, this assay allows wild-type sequences to be unambiguously distinguished from all known mutant QRDR sequences of H. pylori. Next, the Tm values of patient DNAs were established, and the genotypes were confirmed by sequencing. Thus, quinolone-resistant H. pylori strains can be easily and quickly diagnosed before treatment, which will help to avoid the administration of ineffective drug regimes.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Antibiotic resistance; FRET; GyrA; Helicobacter pylori; QRDR mutation diagnosis; Quinolone resistance; RT-PCR

Rapid paracellular transmigration of Campylobacter jejuni across polarized epithelial cells without affecting TER: Role of proteolytic-active HtrA cleaving E-cadherin but not fibronectin - Boehm, Manja; Hoy, Benjamin; Rohde, Manfred; Tegtmeyer, Nicole; Baek, Kristoffer T.; Oyarzabal, Omar A.; Brondsted, Lone; Wessler, Silja; Backert, Steffen (Gut Pathogens, 2012)
Background: Campylobacter jejuni is one of the most important bacterial pathogens causing food-borne illness worldwide. Crossing the intestinal epithelial barrier and host cell entry by C. jejuni is considered the primary reason of damage to the intestinal tissue, but the molecular mechanisms as well as major bacterial and host cell factors involved in this process are still widely unclear. Results: In the present study, we characterized the serine protease HtrA (high-temperature requirement A) of C. jejuni as a secreted virulence factor with important proteolytic functions. Infection studies and in vitro cleavage assays showed that C. jejunis HtrA triggers shedding of the extracellular E-cadherin NTF domain (90 kDa) of non-polarised INT-407 and polarized MKN-28 epithelial cells, but fibronectin was not cleaved as seen for H. pyloris HtrA. Deletion of the htrA gene in C. jejuni or expression of a protease-deficient S197A point mutant did not lead to loss of flagella or reduced bacterial motility, but led to severe defects in E-cadherin cleavage and transmigration of the bacteria across polarized MKN-28 cell layers. Unlike other highly invasive pathogens, transmigration across polarized cells by wild-type C. jejuni is highly efficient and is achieved within a few minutes of infection. Interestingly, E-cadherin cleavage by C. jejuni occurs in a limited fashion and transmigration required the intact flagella as well as HtrA protease activity, but does not reduce transepithelial electrical resistance (TER) as seen with Salmonella, Shigella, Listeria or Neisseria. Conclusion: These results suggest that HtrA-mediated E-cadherin cleavage is involved in rapid crossing of the epithelial barrier by C. jejuni via a very specific mechanismusing the paracellular route to reach basolateral surfaces, but does not cleave the fibronectin receptor which is necessary for cell entry. © 2012 Boehm et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Cellular invasion; E-cadherin; Fibronectin; HtrA; MKN-28; Molecular pathogenesis; Signaling; TER; Virulence

Regulation of mucin MUC2 gene expression during colon carcinogenesis - Gratchev, A.; Böhm, C.; Riede, E.; Foss, H. D.; Hummel, Michael; Mann, Benno; Backert, Steffen; Buhr, H. J.; Stein, H.; Riecken, E. O.; Hanski, C. (Annals of the New York Academy of Sciences, 1998)
Created from Fastlane, Scopus look-up

R-loop-dependent rolling-circle replication and a new model for DNA concatemer resolution by mitochondrial plasmid mp1. - Backert, Steffen (EMBO Journal, 2002)
The mitochondrial (mt) plasmid mp1 of Chenopodium album replicates by a rolling-circle (RC) mechanism initiated at two double-stranded replication origins (dso1 and dso2). Two-dimensional gel electrophoresis and electron microscopy of early mp1 replication intermediates revealed novel spots. Ribonucleotide (R)-loops were identified at dso1, which function as a precursor for the RCs in vivo and in vitro. Bacteriophage T4-like networks of highly branched mp1 concatemers with up to 20 monomer units were mapped and shown to be mainly formed by replicating, invading, recombining and resolving molecules. A new model is proposed in which concatemers were separated into single units by a "snap-back" mechanism and homologous recombination. dso1 is a recombination hotspot, with sequence homology to bacterial Xer recombination cores. mp1 is a unique eukaryotic plasmid that expresses features of phages like T4 and could serve as a model system for replication and maintenance of DNA concatemers.

Role of Abl and Src family kinases in actin-cytoskeletal rearrangements induced by the Helicobacter pylori CagA protein - Tegtmeyer, Nicole; Backert, Steffen (European Journal of Cell Biology, 2011)
The clinical outcome of infections with Helicobacter pylori is determined by a complex interplay of host-pathogen interactions, and persistent infection with this pathogen is the major cause of developing chronic gastritis, peptic ulcers and gastric cancer. Highly virulent strains encode a so-called type IV secretion system which translocates the CagA effector protein into gastric epithelial target cells. Injected CagA becomes tyrosine-phosphorylated on EPIYA sequence motifs by Src and Abl family kinase members. CagA then binds to and activates/inactivates various signalling proteins in a phosphorylation-dependent and phosphorylation-independent manner. In this way injected CagA can act as a master key that evolved during evolution the ability to highjack multiple downstream signalling cascades. Here we review our knowledge on the tyrosine phosphorylation motifs in CagA, the recent advances in the interaction of CagA with Src and Abl tyrosine kinases and their role in signalling events leading to changes of the phosphorylation status of actin-binding proteins cortactin, ezrin and vinculin followed by actin-cytoskeletal rearrangements, cell scattering and elongation. Detailed investigation of these pathways will help to yield novel insights and to elucidate the mechanisms of H. pylori-induced pathogenesis. © 2010 Elsevier GmbH.
Created from Fastlane, Scopus look-up
Keywords: Abl; CagA; CagPAI; Cancer; Cortactin; Csk; Ezrin; Helicobacter pylori; Signalling; Src; Type IV secretion; Tyrosine kinases; Vacuolating cytotoxin; Vinculin

Role of CEACAM members 1 and 5 in type IV secretion of the effector protein CagA by Helicobacter pylori - Tegtmeyer, Nicole; Backert, Steffen (HELICOBACTER, 2019)
CRIS-Team WoS Importer:2019-10-04

Role of the cag-pathogenicity island encoded type IV secretion system in Helicobacter pylori pathogenesis - Tegtmeyer, Nicole; Wessler, Silja; Backert, Steffen (Febs Journal, 2011)
Helicobacter pylori is a very successful human-specific bacterium worldwide. Infections of the stomach with this pathogen can induce pathologies, including chronic gastritis, peptic ulcers and even gastric cancer. Highly virulent H. pylori strains encode the cytotoxin-associated gene (cag)-pathogenicity island, which expresses a type IV secretion system (T4SS). This T4SS forms a syringe-like pilus structure for the injection of virulence factors such as the CagA effector protein into host target cells. This is achieved by a number of T4SS proteins, including CagI, CagL, CagY and CagA, which by itself binds the host cell integrin member β1 followed by delivery of CagA across the host cell membrane. A role of CagA interaction with phosphatidylserine has also been shown to be important for the injection process. After delivery, CagA becomes phosphorylated by oncogenic tyrosine kinases and mimics a host cell factor for the activation or inactivation of some specific intracellular signalling pathways. We review recent progress aiming to characterize the CagA-dependent and CagA-independent signalling capabilities of the T4SS, which include the induction of membrane dynamics, disruption of cell-cell junctions and actin-cytoskeletal rearrangements, as well as pro-inflammatory, cell cycle-related and anti-apoptotic transcriptional responses. The contribution of these signalling pathways to pathogenesis during H. pylori infections is discussed. © 2011 The Authors Journal compilation © 2011 FEBS.
Created from Fastlane, Scopus look-up
Keywords: Helicobacter pylori; signalling; type IV secretion; VirB10; VirB5

Role of the small Rho GTPases Rac1 and Cdc42 in host cell invasion of Campylobacter jejuni - Krause-Gruszczynska, Malgorzata; Rohde, Manfred; Hartig, Roland; Genth, Harald; Schmid, Gudula; Keo, Thormika; König, Wolfgang; Miller, William G.; Konkel, Michael E.; Backert, Steffen (Cellular Microbiology, 2007)
Host cell invasion of the food-borne pathogen Campylobacter jejuni is one of the primary reasons of tissue damage in humans but molecular mechanisms are widely unclear. Here, we show that C. jejuni triggers membrane ruffling in the eukaryotic cell followed by invasion in a very specific manner first with its tip followed by the flagellar end. To pinpoint important signalling events involved in the C.jejuni invasion process, we examined the role of small Rho family GTPases. Using specific GTPase-modifying toxins, inhibitors and GTPase expression constructs we show that Rac1 and Cdc42, but not RhoA, are involved in C.jejuni invasion. In agreement with these observations, we found that internalization of C.jejuni is accompanied by a time-dependent activation of both Rac1 and Cdc42. Finally, we show that the activation of these GTPases involves different host cell kinases and the bacterial fibronectin-binding protein CadF. Thus, CadF is a bifunctional protein which triggers bacterial binding to host cells as well as signalling leading to GTPase activation. Collectively, our results suggest that C.jejuni invade host target cells by a unique mechanism and the activation of the Rho GTPase members Rac1 and Cdc42 plays a crucial role in this entry process. © 2007 The Authors; Journal compilation © 2007 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Role of type IV secretion in Helicobacter pylori pathogenesis - Backert, Steffen; Selbach, Matthias (Cellular Microbiology, 2008)
Helicobacter pylori is a highly successful human-specific gastric pathogen that colonizes more than half the world's population. Infection with this bacterium can induce gastric pathologies ranging from chronic gastritis to peptic ulcers and even cancer. Virulent H. pylori isolates harbour the cag (cytotoxin-associated genes) pathogenicity island, a 40kb stretch of DNA that encodes components of a type IV secretion system (T4SS). This T4SS forms a pilus for the injection of virulence factors into host target cells such as the CagA oncoprotein. This is accomplished by a specialized adhesin of the pilus surface, the CagL protein, which binds to and activates host cell integrins for subsequent delivery of CagA across the host cell membrane. Injected CagA becomes tyrosine-phosphorylated by Src and Abl family kinases and mimics a host cell protein in binding and activation of multiple signalling factors. Here we review the recent advances in the characterization of phosphorylation-dependent and phosphorylation-independent signalling activities of CagA and the T4SS which include the induction of membrane dynamics, actin cytoskeletal rearrangements and the disruption of cell-to-cell junctions as well as proliferative, pro-inflammatory and anti-apoptotic nuclear responses. The contribution of these signalling cascades to H. pylori pathogenesis is discussed. © 2008 The Authors Journal compilation © 2008 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

Roles of the cagPAI and CagA on gastroduodenal diseases - Backert, Steffen; Zanotti, Giuseppe; Lind, Judith; Asche, Carmen Isabell; Tegtmeyer, Nicole (Helicobacter pylori Research: From Bench to Bedside, 2016)
Helicobacter pylori is a highly successful human-specific Gram-negative bacterium. Infections with this pathogen in the stomach can induce pathologies ranging from chronic gastritis, peptic ulcers, to gastric cancer. Highly virulent H. pylori isolates harbor the cytotoxin-associated genes (cag) pathogenicity island, which encodes a typical type IV secretion system (T4SS). This T4SS constitutes a syringe-like pilus structure for the translocation of virulence factors such as the CagA effector protein into gastric epithelial and immune cells. This is achieved by a number of T4SS proteins such as CagL, CagI, CagY, and CagA, which can interact with the host cell integrin member α5β1 followed by transport of CagA across the host cell membrane. After delivery, CagA undergoes phosphorylation by oncogenic tyrosine kinases and mimics a host factor for the activation or inactivation of multiple intracellular signaling cascades. Here we review the current status in the characterization of phosphorylation-dependent and phosphorylation-independent signaling events by CagA and the CagA-independent T4SS activities in vivo and in vitro, which include the induction of membrane dynamics, actin-cytoskeletal rearrangements, disruption of cell-to-cell junctions, as well as pro-inflammatory, proliferative and anti-apoptotic nuclear responses. The contribution of these signaling pathways to pathogenesis during H. pylori infection is discussed.
Created from Fastlane, Scopus look-up
Keywords: Gastric cancer; Helicobacter pylori; Infection; Inflammasome; SH2 domain; Signaling; Type IV secretion; Tyrosine kinase; VirB1—VirB11; VirD4

Rolling-circle replication of mitochondrial DNA in the higher plant Chenopodium album (L.) - Backert, Steffen; Dörfel, Peter; Lurz, Rudi; Börner, Thomas (Molecular and Cellular Biology, 1996)
The mitochondrial genomes of higher plants are larger and more complex than those of all other groups of organisms. We have studied the in vivo replication of chromosomal and plasmid mitochondrial DNAs prepared from a suspension culture and whole plants of the dicotyledonous higher plant Chenopodium album (L.). Electron microscopic studies revealed sigma-shaped, linear, and open circular molecules (subgenomic circles) of variable size as well as a minicircular plasmid of 1.3 kb (mp1). The distribution of single- stranded mitochondrial DNA in the sigma structures and the detection of entirely single-stranded molecules indicate a rolling-circle type of replication of plasmid mp1 and subgenomic circles. About half of the sigma- like molecules had tails exceeding the lengths of the corresponding circle, suggesting the formation of concatemers. Two replication origins (nicking sites) could be identified on mp1 by electron microscopy and by a new approach based on the mapping of restriction fragments representing the identical 5' ends of the tails of sigma-like molecules. These data provide, for the first time, evidence for a rolling-circle mode of replication in the mitochondria of higher plants.
Created from Fastlane, Scopus look-up

Selective upregulation of endothelial E-selectin in response to Helicobacter pylori-induced gastritis - Svensson, Helena; Hansson, Malin; Kilhamn, Jan; Backert, Steffen; Quiding-Jarbrink, Marianne (Infection and Immunity, 2009)
Helicobacter pylori is one of the most common bacterial pathogens, infecting up to 50% of the world's population. The host is not able to clear the infection, leading to life-long chronic inflammation with continuous infiltration of lymphocytes and granulocytes. The migration of leukocytes from the blood into inflamed tissue is dependent on adhesion molecules expressed on the vascular endothelium. The aim of this study was to characterize the effect of H. pylori-induced gastritis with regard to the expression of endothelial adhesion molecules in the gastric mucosa and compare this to other types of chronic mucosal inflammations. Our results demonstrate an increased level of expression of the adhesion molecule E-selectin, but not of intracellular adhesion molecule 1, vascular adhesion molecule 1, or vascular adhesion protein 1, in H. pylori-induced gastritis but not in gastritis induced by acetylsalicylic acid or pouchitis. The upregulated E-selectin expression was determined to be localized to the gastric mucosa rather than being a systemic response to the infection. Moreover, the H. pylori type IV secretion system encoded by the cag pathogenicity island (cagPAI) was found to be an important determinant for the upregulation of human endothelial E-selectin expression in vitro, and this process is probably dependent on the CagL protein, mediating binding to α5β1 integrins. Thus, endothelial E-selectin expression induced by H. pylori probably contributes to the large influx of neutrophils and macrophages seen in infected individuals, and our results suggest that this process may be more pronounced in patients infected with cagPAI-positive H. pylori strains and may thereby contribute to tissue damage in these individuals. Copyright © 2009, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

Separation of different conformations of plant mitochondrial DNA molecules by field inversion gel electrophoresis - Scissum-Gunn, Karyn D.; Gandhi, Medha; Backert, Steffen; Nielsen, Brent Lynn (Plant Molecular Biology Reporter, 1998)
Mitochondrial (mt) DNA structure in higher plants is still unclear as to the circularity or linearity of the genome. We have developed a system to electrophoretically separate distinct populations of mtDNA, with some populations enriched for networked linear and circular DNA molecules. Using field inversion gel electrophoresis (FIGE) and electron microscopy (EM), we have identified four distinct populations of mtDNA from two Brassica species. Using FIGE, two slow migrating mtDNA populations ran faster than a 66 kbp Escherichia coli circular plasmid marker, while these same populations comigrated in the compression zone in contour-clamped homogeneous electrophoretic field (CHEF) gels. A fast-migrating mtDNA population was also resolved by FIGE as a diffuse band between 20 to 70 kbp when compared with linear lambda (lambda) markers. FIGE resolved the 66 kbp circular marker into several multimers, while CHEF resolved only open-circular monomers and linears. In agreement with FIGE results, EM analysis indicated the two slow migrating mtDNA populations contained circular (both supercoiled and relaxed circles) and free linear molecules of 10-60 kbp, and networked linear molecules of 45-140 kbp total size that may represent recombination intermediates. The fast migrating population consisted of 10-50 kbp linear molecules. Well-bound mtDNA showed only long linear molecules of 40-150 kbp with no detection of circles or complex/rosette molecules. This report shows that FIGE has clear advantages over CHEF for separating large DNA molecules with different conformations, and may be very useful for studies to characterize genome structure in complex systems such as plant mitochondria.
Keywords: field inversion gel electrophoresis; genome structure; plant mitochondrial DNA

Serine phosphorylation of cortactin controls focal adhesion kinase activity and cell scattering induced by Helicobacter pylori - Tegtmeyer, Nicole; Wittelsberger, Ruth; Hartig, Roland; Wessler, Silja; Martinez-Quiles, Narcisa; Backert, Steffen (Cell Host & Microbe, 2011)
Cell migration and invasion require the coordinated regulation of cytoskeletal architectural changes by signaling factors, including the actin-binding protein cortactin. Bacterial and viral pathogens subvert these signaling factors to promote their uptake, spread and dissemination. We show that the gastric pathogen Helicobacter pylori (Hp) targets cortactin by two independent processes leading to its tyrosine dephosphorylation and serine phosphorylation to regulate cell scattering and elongation. The phosphorylation status of cortactin dictates its subcellular localization and signaling partners. Upon infection, cortactin was found to interact with and stimulate the kinase activity of focal adhesion kinase (FAK). This interaction required the SH3 domain and phosphorylation of cortactin at serine 405 and a proline-rich sequence in FAK. Using Hp as a model, this study unravels a previously unrecognized FAK activation pathway. We propose that Hp targets cortactin to protect the gastric epithelium from excessive cell lifting and ensure sustained infection in the stomach. © 2011 Elsevier Inc.
Created from Fastlane, Scopus look-up

SHP2-Independent Tyrosine Dephosphorylation of Cortactin and Vinculin during Infection with Helicobacter pylori - Knorr, Jakob; Backert, Steffen; Tegtmeyer, Nicole (European Journal of Microbiology and Immunology, 2020)
The gastric pathogen Helicobacter pylori colonizes approximately half of the hUMan world population. The bacterium injects the effector protein cytotoxin associated gene A (CagA) via a type-IV secretion system into host epithelial cells, where the protein becomes phosphorylated at specific EPIYA-motifs by cellular kinases. Inside the host cell, CagA can interact with over 25 different proteins in both phosphorylation-dependent and phosphorylation-independent manners, resulting in manipulation of host-cell signaling pathways. During the course of an H. pylori infection, certain host-cell proteins undergo tyrosine dephosphorylation in a CagA-dependent manner, including the actin-binding proteins cortactin and vinculin. A predominant response of intracellular CagA is the binding and activation of tyrosine phosphatase, the human Src-homology-region-2-domain-containing-phosphatase2 (SHP2). Here, we considered the possibility that activated SHP2 might be responsible for the dephosphorylation of cortactin and vinculin. To investigate this, phosphatase inhibitor studies were performed. Additionally, a complete knockout mutant of SHP2 in AGS cells was created by CRISPR/Cas9 technology, and these cells were infected with H. pylori. however, neither the presence of an inhibitor nor the inactivation of SHP2 prevented the dephosphorylation of cortactin and vinculin upon CagA delivery. Tyrosine dephosphorylation of these proteins is therefore independent of SHP2 and instead must be caused by another, as yet unidentified, protein tyrosine phosphatase.
CRIS-Team WoS Importer:2020-06-16

Signal transduction of Helicobacter pylori during interaction with host cell protein receptors of epithelial and immune cells - Suneesh Kumar, Pachathundikandi; Tegtmeyer, Nicole; Backert, Steffen (Gut Microbes, 2013)
Helicobacter pylori infections can induce pathologies ranging from chronic gastritis, peptic ulceration to gastric cancer. Bacterial isolates harbor numerous well-known adhesins, vacuolating cytotoxin VacA, protease HtrA, urease, peptidoglycan, and type IV secretion systems (T4SS). It appears that H. pylori targets more than 40 known host protein receptors on epithelial or immune cells. A series of T4SS components such as CagL, CagI, CagY, and CagA can bind to the integrin α5β1 receptor. Other targeted membrane-based receptors include the integrins αvβ3, αvβ5, and β2 (CD18), RPTP- α/β, GP130, E-cadherin, fibronectin, laminin, CD46, CD74, ICAM1/LFA1, T-cell receptor, Toll-like receptors, and receptor tyrosine kinases EGFR, ErbB2, ErbB3, and c-Met. In addition, H. pylori is able to activate the intracellular receptors NOD1, NOD2, and NLRP3 with important roles in innate immunity. Here we review the interplay of various bacterial factors with host protein receptors. The contribution of these interactions to signal transduction and pathogenesis is discussed. © 2013 Landes Bioscience.
Created from Fastlane, Scopus look-up
Keywords: c-Met; E-cadherin; EGF receptor; Integrins; Molecular pathogenesis; Virulence

Specific entry of Helicobacter pylori into cultured gastric epithelial cells via a zipper-like mechanism. - Kwok, T.; Backert, Steffen; Schwarz, H.; Berger, J.; Meyer, Thomas F. (Infection and Immunity, 2002)
Although Helicobacter pylori has generally been considered an extracellular pathogen, a number of in vitro infection experiments and biopsy examinations have shown that it is capable of occasionally entering mammalian host cells. Here, we characterized this entry process by using AGS cells as a host cell model. In gentamicin protection-invasion assays, the number of H. pylori colonies recovered was lower than that for Salmonella enterica serovar Typhimurium X22, Escherichia coli expressing InvA, and Yersinia enterocolitica YO:9 grown at 25 degrees C but higher than that for Neisseria gonorrhoeae VP1 and Y. enterocolitica YO:9 grown at 37 degrees C. At the ultrastructural level, the entry process was observed to occur via a zipper-like mechanism. Internalized H. pylori was bound in tight LAMP-1-containing vacuoles in close association with condensed filamentous actin and tyrosine phosphorylation signals. Wortmannin, a potent inhibitor of phosphatidylinositol 3-kinase, and calphostin C, an inhibitor of protein kinase C, both inhibited the entry of H. pylori in a sensitive and dose-dependent manner; however, the level of entry was enhanced by sodium vanadate, an inhibitor of tyrosine phosphatases and ATPases. Furthermore, the cytokine tumor necrosis factor alpha antagonized the entry of H. pylori into AGS cells. Collectively, these results demonstrate that the entry of H. pylori into AGS cells occurs via a zipper-like mechanism which involves various host signal transduction events.

Specific high affinity interaction of Helicobacter pylori CagL with integrin αVβ6 promotes type IV secretion of CagA into human cells - Buß, Maren; Tegtmeyer, Nicole; Schnieder, Jennifer; Dong, Xianchi; Li, Jing; Springer, Timothy A.; Backert, Steffen; Niemann, Hartmut H. (Febs Journal, 2019)
CagL is an essential pilus surface component of the virulence-associated type IV secretion system (T4SS) employed by Helicobacter pylori to translocate the oncogenic effector protein CagA into human gastric epithelial cells. CagL contains an RGD motif and integrin α5β1 is widely accepted as its host cell receptor. Here, we show that CagL binds integrin αVβ6 with substantially higher affinity and that this interaction is functionally important. Cell surface expression of αVβ6 on various cell lines correlated perfectly with cell adhesion to immobilized CagL and with binding of soluble CagL to cells. We found no such correlation for α5β1. The purified αVβ6 ectodomain bound CagL with high affinity. This interaction was highly specific, as the affinity of CagL for other RGD-binding integrins was two to three orders of magnitude weaker. Mutation of either conserved leucine in the CagL RGDLXXL motif, a motif that generally confers specificity for integrin αVβ6 and αVβ8, lowered the affinity of CagL for αVβ6. Stable expression of αVβ6 in αVβ6-negative but α5β1-expressing human cells promoted two hallmarks of the functional H. pylori T4SS, namely translocation of CagA into host cells and induction of interleukin-8 secretion by host cells. These findings suggest that integrin αVβ6, although not essential for T4SS function, represents an important host cell receptor for CagL.
CRIS-Team Scopus Importer:2019-07-09
Keywords: CagL; Helicobacter pylori; integrin α; RGD motif; type IV secretion

Specific identification of Campylobacter fetus by PCR targeting variable regions of the 16S rDNA - Oyarzabal, Omar A.; Wesley, Irene Varelas; Harmon, Karen M.; Schroeder-Tucker, Linda C.; Barbaree, James M.; Lauerman, Lloyd H.; Backert, Steffen; Conner, Donald E. (Veterinary Microbiology, 1997)
Campylobacter fetus is recognized as a human and animal pathogen. The isolation and differentiation of C. fetus in diagnostic laboratories is hindered by its relatively slow growth and lack of distinguishing biochemical characteristics. We developed a fast, reliable PCR assay that specifically amplifies a 554-bp segment of the 16S rDNA from C. fetus. Fifty-two ATCC reference strains and 255 bacterial field isolates comprising the genera Campylobacter, Arcobacter, Helicobacter, Escherichia, Listeria, Salmonella, and Wolinella were evaluated using this PCR protocol. Only, C. fetus strains were amplified. Sequence analysis of amplicons from ATCC and field strains of C. fetus confirmed the presence of the target DNA fragment. The detection limit of the technique was 5.9 x 103 CFU/ml. This PCR assay can yield reliable detection of C fetus within 3 h after isolation of presumptive colonies on agar plates.
Created from Fastlane, Scopus look-up
Keywords: 16S rRNA; Campylobacter fetus; Diagnosis-bacteria; PCR

Src is the kinase of the Helicobacter pylori CagA protein in vitro and in vivo. - Selbach, M.; Moese, S.; Meyer, Thomas F.; Hauck, CR; Backert, Steffen (Journal of Biological Chemistry, 2002)
The gastric pathogen Helicobacter pylori uses a type IV secretion system to inject the bacterial CagA protein into gastric epithelial cells. Within the host cell, CagA becomes phosphorylated on tyrosine residues and initiates cytoskeletal rearrangements. We demonstrate here that Src-like protein-tyrosine kinases mediate CagA phosphorylation in vitro and in vivo. First, the Src-specific tyrosine kinase inhibitor PP2 specifically blocks CagA phosphorylation and cytoskeletal rearrangements thereby inhibiting the CagA-induced hummingbird phenotype of gastric epithelial cells. Second, CagA is in vivo phosphorylated by transiently expressed c-Src. Third, recombinant c-Src and lysates derived from c-Src-expressing fibroblasts but not lysates derived from Src-, Yes-, and Fyn-deficient cells phosphorylated CagA in vitro. Fourth, a transfected CagA-GFP fusion protein is phosphorylated in vivo in Src-positive fibroblasts but not in Src-, Yes-, and Fyn-deficient cells. Because a CagA-GFP fusion protein mutated in an EPIYA motif is not efficiently phosphorylated in any of these fibroblast cells, the CagA EPIYA motif appears to constitute the major c-Src phosphorylation site conserved among CagA-positive Helicobacter strains.

Strain-specific expression profiles of virulence genes in Helicobacter pylori during infection of gastric epithelial cells and granulocytes - Gieseler, Steffi; König, Brigitte; König, Wolfgang; Backert, Steffen (Microbes and Infection, 2005)
Helicobacter pylori expresses a variety of known virulence-associated factors, whose expression is likely to be dependent on the ecological niche of this pathogen. Here, we compared the temporal changes in the level of virulence-associated gene transcription in H. pylori strains isolated from patients with different pathology. Our aim was to study the coordinated gene expression profiles of these virulence factors during infection of AGS gastric epithelial cells and granulocytes. Using real-time quantitative (TaqMan) RT-PCR, we determined the mRNA expression of cagA, ureA, napA, katA, vacAs1 and vacAs2 alleles in a time course up to 6:h. The expression profiles of the investigated genes vary according to the strain, and were mainly either upregulated or unchanged upon bacterial contact with AGS cells. In contrast, upon contact with granulocytes, the majority of the genes were repressed in H. pylori. The following major results were obtained: (i) genetically diverse H. pylori exhibit different mRNA expression profiles, (ii) the expression patterns were strain-specific and time-dependent and (iii) the regulation of expression profiles was host cell dependent. These data were statistically significant and suggest that contact with target cells leads to an active cross-talk between the pathogen and its host. The use of Taqman-PCR to analyse the expression of mRNA of a bacterial pathogen in response to a changing host environment enabled us to identify variable and strain-specific transcription profiles in a sensitive and reproducible manner. © 2005 Elsevier SAS. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Molecular pathogenesis; Pathogenicity island; Type IV secretion; Virulence

Strand switching during rolling circle replication of plasmid-like DNA circles in the mitochondria of the higher plant Chenopodium album (L.). - Backert, Steffen (Plasmid, 2000)
The structure of sigma-like mitochondrial DNA molecules prepared from suspension cultured cells of Chenopodium album (L.) was studied by electron microscopy. These molecules were highly variable in size, ranging from about 1 to 104 kb, and had single- and double-stranded regions typical for rolling circle replicating intermediates. Partial denaturation studies confirmed that these structures constitute rolling circles. Close inspection of the circle-tail junctions of the replication fork at high magnification suggests that in circles with a double-stranded tail, both strands of the tail seem to be covalently attached to the circle in about 27% of the molecules. This observation can be explained by a phenomenon called strand switching or strand splippage during rolling circle replication, similar to a mechanism proposed for bacterial replicons or in vitro replicating constructs harboring bacteriophage T4 replication origins.

Structure of a three-dimensional domain-swapped dimer of the Helicobacter pylori type IV secretion system pilus protein CagL - Barden, Stephan; Schomburg, Benjamin; Conradi, Jens; Backert, Steffen; Sewald, Norbert; Niemann, Hartmut H. (Acta Crystallographica Section D: Biological Crystallography, 2014)
A new crystal form of the Helicobacter pylori type IV secretion system (T4SS) pilus protein CagL is described here. In contrast to two previously reported monomeric structures, CagL forms a three-dimensional domain-swapped dimer. CagL dimers can arise during refolding from inclusion bodies or can form spontaneously from purified monomeric CagL in the crystallization conditions. Monomeric CagL forms a three-helix bundle, with which the N-terminal helix is only loosely associated. In the new crystal form, the N-terminal helix is missing. The domain swap is owing to exchange of the C-terminal helix between the two protomers of a dimer. A loop-to-helix transition results in a long helix of 108 amino acids comprising the penultimate and the last helix of the monomer. The RGD motif of dimeric CagL adopts an -helical conformation. In contrast to the previously reported structures, the conserved and functionally important C-terminal hexapeptide is resolved. It extends beyond the three-helix bundle as an exposed helical appendage. This new crystal form contributes to the molecular understanding of CagL by highlighting rigid and flexible regions in the protein and by providing the first view of the C-terminus. Based on the structural features, a previously unrecognized homology between CagL and CagI is discussed. © 2014 International Union of Crystallography.
Created from Fastlane, Scopus look-up
Keywords: CagL; three-dimensional domain swapping

Subproteomes of soluble and structure-bound Helicobacter pylori proteins analyzed by two-dimensional gel electrophoresis and mass spectrometry - Backert, Steffen; Kwok, Terry; Schmid, Monika; Seibach, Matthias; Moese, Stefan; Peek, Richard M.; König, Wolfgang; Meyer, Thomas F.; Jungblut, Peter R. (Proteomics, 2005)
Helicobacter pylori is one of the most common bacterial pathogens and causes a variety of diseases, such as peptic ulcer or gastric cancer. Despite intensive study of this human pathogen in the last decades, knowledge about its membrane proteins and, in particular, those which are putative components of the type IV secretion system encoded by the cag pathogenicity island (PAI) remains limited. Our aim is to establish a dynamic two-dimensional electrophoresis- polyacrylamide gel electrophoresis (2-DE-PAGE) database with multiple subproteomes of H. pylori (http://www.mpiib-berlin.mpg.de/2D-PAGE) which facilitates identification of bacterial proteins important in pathogen-host interactions. Using a proteomic approach, we investigated the protein composition of two H. pylori fractions: soluble proteins and structure-bound proteins (including membrane proteins). Both fractions differed markedly in the overall protein composition as determined by 2-DE. The 50 most abundant protein spots in each fraction were identified by peptide mass fingerprinting. We detected four cag PAI proteins, numerous outer membrane proteins (OMPs), the vacuolating cytotoxin VacA, other potential virulence factors, and few ribosomal proteins in the structure-bound fraction. In contrast, catalase (KatA), γ-glutamyltranspeptidase (Ggt), and the neutrophil-activating protein NapA were found almost exclusively in the soluble protein fraction. The results presented here are an important complement to genome sequence data, and the established 2-D PAGE maps provide a basis for comparative studies of the H. pylori proteome. Such subproteomes in the public domain will be effective instruments for identifying new virulence factors and antigens of potential diagnostic and/or curative value against infections with this important pathogen. © 2005 WILEY-VCH Verlag GmbH & Co. KGaA.
Created from Fastlane, Scopus look-up
Keywords: Mass spectrometry; Molecular pathogenesis; Pathogenicity island; Two-dimensional gel electrophoresis; Type IV secretion; Virulence

Subversion of host kinases: a key network in cellular signaling hijacked by Helicobacter pylori CagA - Tegtmeyer, Nicole; Neddermann, Matthias; Asche, Carmen Isabell; Backert, Steffen (Molecular Microbiology, 2017)
Helicobacter pylori is a paradigm of persistent pathogens and major risk factor for developing severe diseases including adenocarcinoma in the human stomach. An important bacterial factor linked to gastric disease progression is the cag pathogenicity island-encoded type-IV secretion system (T4SS) effector protein CagA. Translocated CagA undergoes tyrosine phosphorylation at EPIYA-motifs and then activates or inactivates multiple host signaling proteins in a phosphorylation-dependent and phosphorylation-independent fashion. In this way, intracellular CagA acts as a ‘masterkey’ or ‘picklock’, which evolved during evolution to hijack key host cell signal transduction functions. Crucial targets of CagA represent a variety of serine/threonine and tyrosine kinases, which control major checkpoints of eukaryotic signaling. Here we review the signal transmission by translocated CagA on multiple receptor kinases (c-Met and EGFR) and non-receptor kinases (Src, Abl, Csk, aPKC, Par1, PI3K, Akt, FAK, GSK-3, JAK, PAK1, PAK2 and MAP kinases), manipulating a selection of fundamental processes in the human gastric epithelium such as cell adhesion, polarity, proliferation, motility, receptor endocytosis, cytoskeletal rearrangements, apoptosis, inflammation and cell cycle progression. This enormous complexity generates a highly remarkable and puzzling scenario during H. pylori infection. The contribution of these signaling pathways to bacterial survival, persistence and gastric pathogenesis is discussed.
Created from Fastlane, Scopus look-up

Systematic analysis of phosphotyrosine antibodies recognizing single phosphorylated EPIYA-motifs in CagA of East Asian-type Helicobacter pylori strains - Lind, Judith; Backert, Steffen; Hoffmann, Rebecca; Eichler, Jutta; Yamaoka, Yoshio; Perez-Perez, Guillermo I.; Torres, Javier; Sticht, Heinrich; Tegtmeyer, Nicole (BMC Microbiology, 2016)
Highly virulent strains of the gastric pathogen Helicobacter pylori encode a type IV secretion system (T4SS) that delivers the effector protein CagA into gastric epithelial cells. Translocated CagA undergoes tyrosine phosphorylation by members of the oncogenic c-Src and c-Abl host kinases at EPIYA-sequence motifs A, B and D in East Asian-type strains. These phosphorylated EPIYA-motifs serve as recognition sites for various SH2-domains containing human proteins, mediating interactions of CagA with host signaling factors to manipulate signal transduction pathways. Recognition of phospho-CagA is mainly based on the use of commercial pan-phosphotyrosine antibodies that were originally designed to detect phosphotyrosines in mammalian proteins. Specific anti-phospho-EPIYA antibodies for each of the three sites in CagA are not forthcoming.This study was designed to systematically analyze the detection preferences of each phosphorylated East Asian CagA EPIYA-motif by pan-phosphotyrosine antibodies and to determine a minimal recognition sequence. We synthesized phospho- and non-phosphopeptides derived from each predominant EPIYA-site, and determined the recognition patterns by seven different pan-phosphotyrosine antibodies using Western blotting, and also investigated representative East Asian H. pylori isolates during infection. The results indicate that a total of only 9-11 amino acids containing the phosphorylated East Asian EPIYA-types are required and sufficient to detect the phosphopeptides with high specificity. However, the sequence recognition by the different antibodies was found to bear high variability. From the seven antibodies used, only four recognized all three phosphorylated EPIYA-motifs A, B and D similarly well. Two of the phosphotyrosine antibodies preferentially bound primarily to the phosphorylated motif A and D, while the seventh antibody failed to react with any of the phosphorylated EPIYA-motifs. Control experiments confirmed that none of the antibodies reacted with non-phospho-CagA peptides and in accordance were able to recognize phosphotyrosine proteins in human cells.The results of this study disclose the various binding preferences of commercial anti-phosphotyrosine antibodies for phospho-EPIYA-motifs, and are valuable in the application for further characterization of CagA phosphorylation events during infection with H. pylori and risk prediction for gastric disease development.
EVALuna2:26300
Keywords: c-Abl; c-Src; CagA; cagPAI; Dotblot; EPIYA motifs; Gastric cancer; Helicobacter pylori; Signaling; Type IV secretion; T4SS; Tyrosine kinases

Systematic analysis of phosphotyrosine antibodies recognizing single phosphorylated EPIYA-motifs in CagA of Western-type Helicobacter pylori strains - Lind, Judith; Backert, Steffen; Pfleiderer, Klaus; Berg, Douglas E.; Yamaoka, Yoshio; Sticht, Heinrich; Tegtmeyer, Nicole (PLoS ONE, 2014)
The clinical outcome of Helicobacter pylori infections is determined by multiple host-pathogen interactions that may develop to chronic gastritis, and sometimes peptic ulcers or gastric cancer. Highly virulent strains encode a type IV secretion system (T4SS) that delivers the effector protein CagA into gastric epithelial cells. Translocated CagA undergoes tyrosine phosphorylation at EPIYA-sequence motifs, called A, B and C in Western-type strains, by members of the oncogenic Src and Abl host kinases. Phosphorylated EPIYA-motifs mediate interactions of CagA with host signaling factors–in particular various SH2-domain containing human proteins–thereby hijacking multiple downstream signaling cascades. Observations of tyrosine-phosphorylated CagA are mainly based on the use of commercial phosphotyrosine antibodies, which originally were selected to detect phosphotyrosines in mammalian proteins. Systematic studies of phosphorylated EPIYA-motif detection by the different antibodies would be very useful, but are not yet available. To address this issue, we synthesized phospho- and non-phosphopeptides representing each predominant Western CagA EPIYA-motif, and determined the recognition patterns of seven different phosphotyrosine antibodies in Western blots, and also performed infection studies with diverse representative Western H. pylori strains. Our results show that a total of 9-11 amino acids containing the phosphorylated EPIYA-motifs are necessary and sufficient for specific detection by these antibodies, but revealed great variability in sequence recognition. Three of the antibodies recognized phosphorylated EPIYA-motifs A, B and C similarly well; whereas preferential binding to phosphorylated motif A and motifs A and C was found with two and one antibodies, respectively, and the seventh anti-phosphotyrosine antibody did not recognize any phosphorylated EPIYA-motif. Controls showed that none of the antibodies recognized the corresponding non-phospho CagA peptides, and that all of them recognized phosphotyrosines in mammalian proteins. These data are valuable in judicious application of commercial anti-phosphotyrosine antibodies and in characterization of CagA phosphorylation during infection and disease development.
EVALuna2:26284

T4SS-dependent TLR5 activation by Helicobacter pylori infection - Suneesh Kumar, Pachathundikandi; Tegtmeyer, Nicole; Arnold, Isabelle Catherine; Lind, Judith; Neddermann, Matthias; Falkeis-Veits, Christina; Chattopadhyay, Sujay; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Sticht, Heinrich; Müller, Anne; et al. (Nature Communications, 2019)
Toll-like receptor TLR5 recognizes a conserved domain, termed D1, that is present in flagellins of several pathogenic bacteria but not in Helicobacter pylori. Highly virulent H. pylori strains possess a type IV secretion system (T4SS) for delivery of virulence factors into gastric epithelial cells. Here, we show that one of the H. pylori T4SS components, protein CagL, can act as a flagellin-independent TLR5 activator. CagL contains a D1-like motif that mediates adherence to TLR5+ epithelial cells, TLR5 activation, and downstream signaling in vitro. TLR5 expression is associated with H. pylori infection and gastric lesions in human biopsies. Using Tlr5-knockout and wild-type mice, we show that TLR5 is important for efficient control of H. pylori infection. Our results indicate that CagL, by activating TLR5, may modulate immune responses to H. pylori.
CRIS-Team Scopus Importer:2019-12-27

The 25th Jena Symposium: Campylobacter infections 25. Jenaer Symposium: Campylobacter-Infektionen - Hänel, Ingrid; Alter, T.; Backert, Steffen (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2008)
Created from Fastlane, Scopus look-up

The Cag pathogenicity island and interaction between TLR2/NOD2 and NLRP3 regulate IL-1β production in Helicobacter pylori infected dendritic cells - Kim, Dong-Jae; Park, Jong-Hwan; Franchi, Luigi; Backert, Steffen; Nunez, Gabriel (European Journal of Immunology, 2013)
Helicobacter pylori colonization of the stomach affects about half of the world population and is associated with the development of gastritis, ulcers, and cancer. Polymorphisms in the IL1B gene are linked to an increased risk of H. pylori associated cancer, but the bacterial and host factors that regulate interleukin (IL)-1β production in response to H. pylori infection remain unknown. Using murine BM-derived DCs, we show that the bacterial virulence factors cytotoxin-associated genes pathogenicity island and CagL, but not vacuolating cytotoxin A or CagA, regulate the induction of pro-IL-1β and the production of mature IL-1β in response to H. pylori infection. We further show that the host receptors, Toll-like receptor 2 (TLR2) and nucleotide-binding oligomerization domain 2 (NOD2), but not NOD1, are required for induction of pro-IL-1β and NOD-like receptor pyrin domain containing 3 (NLRP3) in H. pylori infected DCs. In contrast, NLRP3 and the adaptor ASC were essential for the activation of caspase-1, processing of pro-IL-1β into IL-1β, and IL-1β secretion. Finally, we show that mice deficient in caspase-1, IL-1β, and IL-1 receptor, but not NLRP3, are impaired in the clearance of CagA-positive H. pylori from the stomach when compared with WT mice. These studies identify bacterial cag pathogenicity island and the cooperative interaction among host innate receptors TLR2, NOD2, and NLRP3 as important regulators of IL-1β production in H. pylori infected DCs. © 2013 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Created from Fastlane, Scopus look-up
Keywords: Helicobacter pylori; IL-1β; Inflammasome; NLRP3; NOD2

The cytotoxic necrotizing factors from Yersinia pseudotuberculosis and from Escherichia coli bind to different cellular receptors but take the same route to the cytosol - Blumenthal, Britta; Hoffmann, Claudia; Aktories, Klaus; Backert, Steffen; Schmidt, Gudula (Infection and Immunity, 2007)
The cytotoxic necrotizing factors CNF1 and CNF2 produced by pathogenic Escherichia coli strains and CNFY of Yersinia pseudotuberculosis constitutively activate small GTPases of the Rho family. They deamidate a glutamine (Gln63 in RhoA), which is crucial for GTP hydrolysis. CNF1 and CNFY exhibit 61% identity on the amino acid level, with equal distribution over the whole molecule. Although the two toxins are homologous in the receptor binding domain, we show that they bind to different cellular receptors. CNFY does not enter Caco-2 and CHO-K1 cells, which are responsive to CNF1. In contrast, HeLa, Hep-2, and HEK 293 cells do respond to both toxins. Competition studies with catalytically inactive mutants of the toxins revealed that binding of CNF1 has no influence on the uptake of CNF Y into HeLa cells. In contrast, uptake of CNF1 is retarded after preincubation of HeLa cells with the catalytically inactive mutant of CNF Y, suggesting that the toxin receptors overlap. Moreover, we compared the pathways of the toxins from receptor binding into the cytosol and showed that both toxins are taken up independent of the presence of clathrin or lipid rafts and are released into the cytosol from acidified endosomes. Copyright © 2007, American Society for Microbiology. All Rights Reserved.
Created from Fastlane, Scopus look-up

The functional interplay of Helicobacter pylori factors with gastric epithelial cells induces a multi-step process in pathogenesis - Posselt, Gernot; Backert, Steffen; Wessler, Silja (Cell Communication and Signaling, 2013)
Infections with the human pathogen Helicobacter pylori (H. pylori) can lead to severe gastric diseases ranging from chronic gastritis and ulceration to neoplastic changes in the stomach. Development and progress of H. pylori-associated disorders are determined by multifarious bacterial factors. Many of them interact directly with host cells or require specific receptors, while others enter the host cytoplasm to derail cellular functions. Several adhesins (e.g. BabA, SabA, AlpA/B, or OipA) establish close contact with the gastric epithelium as an important first step in persistent colonization. Soluble H. pylori factors (e.g. urease, VacA, or HtrA) have been suggested to alter cell survival and intercellular adhesions. Via a type IV secretion system (T4SS), H. pylori also translocates the effector cytotoxin-associated gene A (CagA) and peptidoglycan directly into the host cytoplasm, where cancer- and inflammation-associated signal transduction pathways can be deregulated. Through these manifold possibilities of interaction with host cells, H. pylori interferes with the complex signal transduction networks in its host and mediates a multi-step pathogenesis. © 2013 Posselt et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up

The Helicobacter pylori CagA protein disrupts matrix adhesion of gastric epithelial cells by dephosphorylation of vinculin - Moese, Stefan; Selbach, Matthias; Brinkmann, Volker; Karlas, Alexander; Haimovich, Beatrice; Backert, Steffen; Meyer, Thomas F. (Cellular Microbiology, 2007)
Helicobacter pylori colonizes the human stomach, contributing to or causing several diseases. Translocation of the CagA bacterial protein into gastric epithelial cells has been linked to an increased risk of peptic ulcer disease and gastric carcinoma. Upon translocation, CagA is tyrosine phosphorylated by Src family kinases (SFKs), which themselves become inactivated via a negative feedback loop. Here, we show that tyrosine-phosphorylated CagA disrupts adhesion of AGS cells to the extracellular matrix. Owing to the inactivation of c-Src via CagA interaction, vinculin is dephosphorylated at tyrosine residues, 100 and 1065, by corresponding phosphatases. Vinculin dephosphorylation disturbs the interaction and recruitment of the actin-related protein 2/3 (Arp2/3) complex by p34Arc, resulting in a reduction of focal adhesion complexes. These defects can be mimicked by downregulating vinculin using RNA interference in non-infected cells. Tyrosine dephosphorylation of vinculin results in severe cellular deficiencies in cell-matrix adhesion, cell spreading and wound repair. We hypothesize that CagA-mediated inactivation of vinculin is a key step in the mechanism by which H. pylori induces damage to the gastric epithelium and represents an important step in disease development. © 2007 The Authors; Journal compilation © 2007 Blackwell Publishing Ltd.
Created from Fastlane, Scopus look-up

The Helicobacter pylori CagA protein induces cortactin dephosphorylation and actin rearrangement by c-Src inactivation - Selbach, Matthias; Moese, Stefan; Hurwitz, Robert; Hauck, Cristof R; Meyer, Thomas F.; Backert, Steffen (EMBO Journal, 2003)
The gastric pathogen Helicobacter pylori translocates the CagA protein into epithelial cells by a type IV secretion process. Translocated CagA is tyrosine phosphorylated (CagA(P-Tyr)) on specific EPIYA sequence repeats by Src family tyrosine kinases. Phosphorylation of CagA induces the dephosphorylation of as yet unidentified cellular proteins, rearrangements of the host cell actin cytoskeleton and cell scattering. We show here that CagA(P-Tyr) inhibits the catalytic activity of c-Src in vivo and in vitro. c-Src inactivation leads to tyrosine dephosphorylation of the actin binding protein cortactin. Concomitantly, cortactin is specifically redistributed to actin-rich cellular protrusions. c-Src inactivation and cortactin dephosphorylation are required for rearrangements of the actin cytoskeleton. Moreover, CagA(P-Tyr)-mediated c-Src inhibition downregulates further CagA phosphorylation through a negative feedback loop. This is the first report of a bacterial virulence factor that inhibits signalling of a eukaryotic tyrosine kinase and on a role of c-Src inactivation in host cell cytoskeletal rearrangements.
Created from Fastlane, WoS look-up

The Helicobacter pylori CagA protein induces tyrosine dephosphorylation of ezrin - Selbach, Matthias; Moese, Stefan; Backert, Steffen; Jungblut, Peter R.; Meyer, Thomas F. (Proteomics, 2004)
Helicobacter pylori is one of the most wide-spread bacterial pathogens and infects the human stomach to cause diseases, such as gastritis, gastric ulceration, and gastric cancer. A major virulence determinant is the H. pylori CagA protein (encoded by the cytotoxin-associated gene A) which is translocated from the bacteria into the cytoplasm of host cells by a type IV secretion system. In the host cell, CagA is phosphorylated on tyrosine residues and induces rearrangements of the actin cytoskeleton. We have previously shown that tyrosine-phosphorylated CagA inhibits the catalytic activity of Src family kinases and induces tyrosine dephosphorylation of several host cell proteins. Here, we identified one of these proteins as ezrin by a combination of preparative gel electrophoresis, two-dimensional electrophoresis (2-DE) and matrix-assisted laser desorption/ionization-mass spectrometry (MALDI-MS). Specific pharmacological inhibition of Src family kinases also induces ezrin dephosphorylation. Therefore, ezrin dephosphorylation appears to be induced by CagA-mediated Src inactivation. Ezrin is the founding member of the ezrin-radixin-moesin (ERM) family of proteins which are signalling integrators at the cell cortex. Since ezrin is a component of microvilli and a linker protein between actin filaments and membrane proteins, this observation has important implications for H. pylori pathogenesis and might also help to explain the development of gastric cancer.
Created from Fastlane, Scopus look-up
Keywords: Actin cytoskeleton; Ezrin-radixin-moesin family; Molecular pathogenesis; Src; Type IV secretion

The Helicobacter pylori Genome Project: insights into H. pylori population structure from analysis of a worldwide collection of complete genomes - Thorell, Kaisa; Muñoz-Ramírez, Zilia Y.; Wang, Difei; Sandoval-Motta, Santiago; Boscolo Agostini, Rajiv; Ghirotto, Silvia; Torres, Roberto C.; Romero-Gallo, Judith; Krishna, Uma; Peek, Richard M.; Piazuelo, M. Blanca; Raaf, Naïma; et al. (Nature Communications, 2023)
Helicobacter pylori, a dominant member of the gastric microbiota, shares co-evolutionary history with humans. This has led to the development of genetically distinct H. pylori subpopulations associated with the geographic origin of the host and with differential gastric disease risk. Here, we provide insights into H. pylori population structure as a part of the Helicobacter pylori Genome Project (HpGP), a multi-disciplinary initiative aimed at elucidating H. pylori pathogenesis and identifying new therapeutic targets. We collected 1011 well-characterized clinical strains from 50 countries and generated high-quality genome sequences. We analysed core genome diversity and population structure of the HpGP dataset and 255 worldwide reference genomes to outline the ancestral contribution to Eurasian, African, and American populations. We found evidence of substantial contribution of population hpNorthAsia and subpopulation hspUral in Northern European H. pylori. The genomes of H. pylori isolated from northern and southern Indigenous Americans differed in that bacteria isolated in northern Indigenous communities were more similar to North Asian H. pylori while the southern had higher relatedness to hpEastAsia. Notably, we also found a highly clonal yet geographically dispersed North American subpopulation, which is negative for the cag pathogenicity island, and present in 7% of sequenced US genomes. We expect the HpGP dataset and the corresponding strains to become a major asset for H. pylori genomics.
CRIS-Team Scopus Importer:2023-12-22

The helicobacter pylori type IV secretion system encoded by the cag pathogenicity Island: Architecture, function, and signaling - Backert, Steffen; Haas, Rainer; Gerhard, Markus; Naumann, Michael (Type IV Secretion in Gram-Negative and Gram-Positive Bacteria, 2017)
Various gram-negative pathogens express type IV secretion systems (T4SSs) which translocate bacterial virulence factors into host target cells to hijack cellular processes for their own benefit and causing disease. The pathology of Helicobacter pylori, the causative agent of chronic gastritis, peptic ulcer disease, and gastric cancer in humans, strongly depends on a T4SS encoded by the cag pathogenicity island (cagPAI). This T4SS represents a pilus-like structure and a membrane-spanning complex. T4SS assembly is achieved by various protein–protein interactions and several pilus-associated components (CagL, CagI, CagY, and CagA) that allow docking to the host cell integrin member α 5 β 1 followed by delivery of its major effector protein, CagA, across the host cell membrane. In addition, recent studies have shown that H. pylori exploits human CEACAM receptors via the adhesin HopQ, encoded outside of the cagPAI, for bacterial adherence and translocation of CagA. Here, we review the composition and assembly of the H. pylori T4SS and its fundamental role in the infection process. We discuss major CagA-dependent and CagA-independent signaling events by the T4SS in vitro and in animal models in vivo, which include the induction of cytoskeletal rearrangements, membrane dynamics, disturbance of cell polarity as well as transcriptional responses involved in inflammation, cell proliferation, and anti-apoptosis. The contribution of these signaling cascades to H. pylori colonization, and pathogenesis is reviewed.
Created from Fastlane, Scopus look-up
Keywords: Adherens junction; CagA; CEACAM; Claudin-8; E-cadherin; HBP; Helicobacter pylori; HtrA; Integrin; NF-κB; Occludin; TLR; Type IV secretion

The Helicobacter pylori type IV secretion system upregulates epithelial cortactin expression by a CagA- and JNK-dependent pathway - Sharafutdinov, Irshad; Backert, Steffen; Tegtmeyer, Nicole (Cellular Microbiology, 2021)
Cortactin represents an important actin-binding factor, which controls actin-cytoskeletal remodelling in host cells. In this way, cortactin has been shown to exhibit crucial functions both for cell movement and tumour cell invasion. In addition, the cortactin gene cttn is amplified in various cancer types of humans. Helicobacter pylori is the causative agent of multiple gastric diseases and represents a significant risk factor for the development of gastric adenocarcinoma. It has been repeatedly shown that H. pylori manipulates cancer-related signal transduction events in infected gastric epithelial cells such as the phosphorylation status of cortactin. In fact, H. pylori modifies the activity of cortactin's binding partners to stimulate changes in the actin-cytoskeleton, cell adhesion and motility. Here we show that H. pylori infection of cultured AGS and Caco-2 cells for 24–48 hr leads to the overexpression of cortactin by 2–3 fold at the protein level. We demonstrate that this activity requires the integrity of the type IV secretion system (T4SS) encoded by the cag pathogenicity island (cagPAI) as well as the translocated effector protein CagA. We further show that ectopic expression of CagA is sufficient to stimulate cortactin overexpression. Furthermore, phosphorylation of CagA at the EPIYA-repeat region is not required, suggesting that this CagA activity proceeds in a phosphorylation-independent fashion. Inhibitor studies further demonstrate that the involved signalling pathway comprises the mitogen-activated protein kinase JNK (c-Jun N-terminal kinase), but not ERK1/2 or p38. Taken together, using H. pylori as a model system, this study discovered a previously unrecognised cortactin activation cascade by a microbial pathogen. We suggest that H. pylori targets cortactin to manipulate the cellular architecture and epithelial barrier functions that can impact gastric cancer development. Take Aways: Helicobacter pylori infection induces overexpression of cortactin at the protein level Cortactin upregulation requires the T4SS and effector protein CagA Ectopic expression of CagA is sufficient to stimulate cortactin overexpression Overexpression of cortactin proceeds CagA phosphorylation-independent The involved host cell signalling pathway comprises the MAP kinase JNK.
CRIS-Team Scopus Importer:2021-07-30
Keywords: cancer; cortactin; Helicobacter; JNK; pathogenesis; pathogenicity island; signalling; virulence

The Helicobacter pylori urease virulence factor is required for the induction of hypoxia-induced factor-1α in gastric cells - Valenzuela-Valderrama, Manuel; Cerda-Opazo, Paulina; Backert, Steffen; González, María Fernanda; Carrasco-Véliz, Nicolás; Jorquera-Cordero, Carla; Wehinger, Sergio; Canales, Jimena; Bravo, Denisse; Quest, Andrew F.G. (Cancers, 2019)
Chronic Helicobacter pylori infection increases the risk of gastric cancer and induction of hypoxia-induced factor (HIF), which is frequently associated with the development and progression of several types of cancer. We recently showed that H. pylori activation of the PI3K-AKT-mTOR pathway in gastric cells increased HIF-1α expression. Here, we identified the H. pylori virulence factor responsible for HIF-1α induction. A mutant of the H. pylori 84-183 strain was identified with reduced ability to induce HIF-1α. Coomassie blue staining of extracts from these bacteria separated by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) revealed poor expression of urease subunits that correlated with reduced urease activity. This finding was confirmed in the 26695 strain, where urease mutants were unable to induce HIF-1α expression. Of note, HIF-1α induction was also observed in the presence of the urease inhibitor acetohydroxamic acid at concentrations (of 20 mM) that abrogated urease activity in bacterial culture supernatants, suggesting that enzymatic activity of the urease is not required for HIF-1α induction. Finally, the pre-incubation of the human gastric adenocarcinoma cell line AGS with blocking antibodies against Toll-like receptor-2 (TLR2), but not TLR4, prevented HIF-1α induction. In summary, these results reveal a hitherto unexpected role for the urease protein in HIF-1α induction via TLR2 activation following H. pylori infection of gastric cells.
CRIS-Team Scopus Importer:2019-07-19
Keywords: Helicobacter pylori; HIF-1α; Toll-like receptor 2 (TLR2); Urease

The impact of serine protease HtrA in apoptosis, intestinal immune responses and extra-intestinal histopathology during Campylobacter jejuni infection of infant mice - Heimesaat, Markus M.; Fischer, Andre; Alutis, Marie; Grundmann, Ursula; Böhm, Manja; Tegtmeyer, Nicole; Goebel, Ulf B.; Kühl, Anja A.; Bereswill, Stefan; Backert, Steffen (Gut Pathogens, 2014)

The Influence of Gastric Microbiota and Probiotics in Helicobacter pylori Infection and Associated Diseases - Verma, Jagriti; Anwar, Md Tanveer; Linz, Bodo; Backert, Steffen; Pachathundikandi, Suneesh Kumar (Biomedicines, 2025)
The role of microbiota in human health and disease is becoming increasingly clear as a result of modern microbiome studies in recent decades. The gastrointestinal tract is the major habitat for microbiota in the human body. This microbiota comprises several trillion microorganisms, which is equivalent to almost ten times the total number of cells of the human host. Helicobacter pylori is a known pathogen that colonizes the gastric mucosa of almost half of the world population. H. pylori is associated with several gastric diseases, including gastric cancer (GC) development. However, the impact of the gastric microbiota in the colonization, chronic infection, and pathogenesis is still not fully understood. Several studies have documented qualitative and quantitative changes in the microbiota’s composition in the presence or absence of this pathogen. Among the diverse microflora in the stomach, the Firmicutes represent the most notable. Bacteria such as Prevotella sp., Clostridium sp., Lactobacillus sp., and Veillonella sp. were frequently found in the healthy human stomach. In contrast, H.pylori is very dominant during chronic gastritis, increasing the proportion of Proteobacteria in the total microbiota to almost 80%, with decreasing relative proportions of Firmicutes. Likewise, H. pylori and Streptococcus are the most abundant bacteria during peptic ulcer disease. While the development of H. pylori-associated intestinal metaplasia is accompanied by an increase in Bacteroides, the stomachs of GC patients are dominated by Firmicutes such as Lactobacillus and Veillonella, constituting up to 40% of the total microbiota, and by Bacteroidetes such as Prevotella, whereas the numbers of H. pylori are decreasing. This review focuses on some of the consequences of changes in the gastric microbiota and the function of probiotics to modulate H. pylori infection and dysbiosis in general.
CRIS-Team Scopus Importer:2025-01-31
Keywords: gastric cancer; gastric microbiota; H. pylori; MALT lymphoma; peptic ulcer disease; probiotics

The mystery of the rings: Structure and replication of mitochondrial genomes from higher plants - Backert, Steffen; Nielsen, Brent Lynn; Börner, Thomas (Trends in Plant Science, 1997)
Higher plant mitochondrial genomes are unique in their size, complexity and evolutionary dynamics. However, in spite of the existence of physical maps, the structural organization of the mitochondrial genome in vivo is not fully understood. The molecules observed are mainly linear or complex, and some of them are much larger than predicted from the genome size. In addition, circular DNA species are found in a continuous size distribution up to >100 kb - although this is heavily skewed towards small molecules. There is a high single-stranded DNA content, and both theta- and sigma-modes of replication have been reported. Recombination between large and small repeats as well as amplification by replication appear to contribute considerably to mitochondrial genome diversity.
Created from Fastlane, Scopus look-up

Therapeutic and protective approaches to combat Campylobacter jejuni infections - Sharafutdinov, Irshad; Linz, Bodo; Tegtmeyer, Nicole; Backert, Steffen (Frontiers in Pharmacology, 2025)
Campylobacter jejuni is a typical zoonotic bacterium, colonizing the gut of many bird species as commensal. In humans, C. jejuni is a major foodborne pathogen. Infection of humans causes campylobacteriosis in the small intestine, constituting a main source of bacteria-dependent gastroenteritis cases worldwide. In particular, the ingestion of under-cooked rooster meat, raw milk and contaminated water, as well as cross-contamination of ready-to-eat food after handling raw chicken meat, are responsible for the majority of C. jejuni infections. As a consequence, infected individuals may acquire watery and/or bloody diarrhea associated with abdominal pain, and eventually post-infection illnesses of the neural system and joints, including the Guillain-Barré, Miller Fisher and Reiter syndromes. One therapeutic strategy is to reduce C. jejuni colonization in chicken farms using vaccination, bacteriocins and phage therapy protocols. Prevention approaches during poultry meat processing comprise the compliance to high hygiene standards. Furthermore, substantial progress has been also made in recent years to combat campylobacteriosis using established mouse and in vitro cell model systems. In this regard, specific C. jejuni colonization- and pathogenicity-associated components were considered as favored treatment structures, targeting bacterial movement, host cell interaction, intracellular survival, propagation and spread of the bacteria. This has been complemented by a number of pharmaceutical compounds to reduce C. jejuni-induced epithelial cell damage, inflammation and apoptosis in infected mice. Here we review these novel treatment and prevention as well as “One World - One Health” approaches that aim to diminish the consequences of acute campylobacteriosis and post-infection sequelae in humans.
CRIS-Team Scopus Importer:2025-05-30
Keywords: bacteriophage; Campylobacter jejuni; epithelial barrier; gut microbiota; One Health; phytochemicals; probiotics; vaccine

The role of CagA in the gastric biology of helicobacter pylori - Backert, Steffen; Blaser, Martin J. (Cancer Research, 2016)
Created from Fastlane, Scopus look-up

The role of serine protease HtrA in acute ulcerative enterocolitis and extra-intestinal immune responses during Campylobacter jejuni infection of gnotobiotic IL-10 deficient mice - Heimesaat, Markus M.; Alutis, Marie; Grundmann, Ursula; Fischer, Andre; Tegtmeyer, Nicole; Böhm, Manja; Kuehl, Anja A.; Goebel, Ulf B.; Backert, Steffen; Bereswill, Stefan (Frontiers in Cellular and Infection Microbiology, 2014)
Campylobacter jejuni infections have a high prevalence worldwide and represent a significant socioeconomic burden. C. jejuni can cross the intestinal epithelial barrier as visualized in biopsies derived from human patients and animal models, however, the underlying molecular mechanisms and associated immunopathology are still not well understood. We have recently shown that the secreted serine protease HtrA (high temperature requirement A) plays a key role in C. jejuni cellular invasion and transmigration across polarized epithelial cells in vitro. In the present in vivo study we investigated the role of HtrA during C. jejuni infection of mice. We used the gnotobiotic IL-10-/- mouse model to study campylobacteriosis following peroral infection with the C. jejuni wild-type (WT) strain NCTC11168 and the isogenic, non-polar NCTC11168ΔhtrA deletion mutant. Six days post infection (p.i.) with either strain mice harbored comparable intestinal C. jejuni loads, whereas ulcerative enterocolitis was less pronounced in mice infected with the ΔhtrA mutant strain. Moreover, ΔhtrA mutant infected mice displayed lower apoptotic cell numbers in the large intestinal mucosa, less colonic accumulation of neutrophils, macrophages and monocytes, lower large intestinal nitric oxide, IFN-γ, and IL-6 as well as lower TNF-α and IL-6 serum concentrations as compared to WT strain infected mice at day 6 p.i. Notably, immunopathological responses were not restricted to the intestinal tract given that liver and kidneys exhibited mild histopathological changes 6 days p.i. with either C. jejuni strain. We also found that hepatic and renal nitric oxide levels or renal TNF-α concentrations were lower in the ΔhtrA mutant as compared to WT strain infected mice. In conclusion, we show here that the C. jejuni HtrA protein plays a pivotal role in inducing host cell apoptosis and immunopathology during murine campylobacteriosis in the gut in vivo.
Created from Fastlane, Scopus look-up
Keywords: Bacterial translocation; Colonization resistance; Extra-intestinal immune responses; Host-pathogen-interaction; Innate immunity; Intestinal immunopathology; Systemic immune responses; Ulcerative enterocolitis

The signaling pathway of Campylobacter jejuni-induced Cdc42 activation: Role of fibronectin, integrin beta1, tyrosine kinases and guanine exchange factor Vav2 - Krause-Gruszczynska, Malgorzata; Boehm, Manja; Rohde, Manfred; Tegtmeyer, Nicole; Takahashi, Seiichiro; Buday, Laszlo; Oyarzabal, Omar A.; Backert, Steffen (Cell Communication and Signaling, 2011)
Background: Host cell invasion by the foodborne pathogen Campylobacter jejuni is considered as one of the primary reasons of gut tissue damage, however, mechanisms and key factors involved in this process are widely unclear. It was reported that small Rho GTPases, including Cdc42, are activated and play a role during invasion, but the involved signaling cascades remained unknown. Here we utilised knockout cell lines derived from fibronectin-/-, integrin-beta1-/-, focal adhesion kinase (FAK)-/-and Src/Yes/Fyn-/-deficient mice, and wild-type control cells, to investigate C. jejuni-induced mechanisms leading to Cdc42 activation and bacterial uptake. Results: Using high-resolution scanning electron microscopy, GTPase pulldowns, G-Lisa and gentamicin protection assays we found that each studied host factor is necessary for induction of Cdc42-GTP and efficient invasion. Interestingly, filopodia formation and associated membrane dynamics linked to invasion were only seen during infection of wild-type but not in knockout cells. Infection of cells stably expressing integrin-beta1 variants with well-known defects in fibronectin fibril formation or FAK signaling also exhibited severe deficiencies in Cdc42 activation and bacterial invasion. We further demonstrated that infection of wild-type cells induces increasing amounts of phosphorylated FAK and growth factor receptors (EGFR and PDGFR) during the course of infection, correlating with accumulating Cdc42-GTP levels and C. jejuni invasion over time. In studies using pharmacological inhibitors, silencing RNA (siRNA) and dominant-negative expression constructs, EGFR, PDGFR and PI3-kinase appeared to represent other crucial components upstream of Cdc42 and invasion. siRNA and the use of Vav1/2-/-knockout cells further showed that the guanine exchange factor Vav2 is required for Cdc42 activation and maximal bacterial invasion. Overexpression of certain mutant constructs indicated that Vav2 is a linker molecule between Cdc42 and activated EGFR/PDGFR/PI3-kinase. Using C. jejuni mutant strains we further demonstrated that the fibronectin-binding protein CadF and intact flagella are involved in Cdc42-GTP induction, indicating that the bacteria may directly target the fibronectin/integrin complex for inducing signaling leading to its host cell entry. Conclusion: Collectively, our findings led us propose that C. jejuni infection triggers a novel fibronectin→integrin-beta1→FAK/ Src→EGFR/PDGFR→PI3-kinase→Vav2 signaling cascade, which plays a crucial role for Cdc42 GTPase activity associated with filopodia formation and enhances bacterial invasion. © 2011 Krause-Gruszczynska et al; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Cdc42; cellular invasion; EGF receptor; molecular pathogenesis; PDGF receptor; PI3-kinase; Rho family GTPases; signaling; Vav2; virulence

The versatility of Helicobacter pylori CagA effector protein functions: The master key hypothesis. - Backert, Steffen; Tegtmeyer, Nicole; Selbach, Matthias (Helicobacter, 2010)
Several bacterial pathogens inject virulence proteins into host target cells that are substrates of eukaryotic tyrosine kinases. One of the key examples is the Helicobacter pylori CagA effector protein which is translocated by a type-IV secretion system. Injected CagA becomes tyrosine-phosphorylated on EPIYA sequence motifs by Src and Abl family kinases. CagA then binds to and activates/inactivates multiple signaling proteins in a phosphorylation-dependent and phosphorylation-independent manner. A recent proteomic screen systematically identified eukaryotic binding partners of the EPIYA phosphorylation sites of CagA and similar sites in other bacterial effectors by high-resolution mass spectrometry. Individual phosphorylation sites recruited a surprisingly high number of interaction partners suggesting that each phosphorylation site can interfere with many downstream pathways. We now count 20 reported cellular binding partners of CagA, which represents the highest quantitiy among all yet known virulence-associated effector proteins in the microbial world. This complexity generates a highly remarkable and puzzling scenario. In addition, the first crystal structure of CagA provided us with new information on the function of this important virulence determinant. Here we review the recent advances in characterizing the multiple binding signaling activities of CagA. Injected CagA can act as a 'master key' that evolved the ability to highjack multiple host cell signalling cascades, which include the induction of membrane dynamics, actin-cytoskeletal rearrangements and the disruption of cell-to-cell junctions as well as proliferative, pro-inflammatory and anti-apoptotic nuclear responses. The discovery that different pathogens use this common strategy to subvert host cell functions suggests that more examples will emerge soon.

The versatility of Helicobacter pylori CagA effector protein functions: The master key hypothesis (Helicobacter 15 (163-176)) - Backert, Steffen; Tegtmeyer, Nicole; Selbach, Matthias (Helicobacter, 2010)
CRIS-Team Scopus Importer:2020-09-18

The versatility of the Helicobacter pylori vacuolating cytotoxin VacA in signal transduction and molecular crosstalk - Backert, Steffen; Tegtmeyer, Nicole (Toxins, 2010)
By modulating important properties of eukaryotic cells, many bacterial protein toxins highjack host signalling pathways to create a suitable niche for the pathogen to colonize and persist. Helicobacter pylori VacA is paradigm of pore-forming toxins which contributes to the pathogenesis of peptic ulceration. Several cellular receptors have been described for VacA, which exert different effects on epithelial and immune cells. The crystal structure of VacA p55 subunit might be important for elucidating details of receptor interaction and pore formation. Here we discuss the multiple signalling activities of this important toxin and the molecular crosstalk between VacA and other virulence factors. © 2010 by the authors; licensee Molecular Diversity Preservation International, Basel, Switzerland.
Created from Fastlane, Scopus look-up
Keywords: CagA; Helicobacter pylori; Lipid rafts; Pathogenicity island; Signalling; Type IV secretion; VacA; Vacuolating cytotoxin

TIFA has dual functions in Helicobacter pylori-induced classical and alternative NF-kappa B pathways - Maubach, Gunter; Lim, Michelle C. C.; Sokolova, Olga; Backert, Steffen; Meyer, Thomas F.; Naumann, Michael (EMBO Reports, 2021)
Helicobacter pylori infection constitutes one of the major risk factors for the development of gastric diseases including gastric cancer. The activation of nuclear factor-kappa-light-chain-enhancer of activated B cells (NF-kappa B) via classical and alternative pathways is a hallmark of H. pylori infection leading to inflammation in gastric epithelial cells. Tumor necrosis factor receptor-associated factor (TRAF)-interacting protein with forkhead-associated domain (TIFA) was previously suggested to trigger classical NF-kappa B activation, but its role in alternative NF-kappa B activation remains unexplored. Here, we identify TRAF6 and TRAF2 as binding partners of TIFA, contributing to the formation of TIFAsomes upon H. pylori infection. Importantly, the TIFA/TRAF6 interaction enables binding of TGF beta-activated kinase 1 (TAK1), leading to the activation of classical NF-kappa B signaling, while the TIFA/TRAF2 interaction causes the transient displacement of cellular inhibitor of apoptosis 1 (cIAP1) from TRAF2, and proteasomal degradation of cIAP1, to facilitate the activation of the alternative NF-kappa B pathway. Our findings therefore establish a dual function of TIFA in the activation of classical and alternative NF-kappa B signaling in H. pylori-infected gastric epithelial cells.
CRIS-Team WoS Importer:2021-08-06

Toll-like Receptor 5 Activation by the CagY Repeat Domains of Helicobacter pylori - Tegtmeyer, Nicole; Neddermann, Matthias; Lind, Judith; Suneesh Kumar, Pachathundikandi; Sharafutdinov, Irshad; Gutiérrez-Escobar, Andrés Julián; Brönstrup, Mark; Tegge, Werner; Hong, Minsun; Rohde, Manfred; Delahay, Robin M.; Sticht, Heinrich; et al. (Cell Reports, 2020)
Helicobacter pylori (Hp) is an important human pathogen associated with gastric inflammation and neoplasia. It is commonly believed that this bacterium avoids major immune recognition by Toll-like receptors (TLRs) because of low intrinsic activity of its flagellin and lipopolysaccharides (LPS). In particular, TLR5 specifically detects flagellins in various bacterial pathogens, while Hp evolved mutations in flagellin to evade detection through TLR5. Cancerogenic Hp strains encode a type IV secretion system (T4SS). The T4SS core component and pilus-associated protein CagY, a large VirB10 ortholog, drives effector molecule translocation. Here, we identify CagY as a flagellin-independent TLR5 agonist. We detect five TLR5 interaction sites, promoting binding of CagY-positive Hp to TLR5-expressing cells, TLR5 stimulation, and intracellular signal transduction. Consequently, CagY constitutes a remarkable VirB10 member detected by TLR5, driving crucial innate immune responses by this human pathogen.
CRIS-Team Scopus Importer:2020-09-25
Keywords: CagY; flagellin; Helicobacter; innate and adaptive immunity; PAMP; PRR; signal transduction; T4SS; TLR5; type IV secretion

Translocation of the Helicobacter pylori CagA protein in gastric epithelial cells by a type IV secretion apparatus - Backert, Steffen; Ziska, Elke; Brinkmann, Volker; Zimny-Arndt, Ursula; Fauconnier, Alan; Jungblut, Peter R.; Naumann, Michael; Meyer, Thomas F. (Cellular Microbiology, 2000)
Helicobacter pylori is one of the most common bacterial pathogens, infecting about 50% of the world population. The presence of a pathogenicity island (PAl) in H. pylori has been associated with gastric disease. We present evidence that the H. pylori protein encoded by the cytotoxin- associated gene A (cagA) is translocated and phosphorylated in infected epithelial cells. Two-dimensional gel electrophoresis (2-DE) of proteins isolated from infected AGS cells revealed H. pylori strain-specific and time- dependent tyrosine phosphorylation and dephosphorylation of several 125-135 kDa and 75-80 kDa proteins. Immunoblotting studies, matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS), cell fractionation and confocal microscopy demonstrated that one of the 125-135 kDa proteins represents the H. pylori CagA protein, which is translocated into the host cell membrane and the cytoplasm. Translocation of CagA was dependent on functional cagA gene and virulence (vir) genes of a type IV secretion apparatus composed of virB4, virB7, virB10, virB11 and virD4 encoded in the cag PAl of H. pylori. Our findings support the view that H. pylori actively translocates virulence determinants, including CagA, which could be involved in the development of a variety of gastric disease.
Created from Fastlane, Scopus look-up

Transmigration route of Campylobacter jejuni across polarized intestinal epithelial cells: Paracellular, transcellular or both? - Backert, Steffen; Böhm, Manja; Wessler, Silja; Tegtmeyer, Nicole (Cell Communication and Signaling, 2013)
Intact intercellular junctions and cellular matrix contacts are crucial structural components for the formation and maintenance of epithelial barrier functions in humans to control the commensal flora and protect against intruding microbes. Campylobacter jejuni is one of the most important zoonotic pathogens causing food-borne gastroenteritis and potentially more severe diseases such as reactive arthritis or Guillain-Barré syndrome. Crossing the intestinal epithelial barrier and host cell invasion by C. jejuni are considered to represent the primary reasons of gut tissue damage in humans and various animal model systems including monkeys, piglets, rabbits, hamsters and ferrets. C. jejuni is also able to invade underlying tissues such as the lamina propria, can enter the bloodstream, and possibly reach distinct organs such as spleen, liver or mesenteric lymph nodes. However, the molecular mechanisms as well as major bacterial and host cell factors involved in these activities are poorly understood. Various models exist by which the pathogen can trigger its own transmigration across polarized intestinal epithelial cells in vitro, the paracellular and/or transcellular mechanism. Recent studies suggest that bacterial factors such as flagellum, serine protease HtrA and lipooligosaccharide LOS may play an active role in bacterial transmigration. Here we review our knowledge on transmigration of C. jejuni as well as some other Campylobacter species, and discuss the pros and cons for the route(s) taken to travel across polarized epithelial cell monolayers. These studies provide fresh insights into the infection strategies employed by this important pathogen. © 2013 Backert et al.; licensee BioMed Central Ltd.
Created from Fastlane, Scopus look-up
Keywords: Adherens junctions; Cell polarity; Cellular invasion; E-cadherin; Fibronectin; HtrA; Integrins; Invasion; Molecular pathogenesis; Signaling; TER; Tight junctions; Transmigration; Virulence

Transport von Proteinen und DNA: Typ IV-Sekretion bei Gram-negativen Bakterien - Backert, Steffen; Fischer, Wolfgang (Naturwissenschaftliche Rundschau, 2007)

Trimer stability of Helicobacter pylori HtrA is regulated by a natural mutation in the protease domain - Zarzecka, Urszula; Tegtmeyer, Nicole; Sticht, Heinrich; Backert, Steffen (Medical Microbiology and Immunology, 2023)
The human pathogen Helicobacter pylori is a major risk factor for gastric disease development. Serine protease HtrA is an important bacterial virulence factor that cleaves the cell junction proteins occludin, claudin-8 and E-cadherin, which causes gastric tissue damage. Using casein zymography, we discovered that HtrA trimer stability varies in clinical H. pylori strains. Subsequent sequence analyses revealed that HtrA trimer stability correlated with the presence of leucine or serine residue at position 171. The importance of these amino acids in determining trimer stability was confirmed by leucine-to-serine swapping experiments using isogenic H. pylori mutant strains as well as recombinant HtrA proteins. In addition, this sequence position displays a high sequence variability among various bacterial species, but generally exhibits a preference for hydrophilic amino acids. This natural L/S171 polymorphism in H. pylori may affect the protease activity of HtrA during infection, which could be of clinical importance and may determine gastric disease development.
CRIS-Team Scopus Importer:2023-05-26
Keywords: Helicobacter pylori; HtrA; Proteases; Trimer stability

Two remarkable serine/leucine polymorphisms in Helicobacter pylori: functional importance for serine protease HtrA and adhesin BabA - Backert, Steffen; Tegtmeyer, Nicole; Horn, Anselm; Sticht, Heinrich; Linz, Bodo (Cell Communication and Signaling, 2024)
Single nucleotide polymorphisms (SNPs) account for significant genomic variability in microbes, including the highly diverse gastric pathogen Helicobacter pylori. However, data on the effects of specific SNPs in pathogen-host interactions are scarce. Recent functional studies unravelled how a serine/leucine polymorphism in serine protease HtrA affects the formation of proteolytically active trimers and modulates cleavage of host cell-to-cell junction proteins during infection. A similar serine/leucine mutation in the carbohydrate binding domain of the adhesin BabA controls binding of ABO blood group antigens, enabling binding of either only the short Lewis b/H antigens of blood group O or also the larger antigens of blood groups A and B. Here we summarize the functional importance of these two remarkable bacterial SNPs and their effect on the outcome of pathogen-host interactions.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Adaptation; BabA; Evolution; HtrA; SNP

Type iv secretion and signal transduction of Helicobacter pylori caga through interactions with host cell receptors - Backert, Steffen; Tegtmeyer, Nicole (Toxins, 2017)
Helicobacter pylori is a highly successful human bacterium, which is exceptionally equipped to persistently inhabit the human stomach. Colonization by this pathogen is associated with gastric disorders ranging from chronic gastritis and peptic ulcers to cancer. Highly virulent H. pylori strains express the well-established adhesins BabA/B, SabA, AlpA/B, OipA, and HopQ, and a type IV secretion system (T4SS) encoded by the cag pathogenicity island (PAI). The adhesins ascertain intimate bacterial contact to gastric epithelial cells, while the T4SS represents an extracellular pilus-like structure for the translocation of the effector protein CagA. Numerous T4SS components including CagI, CagL, CagY, and CagA have been shown to target the integrin-β1 receptor followed by translocation of CagA across the host cell membrane. The interaction of CagA with membrane-anchored phosphatidylserine and CagA-containing outer membrane vesicles may also play a role in the delivery process. Translocated CagA undergoes tyrosine phosphorylation in C-terminal EPIYA-repeat motifs by oncogenic Src and Abl kinases. CagA then interacts with an array of host signaling proteins followed by their activation or inactivation in phosphorylation-dependent and phosphorylation-independent fashions. We now count about 25 host cell binding partners of intracellular CagA, which represent the highest quantity of all currently known virulence-associated effector proteins in the microbial world. Here we review the research progress in characterizing interactions of CagA with multiple host cell receptors in the gastric epithelium, including integrin-β1, EGFR, c-Met, CD44, E-cadherin, and gp130. The contribution of these interactions to H. pylori colonization, signal transduction, and gastric pathogenesis is discussed.
Created from Fastlane, Scopus look-up
Keywords: Cortactin; Glycogen synthase kinase 3beta GSK3β; Janus kinase; P120 catenin; Phosphatase Shp-2; Phosphatidylinositol 3-kinase PI3K; Portioning kinase Par1b; Protein kinase Akt; STAT3; β-catenin

Type IV Secretion in Gram-Negative and Gram-Positive Bacteria - Backert, Steffen; Grohmann, Elisabeth (Springer, 2017)
Type IV secretion systems (T4SSs) are highly versatile membrane-associated transporter machines used by Gram-negative and Gram-positive bacteria to deliver substrate molecules to a large variety of target cells. This volume summarizes our current knowledge of the large variety and structural diversity of T4SSs in pathogenic Escherichia, Agrobacterium, Legionella, Coxiella, Bartonella, Helicobacter, Enterococcus and other species. Divided into 13 chapters contributed by leading experts, it presents findings that significantly enhance our understanding of how various pathogens manipulate host cell functions to trigger bacterial uptake, promote intracellular growth, suppress defense mechanisms and of how bacteria spread antibiotic resistances, thus facilitating bacterial colonization and disease development. The book is an invaluable source of information for researchers and clinicians.<br
Keywords: Gram-negative bacteria; Intracellular lifestyle; Legionella; Bartonella infections; Helicobacter pylori; Membrane-associated transporter complexes; Gram-positive bacteria; Eukaryotic cells; Interbacterial transfer; Antibiotic resistance; T4SS; infectious diseases

Type IV Secretion in Gram-negative and Gram-positive Bacteria. - Grohmann, Elisabeth; Christie, Peter J.; Waksman, Gabriel; Backert, Steffen (Molecular Microbiology, 2018)

Type IV Secretion in Gram-positive and Gram-negative Bacteria - Backert, Steffen; Grohmann, E. (Springer, 2019)

Type IV secretion of Helicobacter pylori CagA into oral epithelial cells is prevented by the absence of CEACAM receptor expression - Tegtmeyer, Nicole; Ghete, Tabita Denisia; Schmitt, Verena; Remmerbach, Torsten; Cortes, Maria Celeste C.; Bondoc, Edgardo M.; Graf, Hans Ludwig; Singer, Bernhard B.; Hirsch, Christian; Backert, Steffen (Gut Pathogens, 2020)
Background: Helicobacter pylori typically colonizes the human stomach, but it can occasionally be detected in the oral cavity of infected persons. Clinical outcome as a result of gastric colonization depends on presence of the pathogenicity island cagPAI that encodes a type-IV secretion system (T4SS) for translocation of the effector protein CagA and ADP-heptose. Upon injection into target cells, CagA is phosphorylated, which can be demonstrated by in vitro infection of the gastric epithelial cell line AGS, resulting in cell elongation. Here we investigated whether H. pylori can exert these responses during interaction with cells from the oral epithelium. To this purpose, three oral epithelial cell lines, HN, CAL-27 and BHY, were infected with various virulent wild-type H. pylori strains, and CagA delivery and ADP-heptose-mediated pro-inflammatory responses were monitored. Results: All three oral cell lines were resistant to elongation upon infection, despite similar bacterial binding capabilities. Moreover, T4SS-dependent CagA injection was absent. Resistance to CagA delivery was shown to be due to absence of CEACAM expression in these cell lines, while these surface molecules have recently been recognized as H. pylori T4SS receptors. Lack of CEACAM expression in HN, CAL-27 and BHY cells was overcome by genetic introduction of either CEACAM1, CEACAM5, or CEACAM6, which in each of the cell lines was proven sufficient to facilitate CagA delivery and phosphorylation upon H. pylori infection to levels similar to those observed with the gastric AGS cells. Pro-inflammatory responses, as measured by interleukin-8 ELISA, were induced to high levels in each cell line and CEACAM-independent. Conclusions: These results show that lack of CEACAM receptors on the surface of the oral epithelial cells was responsible for resistance to H. pylori CagA-dependent pathogenic activities, and confirms the important role for the T4SS-dependent interaction of these receptors with H. pylori in the gastric epithelium.
CRIS-Team Scopus Importer:2020-06-02
Keywords: AGS; BHY; CagA; CAL-27; CEACAM; HN; Signaling; T4SS; Type IV secretion; Tyrosine kinases

Type IV secretion systems and their effectors in bacterial pathogenesis - Backert, Steffen; Meyer, Thomas F. (Current Opinion in Microbiology, 2006)
Type IV secretion systems (T4SSs) are membrane-associated transporter complexes used by various bacteria to deliver substrate molecules to a wide range of target cells. T4SSs are involved in horizontal DNA transfer to other bacteria and eukaryotic cells, in DNA uptake from or release into the extracellular milieu, in toxin secretion and in the injection of virulence factors into eukaryotic host target cells by several mammalian pathogens. Rapid progress has been made towards defining the structures and functions of T4SSs, identifying the translocated effector molecules and elucidating the mechanisms by which the effectors subvert eukaryotic cellular processes during infection. These findings have had an important impact on our understanding of how these pathogens manipulate host cell functions to trigger bacterial uptake, facilitate intracellular growth and suppress defence mechanisms, thus facilitating bacterial colonization and disease development. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Tyrosine-phosphorylated bacterial effector proteins: The enemies within - Backert, Steffen; Selbach, Matthias (Trends in Microbiology, 2005)
The tyrosine phosphorylation of proteins has a central role during signal transduction in eukaryotes. Recent progress shows that tyrosine phosphorylation is also a common feature of several effector proteins translocated by bacterial type III and type IV secretion systems. The involvement of these secretion systems in disease development is exemplified by a variety of pathogenic processes: pedestal formation (Tir of EPEC and Citrobacter), cell scattering (CagA of Helicobacter), invasion (Tarp of Chlamydia) and possibly proinflammatory responses and cell proliferation (BepD-F of Bartonella). The discovery that different bacterial pathogens use this common strategy to subvert host-cell function suggests that more examples will soon emerge. © 2005 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Tyrosine phosphorylation patterns and size modification of the Helicobacter pylori CagA protein after translocation into gastric epithelial cells. - Backert, Steffen; Müller, E.C.; Jungblut, P.R.; Meyer, Thomas F. (Proteomics, 2001)
Helicobacter pylori is one of the most common bacterial pathogens that causes a variety of gastric diseases. During infection, the immuno-dominant H. pylori CagA protein is translocated and tyrosine-phosphorylated in gastric epithelial cells. We compared tyrosine phosphorylation patterns of five CagA variants by two-dimensional electrophoresis (2-DE) and immunoblotting studies. Tyrosine-phosphorylated CagA was detected as two distinct protein species in strains P12, P227, G27 and 26695 suggesting that two tyrosine residues of CagA can be phosphorylated both separately and simultaneously. Prediction programs revealed the presence of three putative tyrosine phosphorylation motifs in the sequences of CagA. Mutations in these motifs were identified suggesting that only two putative phosphorylation-relevant tyrosines are present in each CagA variant. CagA of strain J99 was found to be unique because essential codons were mutated in each of the three motifs and, consequently, revealed no tyrosine phosphorylation signals at all. These findings support the view that CagA from different H. pylori strains can be tyrosine-phosphorylated at one or two out of three predicted positions. Additionally, truncated CagA protein species of about 100-105 kDa (p100CagA) have been detected after infection with some of the H. pylori strains. The isoelectric point determined by both 2-DE and sequence analysis suggested that p100CagA represents the amino (N)-terminal part of the protein. Translocation, tyrosine phosphorylation and size modification of CagA might be involved in host signal transduction and development of gastric disease.

Unique features of the mitochondrial rolling circle-plasmid mp1 from the higher plant Chenopodium album (L.) - Backert, Steffen; Meißner, Karsten; Börner, Thomas (Nucleic Acids Research, 1997)
We analyzed the structure and replication of the mitochondrial (mt) circular DNA plasmid mp1 (1309 bp) from the higher plant Chenopodium album (L.). Two dimensional gel electrophoresis (2DE) revealed the existence of oligomers of up to a decamer in addition to the prevailing monomeric form. The migration behavior of cut replication intermediates during 2DE was consistent with a rolling circle (RC) type of replication. We detected entirely single-stranded (ss) plasmid copies hybridizing only with one of the two DNA strands. This result indicates the occurence of an asymmetric RC replication mechanism. mp1 has, with respect to its replication, some unique features compared with bacterial RC plasmids. We identified and localized a strand-specific nicking site (origin of RC replication) on the plasmid by primer extension studies. Nicks in the plasmid were found to occur at any one of six nucleotides (TAAG/GG) around position 735 of the leading strand. This sequence shows no homology to origin motifs from known bacterial RC replicons. mp1 is the first described RC plasmid in a higher plant.
Created from Fastlane, Scopus look-up

Unique TLR9 Activation by Helicobacter pylori Depends on the cag T4SS, But Not on VirD2 Relaxases or VirD4 Coupling Proteins - Tegtmeyer, Nicole; Linz, Bodo; Yamaoka, Yoshio; Backert, Steffen (Current Microbiology, 2022)
The genomes of the gastric bacterial pathogen Helicobacter pylori harbor multiple type-IV secretion systems (T4SSs). Here we analyzed components of three T4SSs, the cytotoxin-associated genes (cag) T4SS, TFS3 and TFS4. The cag T4SS delivers the effector protein CagA and the LPS-metabolite ADP-heptose into gastric epithelial cells, which plays a pivotal role in chronic infection and development of gastric disease. In addition, the cag T4SS was reported to facilitate conjugative transport of chromosomal bacterial DNA into the host cell cytoplasm, where injected DNA activates intracellular toll-like receptor 9 (TLR9) and triggers anti-inflammatory signaling. Canonical DNA-delivering T4SSs in a variety of bacteria are composed of 11 VirB proteins (VirB1-11) which assemble and engage VirD2 relaxase and VirD4 coupling proteins that mediate DNA processing and guiding of the covalently bound DNA through the T4SS channel. Nevertheless, the role of the latter components in H. pylori is unclear. Here, we utilized isogenic knockout mutants of various virB (virB9 and virB10, corresponding to cagX and cagY), virD2 (rlx1 and rlx2), virD4 (cag5, traG1/2) and xerD recombinase genes in H. pylori laboratory strain P12 and studied their role in TLR9 activation by reporter assays. While inactivation of the structural cag T4SS genes cagX and cagY abolished TLR9 activation, the deletion of rlx1, rlx2, cag5, traG or xerD genes had no effect. The latter mutants activated TLR9 similar to wild-type bacteria, suggesting the presence of a unique non-canonical T4SS-dependent mechanism of TLR9 stimulation by H. pylori that is not mediated by VirD2, VirD4 and XerD proteins. These findings were confirmed by the analysis of TLR9 activation by H. pylori strains of worldwide origin that possess different sets of T4SS genes. The exact mechanism of TLR9 activation should be explored in future studies.
CRIS-Team Scopus Importer:2022-03-11

Untersuchungen zur Struktur und Replikation des Mitochondriengenoms von Chenopodium album (L.) - Backert, Steffen (Friedrich-Alexander-Universität Erlangen-Nürnberg, 1996)

Unusual Manifestation of Live Staphylococcus saprophyticus, Corynebacterium urinapleomorphum, and Helicobacter pylori in the Gallbladder with Cholecystitis - Backert, Steffen; Tegtmeyer, Nicole; Oyarzabal, Omar A.; Osman, Dana; Rohde, Manfred; Grützmann, Robert; Vieth, Michael (International Journal of Molecular Sciences, 2018)
Culture-independent studies have identified DNA of bacterial pathogens in the gallbladder under pathological conditions, yet reports on the isolation of corresponding live bacteria are rare. Thus, it is unclear which pathogens, or pathogen communities, can colonize the gallbladder and cause disease. Using light microscopy, scanning electron microscopy, culture techniques, phylogenetic analysis, urease assays and Western blotting, we investigated the presence of live bacterial communities in the gallbladder of a cholecystitis patient after cholecystectomy. 16S rRNA gene sequencing of isolated bacterial colonies revealed the presence of pathogens most closely resembling Corynebacterium urinapleomorphum nov. sp., Staphylococcus saprophyticus and Helicobacter pylori. The latter colonies were confirmed as H. pylori by immunohistochemistry and biochemical methods. H. pylori cultured from the gallbladder exhibited both the same DNA fingerprinting and Western cagA gene sequence with ABC-type EPIYA (Glu-Pro-Ile-Tyr-Ala) phosphorylation motifs as isolates recovered from the gastric mucus of the same patient, suggesting that gastric H. pylori can also colonize other organs in the human body. Taken together, here we report, for the first time, the identification and characterization of a community consisting of live S. saprophyticus; C. urinapleomorphum, and H. pylori in the gallbladder of a patient with acute cholecystitis. Their potential infection routes and roles in pathogenesis are discussed.
EVALuna2:210710

Use of a novel coinfection system reveals a role for Rac1, H-Ras, and CrkII phosphorylation in Helicobacter pylori-induced host cell actin cytoskeletal rearrangements - Brandt, Sabine; Shafikhani, Sasha; Balachandran, Priya; Jin, Shouguang; Hartig, Roland; König, Wolfgang; Engel, Joanne; Backert, Steffen (FEMS Immunology and Medical Microbiology, 2007)
The Helicobacter pylori CagA protein induces profound morphological changes in the host cytoskeleton and cell scattering, but the signalling involved is poorly understood. Pseudomonas aeruginosa also affects host actin cytoskeleton in a variety of ways by injecting the ExoS and ExoT toxins which encode N-terminal GTPase activating protein and C-terminal ADP-ribosyltransferase (ADPRT) activities. In this study we developed a novel coinfection assay to gain new insights into CagA effector protein functions. We found that P. aeruginosa injecting either ExoT or ExoS efficiently prevented the H. pylori-induced scattering phenotype. Both the Rho-GAP and the ADPRT domains of ExoS were needed to block the H. pylori-induced actin cytoskeletal rearrangements, whereas either domain of ExoT was sufficient for this activity. This strategy revealed common pathways subverted by different pathogens, and aided in the definition of signalling cascades that control the CagA-mediated cell scattering and elongation. We identified Crk adapter proteins, Rac1 and H-Ras, but not RhoA or Cdc42, which are the ExoS and/or ExoT targets, as crucial components of the CagA-induced phenotype. In addition, we show that ADP-ribosylation of CrkII by ExoT blocks phosphorylation of CrkII at Y-221, which is also important for the CagA-induced signalling. © 2007 Federation of European Microbiological Societies.
Created from Fastlane, Scopus look-up
Keywords: Helicobacter pylori; Molecular pathogenesis; Pathogenicity island; Pseudomonas aeruginosa; Toxin; Type III and type IV secretion

Use of cellulose filters to isolate Campylobacter spp. from naturally contaminated retail broiler meat - Speegle, Leslie; Miller, Michael E.; Backert, Steffen; Oyarzabal, Omar A. (Journal of Food Protection, 2009)
Membrane filtration has been used to isolate Campylobacter spp. from feces, although ∼5 log CFU/g must be present in the sample. Few studies have attempted to use filter membranes for the isolation of Campylobacter from foods. We investigated the minimum number of thermotolerant Campylobacter cells that pass through cellulose filters, the effect of different cell conditions on the rate of passage, and the minimum number of cells that could pass the filters from enriched broiler meat naturally contaminated with Campylobacter spp. Cellulose filters with 0.65-μm pore sizes retained fewer cells and were more effective than filters with 0.45-μm pore sizes. Scanning electron microscopy revealed that 15 min of contact of the filters with agar plates allowed for the passage of most bacteria. The minimum number of bacteria required to pass through the filters was contingent on cell conditions; nonmotile cells were retained more than motile cells (P < 0.05). The minimum number of motile bacteria from 24-h cultures and centrifuged cells were 2.2 and 2.1 log CFU, respectively, while the number of coccoid and nonmotile (flaAIB∼ mutant) cells were 4.1 and 3.4 log CFU, respectively. Broiler meat samples enriched in Bolton's broth supplemented with 5% lysed blood showed that approximately 1.7 log CFU of Campylobacter can be filtered to pure colonies on agar plates. These results demonstrate that the motility of the bacteria influences passage through cellulose filters and that 0.65-μm-pore-size filters on agar plates help obtain pure Campylobacter colonies from enriched food samples. Copyright © International Association for Food Protection.
Created from Fastlane, Scopus look-up

Varying Pathogenicity of Campylobacter jejuni Isolates - Oyarzabal, Omar A.; Backert, Steffen (Foodborne Pathogens, 2017)
Campylobacter jejuni and C. coli are typical zoonotic pathogens that are leading causes of bacterial gastroenteritis in humans worldwide. The C. jejuni genome has a high plasticity and the molecular basis for the commensalism in some animals and the expression of virulence in humans is not well understood. C. jejuni colonizes the distal ileum and colon in humans, and ingestion of a few hundred live cells can infect humans. Adherence of C. jejuni to the target cells involves various adhesion factors, and the flagellar export machinery is a crucial secretory device to help C. jejuni entering the host cell. Although the intracellular survival of C. jejuni in non-phagocytic cells has been well documented, there are conflicting reports on the persistence capacity of C. jejuni in phagocytic immune cells. Several animal model systems have been used to study different aspects of this pathogen’s invasion and pathogenicity phases. One of these models shows that the host-specific composition of microbiota is an important determinant in the occurrence of related disease, which complicates even more the study of the interaction of C. jejuni with mammalian host cells. The infant mice model shows promise to be a model system that closely mimics what happens in human cells after invasion by C. jejuni.<br
Keywords: Campylobacte Jejuni; Adhesion; Animal model; Epidemiology; Invasion; Pathogenicity

VirB2 and VirB5 proteins: specialized adhesins in bacterial type-IV secretion systems? - Backert, Steffen; Fronzes, Remi; Waksman, Gabriel (Trends in Microbiology, 2008)
Many type-IV secretion systems (T4SSs) of plant and human pathogens assemble a pilus used to inject virulence molecules (effectors) into host target cells. The T4SS of Agrobacterium tumefaciens consists of VirB1-VirB11 and VirD4 proteins. Whether targeting of T4SSs to the host requires a T4SS-adhesin that specifically engages host receptors for delivery of effectors has, until recently, remained unclear. Recent data of Agrobacterium and Helicobacter indicate that two classes of T4SS components, VirB2 and VirB5, might function as adhesins that mediate host-cell targeting through binding to specific host receptors. Here, we discuss this important issue and recent progress in the field. © 2008 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up

Virulence factors of Helicobacter pylori - Backert, Steffen; Mimuro, H.; Israel, D. A.; Peek, R. M. (Helicobacter pylori in the 21st Century: Advances in Molecular and Cellular Microbiology, 2010)
CRIS-Team Scopus Importer:2020-09-18

Vitamin d reverses disruption of gut epithelial barrier function caused by campylobacter jejuni - Lobo de Sá, Fábia D.; Backert, Steffen; Nattramilarasu, Praveen K.; Mousavi, Soraya; Sandle, Geoffrey I.; Bereswill, Stefan; Heimesaat, Markus M.; Schulzke, Jörg Dieter; Bücker, Roland (International Journal of Molecular Sciences, 2021)
Infections by the zoonotic foodborne bacterium Campylobacter jejuni (C. jejuni) are among the most frequent causes of bacterial gastroenteritis worldwide. The aim was to evaluate the relationship between epithelial barrier disruption, mucosal immune activation, and vitamin D (VD) treatment during C. jejuni infection, using intestinal epithelial cells and mouse models focused on the interaction of C. jejuni with the VD signaling pathway and VD treatment to improve C. jejuni-induced barrier dysfunction. Our RNA-Seq data from campylobacteriosis patients demonstrate inhibition of VD receptor (VDR) downstream targets, consistent with suppression of immune function. Barrierpreserving effects of VD addition were identified in C. jejuni-infected epithelial cells and IL-10−/− mice. Furthermore, interference of C. jejuni with the VDR pathway was shown via VDR/retinoid X receptor (RXR) interaction. Paracellular leakiness of infected epithelia correlated with tight junction (TJ) protein redistribution off the TJ domain and apoptosis induction. Supplementation with VD reversed barrier impairment and prevented inhibition of the VDR pathway, as shown by restoration of transepithelial electrical resistance and fluorescein (332 Da) permeability. We conclude that VD treatment restores gut epithelial barrier functionality and decreases bacterial transmigration and might, therefore, be a promising compound for C. jejuni treatment in humans and animals.
CRIS-Team Scopus Importer:2021-08-27
Keywords: Apoptosis; Campylobacteriosis; HT-29/B6 cell; Intestinal epithelial barrier function; Leaky gut; Mouse model; RNA Sequencing; Tight junction; Translocation; Vitamin D receptor signaling pathway

What a disorder: proinflammatory signaling pathways induced by Helicobacter pylori. - Backert, Steffen; Naumann, Michael (Trends in Microbiology, 2010)
Infection of gastric epithelial cells with Helicobacter pylori induces strong proinflammatory responses by activating nuclear transcription factors NF-κB and AP-1. Several reports indicate that multiple bacterial factors and cellular molecules are involved in this signaling. Injected peptidoglycan, CagA or OipA and urease, and at least 16 different signaling cascades have been implicated in H. pylori-induced proinflammatory signaling. Many of these reports are contradictory, thus generating a highly puzzling scenario. Here we discuss the pros and cons of the multiple signaling activities in the induction of proinflammatory responses and associated problems, and give suggestions for finding ways out of this dilemma.